Assessing the environmental–economic viability of expressway photovoltaics in China: A spatio–temporal life cycle perspective - Liyao Wang; Xiaowei Cui; Pengfei Zhou; Shidong Guo; Xiaoteng Zhou; Jinglan Hong; Wei Liu; Yanan Zhang; Zhaojie Cui; Xianfeng Tan (Environmental Impact Assessment Review, 2027)

Risk identification and early warning of disaster-causing organisms in the cooling water intake area of a coastal nuclear power plant - Heming Cui; Hong Zhou; Cunchao Wu; Mingbo Zhao; Xiangyuan Xu; Haiping Li (Marine Pollution Bulletin, 2026)

Estimation of soil inorganic carbon using simulated satellite multispectral data and environmental covariates in arid oases of southern Xinjiang, China - Zhibo Cui; Yongsheng Hong; Bifeng Hu; Songchao Chen; Jie Peng; Abdul Mounem Mouazen (Soil and Tillage Research, 2026)

A bibliometrics review of non-CO2 greenhouse gas reduction strategies - Yi-Ming Wei; Si-Yu Liu; Li-Jing Liu; Lan-Cui Liu; Qiao-Mei Liang; Xiao-Chen Yuan; Hong-Dian Jiang; Pallav Purohit; Felix Creutzig; Hua Liao; Biying Yu (Energy and Climate Change, 2026)

The hidden roles of insect symbiotic viruses in pest control and arbovirus transmission - Hong Lu; Yumei Fu; Jiahui Tong; Feng Cui (Current Opinion in Insect Science, 2026)

Perillaldehyde reduces mitochondrial oxidative stress damage by regulating KCNT2/NR1D1 protein activity in vascular dementia rats - Qian-qian Wang; Hong-dou Zhang; Pei-yao Liu; Chun-rui Zhang; Bao-yue Cui; Xi-yue Li; Meng-yao zhao; Jin-he Yang; Peng Li; Ya-ling Yin; Xue-yu Sun (Molecular Biology Reports, 2026)

The progress of mitochondrial function and transfer in stem cell regulation and therapy - Yubing Zhang; Zhuojian Qu; Zhiliang Guo; Lijuan Zhang; Hong Li; Xiaoyun Zhang; Xiumei Guan; Xiaodong Cui; Wenxu Wang; Min Cheng (Journal of Physiology and Biochemistry, 2026)

Combined exposure to wildfire ash and road salts reshapes skin and gut microbiota and reduces fitness in amphibians - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Yue-liang Pan; Wen-jing Dong; Ming-da Xu; Zhi-wen Luo; Li-yong Cui (Environmental Research, 2026)

Color- and time-programmed photoswitchable fluorescent nanoparticles for multi-level time-resolved information encryption and dual-modal dynamic anti-counterfeiting - Hong Wang; Yi Zhao; Fengjiao Chen; Kairong Zang; Yong Tian; Xiaomei Zhao; Fucheng Zhang; Fuhua Huang; Jiaxi Cui; Jian Chen (Chemical Engineering Journal, 2026)

Dual-tailoring of microenvironment and electronic structure in tandem catalysts for highly selective CO2-to-ethanol electroreduction - Shuo Cui; Cheng Yang; Tingting Tang; Xinjie Liu; Xinlong Huang; Junyang Li; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2026)

Rainfall modulates the divergent responses of bacterial and fungal communities to naphthalene contamination in soil - Yuntao Zhao; Duo Zhang; Xin Wang; Yong Cui; Ying Guo; Wei Su; Chen Hong; Wenxin Li; Mengwan Lin; Yixiang Chen; Haobo Ya; Jiayu Chen; et al. (Applied Soil Ecology, 2026)

Octanoic acid alleviates intestinal oxidative stress via the AMPK/PGC-1α pathway in large yellow croaker larvae - Yongtao Liu; Yucong Hong; Chuanwei Yao; Yifan Zhou; Yayu Qu; Zhiwei Chen; Zengqi Zhao; Wei Fang; Kun Cui; Kangsen Mai; Qinghui Ai (Aquaculture, 2026)

Patterns and mechanisms of cross-media antimicrobial resistance development in a typical reclaimed water-receiving urban river - Bang-Ze Li; Shu-Hao Du; Han-Lin Cui; Xin-Xin Gao; Jia-Hao Wu; Bei-Ying Li; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2026)

2D and 3D urban green space configurations shape airborne microbiome diversity and potential pathogen abundance - Yujia Bai; Mingyu Liao; Peter M. van Bodegom; Laiyi Li; Anyi Hu; Mengran Zhou; Shenghui Cui; Hong Ye (Urban Forestry & Urban Greening, 2026)

Relationship between genetic polymorphisms of Stannioncalcin 1 and Bone mineral density or serum levels in Chinese geriatrics - Siwen Yu; Ke Xu; Wenchao Fei; Yunqing Cui; Tong Lu; Yang Hong; Yinghua Li (Next Research, 2026)

Enhanced bio-electrochemical decolorization of azo dye by an rGO/ polyaniline-modified biocathode: Performance improvement and cathodic microbiome reshaping - Tao Hou; Hong-Li Lu; Naif Abdullah Al-Dhabi; Ai-Hong Chen; Wang-Wang Tang; Meng-Yuan Li; Dan Cui (Journal of Environmental Chemical Engineering, 2026)

Catalytic ozonation with N, S co-doped sludge biochar for decontamination: Performance and mechanistic insights - Xinyi Tao; Weiwei Chen; Xuehong Fan; Rui Hu; Xuejian Wang; Shiquan Sun; Yu-Hong Cui; Zheng-Qian Liu (Journal of Environmental Chemical Engineering, 2026)

Catalytic oxypyrolysis of gaseous dibutyl phthalate and energy-efficient integration with thermal desorption process - Xiaoyu Wu; Suyun Hong; Mifen Cui; Xu Qiao; Zhuxiu Zhang (Journal of Environmental Chemical Engineering, 2026)

Electronic, optical and mechanical properties, and photocatalytic water splitting of Janus ZrHfCO2 under biaxial strain: First-principles prediction - Rui-Wen Yan; Hao Zhang; Xiao-Hong Li; Rui-Zhou Zhang; Hong-Ling Cui (Journal of Environmental Chemical Engineering, 2026)

Data-driven intelligent modeling for superheater wall temperature prediction and operational optimization of 1000 MW deep peak shaving coal-fired power plants - Xingliang Ji; Yanming Wang; Xiang Ma; Liming Cui; Jiawei Wang; Yongzhong Ni; Hongyuan Li; Tao Wang; Yongsheng Zhang; Hong Xu (Fuel, 2026)

Inhibitory mechanism of phloretin on the AgrA LytTR domain-agr operon complex formation and its application in beef - Hong Li; Haiying Cui; Tariq Aziz; Ashwag Shami; Abdelrahman R. Ahmed; Fakhria A. Al-Joufi; Lin Lin (Food Research International, 2026)

Percolation-tuned mesostructured capacitive sensor for physiological signal detection and acoustic recognition - Weili Zhao; Vuong Dinh Trung; Yinjia Zhang; Xinghua Hong; Kun Chen; Jun Natsuki; Lina Cui; Toshiaki Natsuki (Chemical Engineering Journal, 2026)

Pilot-scale electricity-driven production of single-cell protein from CO₂ by hydrogen-oxidizing bacteria - Hong Zhang; Jiahao Cao; Jinpeng Yu; Xueqi Wang; Yang Li; Bingyan Wang; Wenfang Cai; Kai Cui; Kun Guo (Chemical Engineering Journal, 2026)

The impact of the blue bay initiative on the coastal tourism economy in China: an intensity difference-in-differences analysis - Yuhu Cui; Hanxiao Xu; Guosheng Han; Hong Ching Goh; Lin Yang (Environment, Development and Sustainability, 2026)

A fully human antibody A140 neutralizes abrin toxin via lysosomal intracellular mechanisms, confers potent protection in vitro and in vivo, and reverses transcriptomic dysregulation with a Favorable safety profile - Feng Qin; Shi-You Chen; Peng Lin; Bin Wang; Xin Fu; Jian-Li Jiang; Hong-Yong Cui; Shi-Jie Wang (Toxicology and Applied Pharmacology, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

Constraining marine silicate alteration in volcanic material-rich continental margin sediments since the last Glacier Maximum evidenced by stable Si isotopes - Quanchao Cui; Min Luo; Wei-Li Hong; Tzu-Hao Huang; Weidong Sun; Xiaole Sun (Geochimica et Cosmochimica Acta, 2026)

From outcrossing to reproductive assurance: Seasonal plasticity in the breeding system of bi-seasonal flowering Tamarix ramosissima Ledeb. (Tamaricaceae) - Meng-Yuan Zhang; Jia-Hui Leng; Hong-Ju Cui; Jun-Xue Shi; Yuan-yuan Li; Xiang Shi (Flora, 2026)

Carbon source-driven anaerobic assimilation of dye-derived dissolved organic nitrogen: A low-carbon strategy with performance and mechanism insights - Xumeng Lin; Huahan Huang; Ying Wu; Ling Xiong; Yang Meng; Faheem Ahmed Ghori; He Cui; Yinchuan Yang; Hong Chen; Gang Xue (Environmental Research, 2026)

Recovery trajectories of amphibian skin microbiota following ash exposure across translocation and natural recovery scenarios - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Ming-da Xu; Yue-liang Pan; Li-yong Cui (Environmental Pollution, 2026)

High-fidelity phase-change transfer platform for laser-induced graphene toward multifunctional flexible electronics - Zhao Li; Yanping Song; Wenjie Shao; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Zhuang Miao; Shudong Zhang; Cui Liu; Min Xi; et al. (Chemical Engineering Journal, 2026)

Bismuth-embedded hard carbon derived from Solidago canadensis toward sodium-ion batteries - Jiacheng Shen; Liang Liu; Hong Cui; Yiting Dai; Ge Lin; Yuanzhe Wang; Ziyao Zhang; Jiantie Xu (Chemical Engineering Journal, 2026)

Structure characterization and multi-target inhibitory activities of fucosylated chondroitin sulfate from sea cucumber Thelenota anax - Ying Hong; Ying Pan; Guangyu Zhu; Jing Wen; Rou Chen; Lige Cui; Huilin Chen; Tong Wu; Ronghua Yin; Jinhua Zhao (Carbohydrate Polymers, 2026)

Hydrogel-encapsulated microalgae-bacteria consortia for resilient saline agriculture - Xiao-Jing Wang; Nan Wu; Xiao Yu; Si-Ming Li; Zi-Rui Yang; Zhi-Hai Zhong; Kang Wang; Hong-Li Cui; Cheng-Gang Ren; Song Qin (World Journal of Microbiology and Biotechnology, 2026)

CXCL12/CXCR4 signaling governs ischemic neurovascular pathophysiology and repair: a multidimensional contextual analysis - Shahram Eisa-Beygi; Hao Wu; Kui Cui; Kulandaisamy Arulsamy; Bo Zhu; Beibei Wang; Bandana Singh; Krishan Gupta; Jianing Gao; Scott Wong; Joyce Bischoff; Hanqiang Deng; et al. (Angiogenesis, 2026)

Endothelial progenitor cells-derived exosomes reduce ferroptosis and promote neovascularization after intracranial atherosclerosis in association with the NCOA4/FTH1 cascade modulation - Lihong Zhang; Cui Wang; Zhanjun Wu; Hong Qu; Jitong Ma; Di Li (Drug Delivery and Translational Research, 2026)

A Causal Framework for Quantifying Task-Driven Selection Bias in Historical Deployment of Integrated Underwater Communication and Positioning Networks - Lipeng Huo; Jifeng Zhu; Jian Wang; Heng Wen; Zheng Peng; Xiaoxin Guo; Yusha Liu; Jun-Hong Cui (Journal of Marine Science and Engineering, 2026)
To address task-driven selection bias in historical deployment records, this study proposes a structural-causal-model-based framework for quantifying bias in the utility assessment and deployment-effect estimation of integrated underwater communication and positioning networks. Four datasets were constructed under unbiased, communication-dominant, positioning-dominant, and joint-biased sampling mechanisms, and double machine learning (DML) was adopted to analyze overall utility and its communication/localization components under decision factors. The simulation results demonstrate that communication-dominated data overestimates overall utility by 23.5%, while location-dominated data underestimates by 21.4%. CATE analysis further identifies noise spectral level as the strongest effect modifier (feature importance 0.76). The sea trial results show close agreement between simulated CRLB and measured RMSE, which supports the physical plausibility of the positioning utility model and the WOA23-based simulation pipeline underlying the causal analysis.

Maize/peanut intercropping alleviates continuous peanut cropping stress via root exudate– and rhizosphere bacteria–mediated mechanisms - Zizheng Li; Li Cui; Jie Zhang; Tingting Yi; Hong Yu; Jialei Zhang; Sha Yang; Nianyuan Jiao; Feng Guo; Shubo Wan (Soil and Tillage Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Formulation and biological evaluation of a Perilla frutescens seed oil nanoemulsion: A novel therapeutic agent for alleviating gut-liver axis inflammation - Jia-Yu Ye; Wei Zhang; Mei Qin; Hong-Jie Cui; Jian Li (Research in Veterinary Science, 2026)

Task allocation in distributed multi-UUV: An adaptive fuzzy response threshold method with task-age awareness - Lianpeng Qiu; Jiangzhou Zhu; Yusha Liu; Jun-Hong Cui (Ocean Engineering, 2026)

Adaptive multi-mode underwater acoustic communication: A comprehensive survey from physical modulations to intelligent decision-making - Jiangzhou Zhu; Lianpeng Qiu; Yusha Liu; Zheng Peng; Jun-Hong Cui (Ocean Engineering, 2026)

Time-dependent citrate-mediated precipitation inhibition in uranium column leaching: Mechanistic insights into pore evolution and uranium migration - Xiaowei Zhou; Jing Sun; Qian Li; Guangyue Li; Shangze Li; Ling Xiao; Hong Shu; Haiying Fu; Ting Li; Yongdong Wang; Zhao Cui; Guosen Xie (Journal of Hazardous Materials, 2026)

Metabolic complementarity in LAB-yeast co-fermentation associates with enhanced ester aroma in cream cheese - Beibei Duan; Yueyue Zhou; Siyu Wang; Ling Yan; Yujie Lin; linze Li; Bin Xue; Rui Huang; Yipan Zhang; Yue Cui; Nan Wu; Xiangting Kong; et al. (Food Research International, 2026)

Investigation of the interaction between phloretin and Staphylococcus aureus toxin proteins and its application in chicken meat - Hong Li; Ce Shi; Tariq Aziz; Nawal Al-Hoshani; Manal F. Elkhadragy; Abdelrahman R. Ahmed; Haiying Cui; Lin Lin (Food Chemistry, 2026)

Intestinal inflammation is associated with higher cadmium burden, potentially via compromised gut barriers: Evidence from NHANES and colitic mouse model - Jin-Feng Xi; Chen Li; Lei Zhou; Bing-Zi Cui; Dongmei Zhou; Hong-Bo Li (Environmental Pollution, 2026)

Corrigendum to “Catechol-induced assembly to enhance the performance of antimicrobial peptide fully” [Chem. Eng. J. Volume 524 (2025) 169195] - Xiao Wang; Yuanyuan He; Beibei Cui; Yuan Feng; Jingjing Lin; Xirui Long; Yanchao Wang; Zhen Li; Feng Luo; Jiehua Li; Hong Tan (Chemical Engineering Journal, 2026)

Chloride-repelling and interfacial hydroxyl enrichment synergy in Co-Pi@Cr2O3-CoP for high current density alkaline seawater electrolysis - Tingting Tang; Cheng Yang; Xinlong Huang; Shuo Cui; Xinjie Liu; Junyang Li; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2026)

Chromosomal collinearity drives meiotic instability in Brassica autoallopolyploid - Fang Yue; Qinfei Li; Jiaqin Mei; Lei Wang; Yixin Cui; Kusum Rana; Fajing Zheng; Junxiong Xu; Chunlei Shu; Hong Zhang; Zhiyong Xiong; Wei Qian (Theoretical and Applied Genetics, 2026)

Lifetime burden of congenital heart disease from 1990 to 2021: a systematic analysis from the Global Burden of Disease Study 2021 - Meng-Yi Liu; Yue Cui; Lu-Hong Qiu; Jia-Xing Zhang; Su-Xin Zhang; Jie-Ling Ma; Hong Pan; Jie-Xin Zhang; Wei-Guo Ma; Ji-Mei Chen; Zhi-Cheng Jing (Science China Life Sciences, 2026)

Correction: MdSOS2L1 phosphorylates MdVHA-B1 to modulate malate accumulation in response to salinity in apple - Da-Gang Hu; Cui-Hui Sun; Mei-Hong Sun; Yu-Jin Hao (Plant Cell Reports, 2026)

LncRNA MNX1-AS1 drives the progression of non-small cell lung cancer and serves as a ceRNA to target COMMD8 by sponging miR-218-5p - Gao-Feng Liu; Li Zhou; Yu-Bo Zhao; Jia-Hong Tang; Qing-Yuan Li; Xiao-Yong Ding; Xiao-Zhen Zhang; Su-Juan Cui; Yong Zhang; Zhen-Wei Sun (Journal of Molecular Histology, 2026)
The role and mechanistic action of MNX1-AS1 in non-small cell lung cancer (NSCLC) remain unclear. This study aimed to investigate the function of MNX1-AS1 in the progression of NSCLC. A total of 40 paired tumor and adjacent lung tissue samples from patients with NSCLC were collected to investigate the expression of MNX1-AS1. H1299 and HCC827 cells were transfected with sh-MNX1-AS1, shRNA-NC, miR-218-5p mimic, mimic-NC, pcDNA3.1-COMMD8, or empty vector (pcDNA3.1). The expression of MNX1-AS1, miR-218-5p, and COMMD8 was detected using quantitative real-time PCR (qRT-PCR). Cell proliferation was evaluated using CCK-8 assays, while cell migration and invasion were evaluated using Transwell assays. Dual-luciferase reporter and RNA pull-down assays were performed to validate the targeting interactions between MNX1-AS1 and miR-218-5p, as well as between COMMD8 and miR-218-5p. In vivo, a nude mouse model was established: tumor volume and weight were measured after four weeks. Gene expression in tumor tissue was quantified using qRT-PCR, and Ki-67 expression was evaluated using immunohistochemistry. MNX1-AS1 expression was significantly upregulated in NSCLC tissues ( P < 0.05) and was correlated with poor prognosis in NSCLC patients. MNX1-AS1 knockdown markedly suppressed the viability, migration, and invasion of H1299 and HCC827 cells ( P < 0.05). Mechanistically, MNX1-AS1 acted as a molecular sponge for miR-218-5p, thereby relieving miR-218-5p-mediated repression of its direct target COMMD8 ( P < 0.05). Functional rescue experiments revealed that miR-218-5p silencing or COMMD8 overexpression partially reversed the inhibitory effects of MNX1-AS1 knockdown on the cell viability, migration, and invasion of H1299 and HCC827 cells. In vivo, sh-MNX1-AS1 significantly reduced tumor volume and weight ( P < 0.05). Moreover, the expression of MNX1-AS1, COMMD8, and Ki-67 were downregulated, while the expression of miR-218-5p was upregulated in sh-MNX1-AS1 tumor tissues ( P < 0.05). MNX1-AS1 promotes the progression of NSCLC by modulating the miR-218-5p/COMMD8 axis.

Decalin derivatives from an endophytic fungus Trichoderma harzianum GLQ03 and their anti-inflammatory activities - Pei-Shan Li; Qi-Yu Chen; Jian-Ying He; Xin-Huan Qiu; Feng Wang; Qi Luo; Hong-Hua Cui (Natural Product Research, 2026)

Editorial Expression of Concern: Knockdown of NOB1 expression inhibits the malignant transformation of human prostate cancer cells - Xiangmin Zhang; Dongxu Zhang; Fajun Qu; Yi Hong; Jianwei Cao; Xiuwu Pan; Lin Li; Yi Huang; Hai Huang; Lei Yin; Lu Chen; Jizhong Ren; et al. (Molecular and Cellular Biochemistry, 2026)

Structurally constrained hybrid modeling for cross-year prediction and mechanistic interpretation of marine biofouling evolution - Zhiqiang Cui; Haonan Huang; Yuanbei Li; Qiang Xu; Yuwei Hong; Mengting Jia (Ocean Engineering, 2026)

Low-temperature semi-solid-state H2 battery with high energy density - Xiuquan Chen; Yuhua Zhao; Simin Hong; Xiaodong Rang; Hong Dong; Jie Zhang; Shangjun Lu; Xiang Cui; Yajing Liu (Chemical Engineering Journal, 2026)

Synergistic Mo2C/MoO2 hybridization in sucrose-derived hard carbon spheres for sodium-ion batteries - Hong Cui; Liang Liu; Jiacheng Shen; Ge Lin; Yiting Dai; Yuanzhe Wang; Yue Tang; Jiantie Xu (Chemical Engineering Journal, 2026)

Automated approach to identifying wildfire plumes using S-band polarimetric radar observations - Hong Wang; Hua Deng; Haojia Li; Binqi Zhao; Cui Ye (Atmospheric Research, 2026)

Correction to: FOXK2/SH2D3A axis recruits EGFR to drive papillary thyroid cancer progression and confers sensitivity to EGFR inhibition - Qin Cui; Xulin Hong; Lin Gan; Bimin Shi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

FOXK2/SH2D3A axis recruits EGFR to drive papillary thyroid cancer progression and confers sensitivity to EGFR inhibition - Qin Cui; Xulin Hong; Lin Gan; Bimin Shi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Gastrodin Ameliorates Blood Pressure by Targeting the PPAR-γ/NF-κB/NLRP3 Signaling Axis in the Hypothalamic Paraventricular Nucleus - Yu Yang; Xiao-Jing Yu; Li-Yan Fu; Jie Qi; Kai-Li Liu; Xiu-Yue Jia; Wei Cui; Qing Su; Ting Huang; Yan-Feng Liang; Hua Tian; Huan Liu; et al. (Cardiovascular Toxicology, 2026)

Uneven geographies, contested practices: The politics of knowledge production in Chinese urban studies - Rong Yang; Chen Cui; Zhenjie Yuan; Hong Zhu (Applied Geography, 2026)

Bronze mirrors from Xi’an reveal central policy changes and regional trade details in the Han dynasties - Yihan Huang; Xue Ling; Xiuyuan Hong; Luxi Peng; Jian Cui (Archaeological and Anthropological Sciences, 2026)

Classification, heterogeneity, and evolution of snow drought in Xinjiang under climate warming - Hong Zhu; Peng Cui; Yan Wang; Jiansheng Hao; Guoqing Chen; Changgui Lin; Lanhai Li (Science China Earth Sciences, 2026)

A new fatty acid derivative derived from the deep-sea fungus Aspergillus sp. SCSIO41324 - Yu-Shi Chen; Ying-Ying Song; Sheng-Yi Deng; Xin-Kai Xiao; Xiao-Yan Pang; Wei-Jia Zhang; Yong-Hong Liu; Hong-Hua Cui; Jun-Feng Wang (Natural Product Research, 2026)

Vehicle-induced vibration and damage characteristics of ballastless track in subgrade settlement zone at 400 km/h - Weitao Cui; Hong Xiao; Yanglong Zhong; Chaozhi Ma; Liang Gao; He Chen; Shuxin Zhao (Transportation Geotechnics, 2026)

Particle Swarm Optimization with complementary velocity learning scheme and multiple performance mechanisms: Applications in power electronics - Libin Hong; Chengbo Dai; Tianxiang Cui; Zheng Lu; Ning Xue (Swarm and Evolutionary Computation, 2026)

Serine metabolism hijacks radiotherapy-driven antitumor immunity via suppressing STING-dependent DNA sensing - Xiaochuan Hong; Yuanqin Yang; Lingling Wu; Shuting Xu; Chao Yang; Tong Cui; Qishan Wang; Zhihao Wu; Xueni Yu; Qi Chen; Hanyu Hong; Qianjiang Chen; et al. (Science Bulletin, 2026)

Effect of hidden welding defects and residual stress on fatigue behavior of welded joints in orthotropic steel decks - Qinyong Wang; Jian Cui; Siwei Hong; Naiwei Lu (Ocean Engineering, 2026)

Earliest centripetal flaking system in eastern Eurasia reveals human behavioral complexity in late Middle Pleistocene China - Yu-chao Zhao; Zhan-yang Li; Hai-wei Zhang; Xin-ya Shao; Hao-hong Cai; Ying Cui; Ya-Nan Li; Hai Cheng; Zhe Hou; Christopher J. Bae; Brian A. Stewart (Journal of Human Evolution, 2026)

A Ca-MOF@COF composite and its in situ grown gel membrane for highly efficient capture of Cd2+ - Xue-Mei Liu; Chuang-Chuang Zhang; Kun Yang; Wei-Liang Jin; Guan-Lian Mo; Rui Liu; Hong-Xin Jiang; Hao-Jie Cui; De-Ming Kong (Journal of Cleaner Production, 2026)

Metabolic engineering of Yarrowia lipolytica for liquiritin production - Cun-Cui Kong; Xiao-Jing Wang; Hong-Xia Zhang; Song Qin; Cheng-Gang Ren (Chemical Engineering Journal, 2026)

New mesoporous UiO-66-OH framework with in-situ grown CsPbBr3 perovskite nanocrystals as a multifunctional sensor for the discrimination and instrument-free detection of three natural food additives - Hou-Qun Yuan; Qian-Wen Yang; Ling-Yi Guo; Yao-Hong Wang; Guan-Qun Li; Qiong-Yue Cui; Zhen-Chong Dou; Zhi-Qiang Cai; Yi-Fan Xia; Guang-Ming Bao (Chemical Engineering Journal, 2026)

Design of millimeter-sized porous carbon spheres guided by hydrodynamic principles - Xiao-Dong Shi; Cheng-Tong Wang; Wen-Cui Li; Hong-Lei Wang; An-Hui Lu (Chemical Engineering Journal, 2026)

Chemical structure and P-selectin inhibition of two linear and highly regular homofucans from the brown alga Fucus vesiculosus - Linxia Chen; Dilihumaer Ruzemaimaiti; Lige Cui; Guangyu Zhu; Jiali Zhang; Huifang Sun; Yan Ma; Ying Hong; Na Gao; Lina Nong; Wenxin Ma; Qinjie Qin; et al. (Carbohydrate Polymers, 2026)

Integrating elite selection and micropropagation: a production line for early-stage domestication of Vaccinium bracteatum - Chuizheng Xia; Muhammad Junaid Rao; Ying Wu; Yuanyuan Li; Xuefeng Wang; Weicong Hong; Mengxue Wang; Yihong Jin; Jiani Zhu; Xuan Yu; Haidi Yuan; Jiao Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Regulatory patterns of antibody-dependent cellular phagocytosis–related genes in triple-negative breast cancer: An integrated multi-omics and single-cell analysis - Guihua Hong; Zhanyue Cui; Xiaowen Xu; Shiwei Lin; Changqing Yang; Ran Ding; Ludan Liang; Ying Chen; Ziyue Tian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

DRCD-TL: a novel co-seismic landslide mapping approach by deep representation-driven unsupervised change detection based on transfer learning - Hong Fang; Chenghao Wu; Qitong Cao; Bin Cui; Chenghan Yang (Natural Hazards, 2026)

A novel pretreatment strategy for non-aggressive chromium speciation based on a sole bifunctional magnetic ion-imprinted nanocomposite with mild freezing grinding - Yi-Fan Pan; Sen Zhang; Jing Yang; Xiao-Bing Cui; Hong-Zhen Lian (Analytica Chimica Acta, 2026)

PSD3 links autophagic flux to MHC-I–associated immune modulation in esophageal squamous cell carcinoma - Shujuan Luo; Aididar Nurbahati; Bangwu Cai; Hong Cui; Tianyuan Peng; Wei Wang; Huifang Li; Jiao Chen; Qing Liu; Xiaomei Lu; Shutao Zheng (Apoptosis, 2026)

Talarombrevisone A, an β -aminopropionate with two polyketide units, isolated from an endophytic fungus Talaromyces brevis - Yun-He Tuo; Zhong-Duo Yang; Jian-Guo Chen; Cui-Juan Xu; Lin-bo Liu; Tian-Kun Zhao; Yue Li; Li-Bin Xia; Shuai Yu; Ai-Hong Zhao; Shuo Li (Natural Product Research, 2026)

Altered insula resting-state functional connectivity correlates with impaired cognitive control in children with emotional undereating - Xiaoyi Li; Shaorui Wang; Mingyue Xiao; Yicen Cui; Ximei Chen; Yong Liu; Hong Chen (Appetite, 2026)

Development of a self-assembling aggregation-induced emission nanoprobe for targeted therapy and real-time imaging in non-small cell lung cancer - Zhen Ren; Shuai Li; Tong Cui; Tianjie Zhu; Dapeng Ding; Jingyuan Zhao; Hong Yuan (Journal of Photochemistry and Photobiology B: Biology, 2026)

Plastisphere denitrification dynamics shaped by soil acidification: Microbial Community and activity responses - Yu-Chen Li; Sha Zhao; Hu Li; Pei-Yuan Xu; Hong-Xia Cui; Jian-Qiang Su (Journal of Hazardous Materials, 2026)

Regulating chemistry and wettability of chitosan-based colloidal particles for dextran-in-PEG highly dispersed phase emulsions - Shukai Cheng; Liuyan Zhu; Wanying Cui; Ran Hong; Maodong Xu; Zhenxia Song; Jian Zhao; Cuige Zhang; Chunmiao Xia; Rongli Zhang (Food Hydrocolloids, 2026)

Crop rotation and nitrogen management achieve a trade-off among crop productivity, net income and soil CO2 emission in the Hexi Oasis irrigation area - Lili Yang; Xiaoyuan Bao; Hong Fan; Congcong Guo; Fuyang Cui; Jie Zhou; Chengxin Bai; Qiang Chai; Cai Zhao (Field Crops Research, 2026)

Bridging the gap between empirical and rational design: machine learning framework for lithium ion-sieve performance prediction - Zhenjie Cui; Sheng Pang; Xinying Ren; Jianwei Guo; Hong Yue; Dong Wang; Zhi Wang (Desalination, 2026)

Starch as a designable platform for oral drug delivery: From structural modulation to application in inflammatory bowel disease - Mengyuan Qin; Feng Jiang; Yan Hong; Lingjin Li; Yongmin Cui; Canran Jin; Zhengbiao Gu; Li Cheng; Zhaofeng Li; Caiming Li; Xiaofeng Ban (Carbohydrate Polymers, 2026)

A novel compatible fluid connector for liquid cooling system in data center - Hansong Xiao; Hongjie Wu; Hailiang Luo; Zeqi Tian; Hong Liu; Yin Li; Jiaqi Hou; Li Chen; Haidong Cui; Rongzhen Wan (Building and Environment, 2026)

PfAgo-mediated a rapid and visual detection assay for porcine circovirus type 3 based on recombinase-aided amplification - Xi-Meng Chen; Jia-Qi Zhang; Hong-Bo Cui; Lan-Lan Zheng; Xue-Yan Ding; Hong-Ying Chen; Shi-Jie Ma (Analytica Chimica Acta, 2026)

Niaodukang for the treatment of chronic kidney disease: Regulation of the TRAF3/NF-κB2 signaling pathway and its improvement of the intestinal barrier - Juan Xu; Lei Wang; Hong Wang; Jie Pang; Linna Liu; Ting Zhang; Ling Yuan; Xiaoxue Cui; Qian Jiang; Yanlin Li (Tissue and Cell, 2026)

Hydrodynamic analysis of ditching for aircraft with bank angle:A multi-resolution SPH-based preliminary investigation - Xin Chen; Hong-lei Lyu; Jie Cui; Yuan-yuan Xia; Wen-fu Geng (Ocean Engineering, 2026)

Singlet oxygen-dominated peroxymonosulfate activation by wastewater-borne copper phthalocyanine for simultaneous dye degradation and pigment recovery - Yan Wang; Xin Yang; Chen-Xuan Li; Wenhui Xu; Hong Mei; Feng Zhang; Zhuoya Gao; Yelei Liu; Kai Zhou; Houyun Yang; Kangping Cui (Journal of Environmental Management, 2026)

Revisit the improvement of coagulation pretreatment on ozonation performance: The critical roles of HO• and O3 for effluent organic matter transformation and micropollutant degradation - Rui Hu; Hao-Tong Zheng; Boxi Tang; Jialing Tu; Yu-Hong Cui; Xuedong Zhai; Gang Wen; Zheng-Qian Liu (Journal of Cleaner Production, 2026)

Flow-driven piezo-photocatalytic synergy in Bi24O31Br10/β-PVDF membranes: Interfacial electron transfer-mediated enhancement of tetracycline degradation - Yixuan Hong; Yanhua Cui; Zengkai Wang; Jian Ye; Chunyan Li; Weilong Shi; Chao Yan (Journal of Environmental Chemical Engineering, 2026)

Insight into the oxygen-dependent biotransformation pathways of mercury by a facultative bacterium Raoultella terrigena TGRB3 - Hui Li; Qunyao Cui; Yuping Xiang; PengYu Feng; Lanqing Wang; Jiwu Wang; Yongmin Wang; Dingyong Wang; Hong Shen (Journal of Environmental Sciences, 2026)

The characteristics of metabolites accumulation and their connections with endophytic fungi in roots and stems of Ephedra sinica with different cultivation ages - Shan-Shan Wang; Xin Ji; Jun-Hong Wang; Yuan-Peng Hao; Jin-Long Cui (Fungal Biology, 2026)

The performance and mechanism of sodium carboxymethyl cellulose in promoting the anaerobic ammonium oxidation coupled with Fe (III) reduction - Hong-Yan Meng; Shen Cui; Lei Yang; Yu-Chao Wang; Hao-Qi Lu; Dun Guo; Pan Liang; Jun Lan; Yong-Xiang Ren (Bioresource Technology, 2026)

In situ cultivation and chromogenic screening: a dual approach for rapid discovery of PDE1 inhibitors from pinus-tree associated microbes - Cui-Juan Xu; Shuo Li; Zhong-Duo Yang; Lin-Bo Liu; Yun-He Tuo; Yong-Jiao Niu; Lei-Lei Chen; Jian-Guo Chen; Tian-Kun Zhao; Ai-Hong Zhao (World Journal of Microbiology and Biotechnology, 2026)

Therapeutic effects of Gardenia jasminoides Ellis on salpingitis in laying hens: mechanisms of inflammatory regulation and egg quality improvement - Ruo-Yi Zhang; Hua-Lin Peng; Wei Zhang; Rong-Qiang Li; Hong-Jie Cui; Jian Li (Veterinary Research Communications, 2026)

Metagenomic sequencing reveals high reproducibility of human donor microbiota transplanted into germ-free mice via lower gut route - Yapeng Yang; Xiang Tan; Zeyue Zhang; Lifeng Liang; Zhifeng Wu; Jinhui He; Yuqing Wang; Miaomiao Dong; Jixia Zheng; Hang Zhang; Shuaifei Feng; Wei Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Halovenus anhuiensis sp. nov. and Natronomonas salinimetallica sp. nov., two extremely halophilic archaeon isolated from a salt mine - Ya-Ling Mao; Aodi Zhang; Tao Hong; Yue Ding; Jingfang Liu; Jing Hou; Heng-Lin Cui; Shaoxing Chen (Extremophiles, 2026)

Composition characterization of the culturable endophytic fungi in roots and their antagonistic activity against root rot of Astragalus mongholicus - Zhong-Ya Zhou; Xi Liu; Fen Gao; Meng-Liang Wang; Jun-Hong Wang; Jin-Long Cui (Archives of Microbiology, 2026)

Numerical investigation on hydrodynamic characteristics of floating breakwater with wings using a coupled SPH method - Xin Chen; Ming-yuan Li; Peng-cheng Shi; Hong-lei Lyu; Jie Cui (Marine Georesources & Geotechnology, 2026)

CER-DETR: Channel-aware and edge-aligned detection of floating debris under complex weather - Hong Shao; Shuo Wang; Wencheng Cui (Marine Pollution Bulletin, 2026)

Damage mechanism of double-block ballastless track on subgrade under coupled complex loads - Xuhao Cui; Yapeng Liu; Bowen Du; Hong Xiao; Lei Xu; Zhihai Zhang; Yang Wang (Transportation Geotechnics, 2026)

Haladaptatus marinus sp. nov., Haladaptatus rarus sp. nov., Haladaptatus ordinarius sp. nov., and Halomicrococcus pelagicus sp. nov., halophilic archaea from diverse coastal tidal flats - Xin-Ru Zhang; Jing Hou; Zhen Rong; Yue-Hong Wu; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Corrigendum to “Both target-site and non-target-site resistance mechanisms confer mesosulfuron-methyl resistance in Silene conoidea L.” [Pesticide Biochemistry and Physiology 218(2026) 106905] - Xinhui Xue; Hailan Cui; Shen'ao Hu; Hong Ma; Shouhui Wei; Hongjuan Huang; Xiangju Li; Zhaofeng Huang (Pesticide Biochemistry and Physiology, 2026)

Both target-site and non-target-site resistance mechanisms confer mesosulfuron-methyl resistance in Silene conoidea L. - Xinhui Xue; Hailan Cui; Shen'ao Hu; Hong Ma; Shouhui Wei; Hongjuan Huang; Xiangju Li; Zhaofeng Huang (Pesticide Biochemistry and Physiology, 2026)

Quorum sensing-driven biofilm cathode of Shewanella oneidensis for enhanced uranium adsorption: Elucidating the role of exogenous AHLs and validation in actual uranium-contaminated groundwater - Jing Sun; Hong Shu; Xiaoyan Wu; Tingting Liu; Guangyue Li; Zhao Cui; Ting Li; Xiaowei Zhou; Zhongran Dai; Qian Li (Journal of Hazardous Materials, 2026)

Enzymatic synthesis of N-propionyl phenylalanine: enhancement of umami and salty taste and decoding of its taste mechanism - Jieshee Hong; Hongli Xiao; Chun Cui; Lei Cai (Food Chemistry, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Enhanced stability and antioxidant activity of pickering emulsions stabilized by chayote tuber starch-tea polyphenol composites - Xiaoxue Wang; Jia Huang; Xingyuan Zhu; Qing Guo; Qiang Cui; Jie Yu; Xiaoyan Hou; Hong Liu; Guanghui Shen; Zhongqun He; Zhiqing Zhang (Food Hydrocolloids, 2026)

Influence of protease type and concentration on protein digestibility, physicochemical and textural properties of extruded high-moisture meat analogues - Grace Cui Fang Ng; Caleb Ong; Alicia Hui Ping Theng; Dayna Shu Min Ong; Chaoyu Dong; Hui Yu Sim; Xin Yi Hua; Felicia Siew Kay Ng; Jie Hong Chiang (Food Hydrocolloids, 2026)

Machine learning unlocks multi-metal synergy in Prussian blue cathodes toward ultralow-cost sodium-ion grid storage - Hong Qian; Zhong Tang; Yuhao Liu; Xiaofei Hou; Xiangyang Liu; Binxia Yuan; Haoyang Cui (Chemical Engineering Journal, 2026)

Silicon isotope-based assessments of biogenic and dissolved silica content determination in marine sediments - Die Li; Quanchao Cui; Haiyang Liu; Tzu-Hao Huang; Wei-li Hong; Bangqi Hu; Jing Huang; Min Luo; Weidong Sun; Xiaole Sun (Chemical Geology, 2026)

TMEM158-mediated TGF-β signaling pathway modulates the sensitivity of TP53-deficient osteosarcoma to USP14 inhibitors - Zi-Yu Chen; Miersalijiang Yasen; Song-Yao Jiang; Zi-Yi Ye; Qin-Xin Yang; Cui-Ni Lu; Yi Shi; Xin-Yun Liu; Ting-Ting Du; Xiao-Mei Tang; Da Fu; Yu-Shui Ma; et al. (Molecular and Cellular Biochemistry, 2026)

Reverse temporal spectral signal extraction and deep spectral signal decoupling fusion for detection of SCLB infection process - Guohui Liu; Jinyang Chao; Changle Guo; Lulu An; Yang Liu; Hong Sun; Chunqi Zhang; Mingjia Liu; Zheng Cui; Man Zhang; Minzan Li; Wei Yang (Computers and Electronics in Agriculture, 2026)

YOLOv11-SDiseasedFishNet:Recognition of body surface symptoms of diseased fish based on automatic combination augmentation and multi-scale feature fusion - Zijian Wu; Jian Li; Rui Shi; Hongjing Dai; Zhibo Cui; Yue Wang; Hong Yu (Aquaculture, 2026)

The influence of tunnel floor heave induced by high water pressure on the mechanical response of ballastless track - Xuhao Cui; Yapeng Liu; Bowen Du; Hong Xiao; Hongbin Xu; Yang Wang; Yihao Chi (Transportation Geotechnics, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Evidence of heterogeneity in the mantle source of Quaternary Naozhou Island basalts from REEs and Sr-Nd-Pb isotopes - Cui Xiao-Ge; Li Zhi-Hua; Xie Shi-Xiong; Yang Wen-Jian; Wang Ming-Qiu; Cheng Liu-San; Gao Cai-Xia; Jiang Hong-Liang (Lithos, 2026)

Effects of different iron compounds on the acclimation of Feammox sludge: Nitrogen-iron transformation, sludge physicochemical properties, and microbial communities - Pan Liang; Lei Yang; Yu-Chao Wang; Hao-Qi Lu; Dun Guo; Hong-Yan Meng; Shen Cui; Jun Lan; Yong-Xiang Ren (Environmental Research, 2026)

Synergistic antibiotic degradation by polydopamine/BiOBr-modified photocathode in self-powered photo-bio-electrochemical system - Mei-Qi Ren; Hong-Li Lu; Zhuo-Chao Liu; Tao Hou; Shuai Wang; Dan Cui; Yong-Zhen Peng (Bioresource Technology, 2026)

PET Molecular Imaging of the Endocannabinoid System in Psychiatric Disorders - Chunyi Cui; Xiaofeng Dou; Peili Cen; Chentao Jin; Jing Wang; Jiaqi Niu; Chenxi Xue; Mei Tian; Hong Zhang; Yan Zhong (Neuroscience Bulletin, 2026)

Development of a high-throughput LLE-UPLC-QqQ-MS/MS method and comprehensive profiling of urinary steroid hormones in Chinese elderly adults - Xiao Ma; Huimin Ren; Li Zhao; Xiaojie Guo; Jiran Zhang; Juan Liu; Xiaona Wang; Mengyao Wang; Yifu Lu; Shilu Tong; Hongyang Cui; Hong Chang; et al. (Analytica Chimica Acta, 2026)

A Hybrid CUBE-IForest Approach for Outlier Detection in Multibeam Bathymetry - Rui Han; Yukai Hong; Xibin Han; Yi Zhang; Shunming Hu; Yuan Huan; Xiaodong Cui; Xiaohu Li (Journal of Marine Science and Engineering, 2026)
With the rapid development and widespread application of multibeam echo-sounding systems, large-scale and high-resolution seafloor topography can be efficiently acquired, enabling precise mapping of seabed terrain. However, due to complex oceanographic conditions, instrumental noise, and acoustic interferences, the acquired multibeam data often contain outliers that deviate from the true seafloor surface. These outliers can distort the representation of seafloor topography, adversely affecting subsequent geological analysis and engineering applications. To address this issue, a hybrid outlier detection method combining CUBE filtering with the Isolation Forest (IForest) algorithm, termed CUBE-IForest, is proposed. The method first employs CUBE filtering to remove gross outliers based on local uncertainty estimation, followed by the application of IForest to identify subtle anomalies in the refined data, achieving hierarchical detection of outliers. Experimental results based on in situ multibeam bathymetric data from the northeastern Pacific demonstrate that compared with traditional filtering methods the CUBE-IForest approach significantly improves detection accuracy and reduces both false positive and false negative rates by approximately 30%, confirming its efficiency and reliability in seafloor mapping and analysis.

Longitudinal biomarker trajectories and their prognostic utility for 21-day mortality in burn patients with sepsis: a retrospective cohort study - Jiaqi Lou; Hong Kong; Jiliang Li; Ziyi Xiang; Xiaoyu Zhu; Shengyong Cui; Neng Huang; Sida Xu; Guoying Jin; Xin Le; Youfen Fan (Inflammation Research, 2026)

Triterpenoid and trichothecenes from a rhizospheric soil-derived Paramyrothecium sp. KMU22107 - Hong-Tao Li; Xing-Yi Guo; Ya-Ting Shao; Wen-Yu Huang; Cui-Ping Miao; Wei Li (Natural Product Research, 2026)

A variant of united multi-operator evolutionary algorithms with application to livestock feed ration optimization - Libin Hong; Dongxu Zhang; Tianxiang Cui (Swarm and Evolutionary Computation, 2026)

Temperature effect of CRTS Ⅲ slab track in natural environments and its influence on vehicle-track dynamic interaction at 400 km/h - Weitao Cui; Liang Gao; Hong Xiao; Yanglong Zhong; Chaozhi Ma; Lei Zhao; Shuxin Zhao (Soil Dynamics and Earthquake Engineering, 2026)

Exposing Drosophila to wheat-derived microbes enhances its immunity and survival under simulated microgravity - Letian Chen; Shijing Wang; Chuanmeng Cai; Jingjing Cui; Hong Liu; Yuming Fu (Life Sciences in Space Research, 2026)

Revealing the causes of inequality in rainstorm flood disaster resilience between town and rural areas in southwestern China: Based on natural and social system dimensions - Zhangjie Li; Lihong Yang; Ling Zhu; Jing Tan; Zhiqiang Xie; Yudong Wang; Hong Zhang; Jinhang Xie; Songyun Cui; Shihan Bai; Zhiqun Hou (Journal of Rural Studies, 2026)

Corrigendum to ‘Metabolic flexibility of rhizobacteria drives soil nutrient cycling and enhances rare earth elements hyperaccumulation in ferns colonizing degraded mine ecosystems’ [J. Environ. Manag. 395 (2025) 128013] - Yong-He Han; Xi-Wen Cui; Hai-Bin Han; Yang-Long Jiang; Li-Chao Tong; Jian-Fei Chen; Hong Zhang; Yong Zhang; Zhibiao Chen (Journal of Environmental Management, 2026)

Organ-specific toxicity of Maillard-derived 2-furfural and 5-hydroxymethylfurfural: Quantitative evidence from zebrafish - Xiangxin Wang; Qingxue Chen; Shubo Luo; Dongying Cui; Sinan Mu; Jufang Li; Qinggang Xie; Bailiang Li; Hong You (Food Research International, 2026)

Pre-harvest application of co-assembled Berberine-integrated herbal hydrogel for enhancing strawberry quality and shelf life - Mingping La; Jiamei Le; Hong Gu; Guangyu Zhao; Xiaohong Zhu; Feng Chen; Cui Li (Food Chemistry, 2026)

Moisture dynamics and flavor evolution in green Sichuan pepper during processing: An LF-NMR/MRI approach - Jiao Wang; Xingyuan Zhu; Junhang Ye; Xiang Zhu; Xiaoyan Hou; Guanghui Shen; Qiang Cui; Jie Yu; Hong Liu; Chenggang Wen; Anjun Chen; Zhiqing Zhang (Food Chemistry, 2026)

Lactiplantibacillus plantarum CCFM1296 postbiotics ameliorate skin aging in mice associated with enhanced endogenous hyaluronic acid synthesis - Xin Tang; Haobo Cui; Qing Hong; Bingyong Mao; Qiuxiang Zhang; Jianxin Zhao; Wei Chen; Shumao Cui; Zhenmin Liu (Food Bioscience, 2026)

Dynamic thermal sensation model during speaking behaviours of occupants using machine learning - Xuange Zhang; Minhyun Lee; Junjiang Luo; Mohammad Nyme Uddin; Xue Cui; Hakpyeong Kim; Taehoon Hong (Energy and Buildings, 2026)

Mechanisms of Fish Intestinal Damage Under Environmental Stress: Insights From Carbonate Saline–Alkali Water Perspective - Jia Rui Cui; Qi Fang Lai; Yue‐Hong Li (Reviews in Aquaculture, 2026)
The intestinal tract is an important functional organ in fish, as it plays a key role in digestion and absorption, mucosal immunity, endocrine function, and metabolism. Therefore, damage to this organ greatly impacts fish health. This injury is usually associated with a poor aquaculture water environment, stressful conditions, and pathogen presence. In this review, in light of gut injury being a common pathology in aquaculture, we have summarized the current understanding of the intestinal damage of fish caused by carbonate water stress, and the mechanism of intestinal tissue damage caused by carbonate saline water stress, including the intestinal barrier function of fish and the role of various cells and molecules involved in the occurrence and development of diseases. Comparative data on carbonate stress responses across different teleost lineages (such as the Cyprinidae and Perciformes) have been integrated. The review also covers current methods for treating intestinal damage in fish, including dietary interventions, medications, and probiotics. Our findings highlight the need for more in‐depth research in this area to better understand the mechanisms underlying the occurrence of intestinal tissue damage in fish in carbonate‐based saline waters and to develop effective preventive and therapeutic strategies. Improved development of saline–alkaline waters and research into new treatments are essential for the sustainability of aquaculture and the health and productivity of farmed fish.

Rare earth element hyperaccumulation in vascular plants: Occurrence, mechanisms, and applications - Ruo-Rong Liu; Cui-Ling Huang; Hong-Xiang Zheng; Chong Liu; Rui-Qi Zhang; Yue Cao; Antony van der Ent; Can-Die Xie; Wen-Shen Liu; Jean Louis Morel; Catherine Sirguey; Damien Blaudez; et al. (Critical Reviews in Environmental Science and Technology, 2025)

Harnessing lactobacillus : a probiotic revolution in combating metabolic dysfunction-associated steatotic liver disease - Minwen Gu; Qing Hong; Jie Cui; Wenhui Li; Jian Zhang; Ye Sun; Jinchi Jiang; Yonghong Hu (Critical Reviews in Food Science and Nutrition, 2025)

Using UAV multispectral image data to monitor the nitrogen status of head cabbage shoots in the Liupan Mountain area of China - Shuai Wang; Long-Guo Wu; Hua Ma; Kelsang Choron; Fu-Shun Zheng; Zhong-Ting Song; Cui Yin; Hong-Yan Zhu; Peng-Yuan Lv; Yun-e Cao (International Journal of Remote Sensing, 2025)

Susceptibility of five thrips pests to spinetoram and the frequency of G275E target-site mutation in a major vegetable production region of China - Hong-Ping Tian; Hong-Xia Tian; Jin-Cui Chen; Fu-Jun Li; Jing-Jing Kang; Hui-Juan Li; Jin-Peng Gao; Guo-Cai Lu; Ya-Jun Gong; Shu-Jun Wei (Crop Protection, 2025)

Pasteurized Akkermansia muciniphila ameliorates insulin resistance by reducing placental inflammation in GDM mouse model - Yi Wang; Yuting Zhu; Yan Cui; Jiali Fang; Hong Zhong; Yujie Shi; Lan Liu; Xianwei Cui (Reproductive Biology, 2025)

Environmental impacts of rare earth elements mining and strategies for sustainable management: A comprehensive review - Yong-He Han; Xi-Wen Cui; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2025)

Metabolic flexibility of rhizobacteria drives soil nutrient cycling and enhances rare earth elements hyperaccumulation in ferns colonizing degraded mine ecosystems - Yong-He Han; Xi-Wen Cui; Hai-Bin Han; Yang-Long Jiang; Li-Chao Tong; Jian-Fei Chen; Hong Zhang; Yong Zhang; Zhibiao Chen (Journal of Environmental Management, 2025)

Synergistic effect of element doping and support introduction on the ortho-para hydrogen conversion activities of Fe2O3 - Xin Yu; Jiawei Wang; Jin Shen; Yulin Cui; Jianjian Xia; Hong Xu; Shaowei Zhu; Cunman Zhang; Mingzhe Xue (Journal of Environmental Chemical Engineering, 2025)

A study of the effect of ammonia on the oxidation reactivity and structure of char from coal/ammonia co-pyrolysis - Dikun Hong; Yajing Guo; Changlong Qu; Yong Zhang; Liming Cui; Wenzhen Zhang; Wei Chu; Xingxing Cheng; Chunbo Wang (Fuel, 2025)

Limosilactobacillus fermentum A6-3 from Chinese fermented glutinous rice achieves Helicobacter pylori clearance without destroying the gut microbiota - Taotao Liao; Fali Fang; Haoyu Wang; Qiwei Li; Lixia Hong; Lixin Yang; Guzhen Cui; Zhenghong Chen; Daoyan Wu (Food Bioscience, 2025)

Performance and mechanistic insights into denitrification enhancement by PPy/rGO-modified carbon felt biocathodes - Shuai Wang; Hong-Li Lu; Tong-Yang Feng; Zhuo-Chao Liu; Mei-Qi Ren; Dan Cui; Yong-Zhen Peng (Chemical Engineering Journal, 2025)

A pH-responsive and nitric oxide-producing nanocarrier for targeted therapy of melanoma - Shuai Cui; Qing Yu; Ziyuan Su; Yiting Han; Sujuan Wang; Xiangyu Zou; Lin An; Nannan Yin; Hao Hong; Dongzhi Yang (Chemical Engineering Journal, 2025)

Influence of cooling-induced salt crystallization on the shear strength of sulfate saline soils - Yanjie Ji; Bing Bai; Xu Li; Hong-huan Cui (Cold Regions Science and Technology, 2025)

Enhanced Removal of Phorate in Polluted Soil by Co-Solvent-Augmented Alkaline Activation of Persulfate - Tingting Lv; Hong Wang; Ding Li; Ruihai Li; Chengliang Yang; Wei Zhao; Zhenyu Cui; Jianxin Li (Water, Air, & Soil Pollution, 2025)

Association of Serum Neurofilament Light and Glial Fibrillary Acidic Protein with Cerebral Small Vessel Disease in Nondemented Middle-to-Old Aged Population - Xiao-Hong Huang; Feng Gao; Jing Yuan; Ding-Ding Zhang; Mei-Jun Shu; Fei-Fei Zhai; Fei Han; Ming-Yu Tang; Ming-Li Li; Li-Xin Zhou; Jun Ni; Ming Yao; et al. (Translational Stroke Research, 2025)

Different Intensities of Exercise Affect the Prognosis of Ventricular Aneurysm in Mice by Regulating the Progression of Cardiac Fibrosis - Rui-Qiang Qi; Juan Song; Hong-Bin Ma; Mei-Ling Nie; Liu-Hang Su; Cui-Lian Dai; Fa-Guang Zhou; Sui-Ji Li (Cardiovascular Toxicology, 2025)

Modulation of greenhouse gas emissions and soil organic carbon in rice paddies through various crop rotation systems combined with water-saving irrigation: Insights into soil bacterial composition and functional alterations - Ligong Peng; Sicheng Deng; Wentao Yi; Yizhu Wu; Baoling Cui; Yingying Zhang; Xiangbin Yao; Xuechan Zhang; Hong Yang; Xiangru Tang (Agriculture, Ecosystems & Environment, 2025)

Chemical constituents and biological activities of the endophytic fungus Hypoxylon sp. from Cupressus funebris Endl - Yun-He Tuo; Zhong-Duo Yang; Bing Sun; Cui-Juan Xu; Jian-Guo Chen; Tian-Kun Zhao; Ai-Hong Zhao; Sahyun Kim (Natural Product Research, 2025)

Sex difference in neural substrates linking negative body image and disordered eating behaviors - Yicen Cui; Yazhi Pang; Shaorui Wang; Hong Chen (Brain Structure and Function, 2025)

Hetero-protein systems: an effective strategy to improve the functional properties of protein - Yue-Yue Liu; Rui Cui; Teng-Gen Hu; Bing Li; Hong Wu (Trends in Food Science & Technology, 2025)

On vibration of a fluid-submerged multi-segment combined shell: A hybrid modeling methodology - Hong Yin; Dechun Zhang; Peng Li; Junzhe Cui (Ocean Engineering, 2025)

PufH: A promising biocatalyst for the recycling and bioremediation of polyurethane foam waste - Yuting Jiang; Mingliang Zhang; Jie Zhou; Zhongli Cui; Qing Hong; Weiliang Dong; Xin Yan (Journal of Hazardous Materials, 2025)

Rapid formation of acetaldehyde and its influence on ozone formation in a petrochemical industrialized region - Can Cui; Yujiao Zhu; Xiaoyu Yan; Xin Zhang; Min Zhao; Jiangshan Mu; Xuelian Zhong; Jinghao Tang; Yanqiu Nie; Cong An; Wanghui Chu; Yue Sun; et al. (Journal of Environmental Sciences, 2025)

Ionic liquid functionalized magnetic microporous organic network for efficient extraction of phenoxyacetic acid herbicides from vegetables - Xu-Hui Li; Yan-Hong Li; Yuan-Yuan Cui; Cheng-Xiong Yang (Food Chemistry, 2025)

rGO/polypyrrole-modified bioelectrode reshapes microbial communities for enhanced energy-recovering denitrification in carbon-limited wastewater - Yue-Jia Yang; Hong-Li Lu; Naif Abdullah Al-Dhabi; Wang-Wang Tang; Shuai Wang; Dan Cui (Environmental Research, 2025)

Study on the residual dynamics of diazepam in freshwater fish of Zhejiang, China and its implications for human health - Jing Cui; Jing Wang; Shihuan Zhong; Min Hong; Chenze Lu; Jiehong Fang; Han Jiang (Environmental Pollution, 2025)

Fe-SMA prestressed strengthening of damaged transverse hinge joints in hollow slab bridges - Zhiqiang Dong; Cui Zou; Xinliang Sun; Xihua Zhan; Hong Zhu; Yijie Pan; Elyas Ghafoori (Engineering Structures, 2025)

Lateral impact behavior of reinforced concrete columns strengthened with Fe-SMA/FRP-HDPE tube and rubber concrete cladding - Tianhao Han; Zhiqiang Dong; Chushi Cui; Hong Zhu; Ou Zhao (Engineering Structures, 2025)

Subway track health monitoring based on carriage interior noise signals and contrastive predictive coding - Yang Wang; Hong Xiao; Xuhao Cui; Zhihai Zhang; Yihao Chi; Zhongxia Qian (Engineering Structures, 2025)

Catechol-induced assembly to enhance the performance of antimicrobial peptide fully - Xiao Wang; Yuanyuan He; Beibei Cui; Yuan Feng; Jingjing Lin; Xirui Long; Yanchao Wang; Zhen Li; Feng Luo; Jiehua Li; Hong Tan (Chemical Engineering Journal, 2025)

Stretchable high-capacitance supercapacitors enabled by Soft-Pore-Array engineered Ag@polyurethane current collectors - Xin Jiang; Meng Wang; Yifan Shang; Tianhe Xu; Jixiang Cui; Karen Forberich; Chaohong Zhang; Hong Meng (Chemical Engineering Journal, 2025)

A Facile-Synthesized Dual-Network Multi-Ionic Integrated Explosive with Enhanced Detonation Performance and Promoted Aluminum Reactivity - Yun-Fan Yan; Yu Shang; Ming-Yu Guo; Shao-Li Chen; Meng Cui; Zhi-Hong Yu; Wei-Xiong Zhang; Xiao-Ming Chen (Chemical Engineering Journal, 2025)

Gellan gum/chitosan-based bilayer scaffold for the targeted delivery of curcumin and green tea, designed to enhance breast cancer treatment paradigms - Xiaopeng Yu; Hong Yu; Chuanjia Yang; Cen Wu; Ying Cui; Ning Xu (Carbohydrate Polymers, 2025)

Model Construction and Research of Synergistic Effect Mechanism on Subglacial Bedrock Core Breaking - Rusheng Wang; Zhihao Cui; Guigang Tu; Xiaopeng Fan; Da Gong; Siqi Hong; Xinyu Lv (Rock Mechanics and Rock Engineering, 2025)

Cassiterite U–Pb ages from the Tin Islands, Indonesia, the southern end of the Southeast Asian tin province - Jie-Hua Yang; Rui-Zhong Hu; Mei-Fu Zhou; Bernd Lehmann; Jun-Hong Zhao; Jing-Hua Wu; Liang Liu; Wei Mao; Zheng-Teng Cui; Mega Fatimah Rosana (Mineralium Deposita, 2025)

YOLOv11-OPNet: dual-modality framework for fishing vessel detection in complex long-range maritime scenarios - Jian Li; Hong Yu; Rui Shi; Zhibo Cui; Hongjing Dai; Zijian Wu; Yue Wang (Aquaculture International, 2025)

Extreme Phenotypic Variation Confounds Acanthocephalan Systematics: A Case Study of Longicollum pagrosomi and Pomphorhynchus zhoushanensis (Acanthocephala: Echinorhynchida) - Cui‐Hong Zhao; Hui‐Xia Chen; Matthew Thomas Wayland; Rui‐Jia Yang; Xiao‐Hong Gu; Liang Li (Zoologica Scripta, 2025)
The phylum Acanthocephala is a ubiquitous group of zooparasites, with major socio‐economic importance. The true diversity of the Acanthocephala is obscured by the phenomena of cryptic speciation and a large degree of intraspecific variation. In this study we describe an example of extreme phenotypic variation in neck morphology. The pomphorhynchid acanthocephalans, Longicollum pagrosomi and Pomphorhynchus zhoushanensis were originally differentiated on the basis of differences in neck morphology; P. zhoushanensis possesses a neck bulb whereas this structure is absent in L. pagrosomi . However, ASAP and phylogenetic analyses of the ITS, 12S, cox 1 and cox 2 sequence data, together with comparative mitogenomics, revealed that the two taxa are in fact conspecific. Therefore, the presence or absence of a neck bulb represents extreme phenotypic variation, and this character is not reliable for distinguishing the genera Pomphorhynchus and Longicollum. In the absence of other characters to discriminate the two genera, Longicollum is relegated to a junior synonym of Pomphorhynchus . A new combination Pomphorhynchus pagrosomi (Yamaguti, 1935) comb. nov. is proposed for L. pagrosomi Yamaguti, 1935 and P. zhoushanensis Li, Chen, Amin & Yang, 2017 is relegated to a junior synonym of P. pagrosomi .

Spermidine-mediated enhancement of salt tolerance in cucumber and the role of H2O2 in regulating this enhancement - Ting-Ting Xu; Cui-Yun Dong; Cai-Hong Chai; Qiao Zhu; Cheng Ma; Zi-Qi Pei; Juan Wang; Sheng Zheng; Teng-Guo Zhang (Biologia, 2025)

Regulating community redox metabolism for systematic mitigation of antibiotic chemical and biological risks - Ke Shi; Wen-Bin Xu; Han-Lin Cui; Li-Ying Zhang; Jing-Yi He; Wei-Wei Ben; Cheng-Yuan Su; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2025)

Efficacy of a non-recombinant NADC34-like PRRSV-2 vaccine candidate against a recombinant NADC34-like PRRSV-2 isolate - Ming Qiu; Shuai Li; Meng Cui; Shuai Yang; Xiaoyang Zhu; Yifan Meng; Yanhan Lin; Hong Lin; Zhe Sun; Yuan Wang; Sen Jiang; Wanglong Zheng; et al. (Veterinary Microbiology, 2025)

Proteins extracted from placenta regulate osteogenic differentiation of human mesenchymal stem cells - Benjie Wei; Ying Chen; Shengmin Zhang; Laisen Cui; Shuo Zhang; Zhong Zhuang; Chunhui Sun; Na Ren; Hong Liu (Tissue and Cell, 2025)

Two pairs of isomeric resin glycosides from Argyreia obtusifolia - Shuo Chen; Yi-Lin Niu; Zhi-Tong Li; Hong-Hua Cui; Yong-Qin Yin; Yan-Fen Chen (Phytochemistry Letters, 2025)

Dismembered Guadalupian (Middle Permian) seamounts within the Yarlung-Tsangpo Suture Zone: Implications for the opening time of the Neo-Tethys Ocean - Hong-fu Zhou; Yi-chun Zhang; Mao Luo; Xin Li; Hua Zhang; Hai-peng Xu; Ruo-lan Liao; Qi Ju; Xiao-Hui Cui; Jun-jie Liu; Yao-feng Cai; Shu-zhong Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Effects of curcumin on jejunal morphology and intestinal integrity of broiler under heat stress - Ding-Ding Zhang; Meng-Ru Xue; Yu-Ting Liu; Hong-Jie Cui; Ding-Ping Bai (Journal of Thermal Biology, 2025)

Urbanization homogenized soil viral communities across three climate zones - Hu Liao; Xin Sun; Chen-Song Duan; Huayuan Shangguan; Hai-Feng Yao; Zhihong Qiao; Hong-Xia Cui; An Xie; Patrick O'Connor; Jian-Qiang Su (Journal of Hazardous Materials, 2025)

Advances in CDs composites toward detection and adsorption of uranium and other radioactive elements: A review - Jie Sun; Dongying Lin; Qian Wu; Zifan Hong; Xiaoyue Chen; Zhen Liu; Xing Liu; Junya Cui; Zhonghua Yuan; Xilin Xiao (Journal of Environmental Chemical Engineering, 2025)

Laser-engineered carbon hierarchies with multiscale attenuation mechanisms for ultrabroadband microwave absorption - Zhao Li; Nian Li; Yanping Song; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Shudong Zhang; Cui Liu; Min Xi; Congfa Song; et al. (Chemical Engineering Journal, 2025)

In situ tracking of MOF structural reconstruction toward a Cu/Bi/MOF composite electrocatalyst for efficient CO2-to-formate conversion - Yutao Cao; Yongjian Zhao; Tingting Tang; Shuo Cui; Min Li; Xianhu Sun; Wei Cui; Hong Zhao (Chemical Engineering Journal, 2025)

Tuning liganded nanocrack geometry for dynamic regulation of host macrophages - Hyunsik Hong; Sungkyu Lee; Choongmo Kang; Jungyeon Rhi; Hwapyung Jung; Ramar Thangam; Jeongah Shin; Yumi Cho; Jae Kwon Shin; Kanghyeon Kim; Jeongyun Heo; Qiyue Wang; et al. (Chemical Engineering Journal, 2025)

Examining mental resilience of contractor in urban rail transit construction project under disruptive events - Bei-Xuan Dong; Ming Shan; Ji-Hong Cui; Bon-Gang Hwang (Tunnelling and Underground Space Technology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Glycerol enhanced simultaneous selenite bioremediation and astaxanthin biosynthesis in Haematococcus lacustris - Yu-Hu Jiao; Zhong-Hong Zhang; Yu-Hong Liu; Yan Huang; Meng-Ting Jiang; Yong-Teng Zhao; Xinfei Xie; Wei-Dong Yang; Hong-Ye Li; Lei Cui; Xiang Wang (Journal of Hazardous Materials, 2025)

Supermolecule-derived N-containing carbon spherical nanoparticles inserted in expanded graphite for capacitive Zn-ion storage - Yuxiao Hu; Kai Zhang; Jiayin Shang; Qiguan Wang; Jiale Chen; Hong Deng; Yuxin Cui; Sumin Wang (Chemical Engineering Journal, 2025)

Bioinspired 4D printing of multi-responsive and tough hydrogels with micelle-enhanced double networks - Jingjing Bai; Fukang Liu; Jingjing Cui; Yibo Hong; Mingzheng Hao; Bingxiao Liu; Yanyan Lv; Yan Zhai; Weijie Ren; Zhenxing Qin; Biao Zhang (Chemical Engineering Journal, 2025)

Oral administration of nanozyme-armed probiotic Escherichia coli Nissle 1917 with ROS scavenging for inflammatory bowel disease therapy - Tiantian Cui; Bing Li; Zhaoyang Lou; Kai Yang; Kaijin Yan; Danhong Ding; Hong Ge (Chemical Engineering Journal, 2025)

Mitophagy-enhanced multimodal macrophage-derived hybrid nanovesicles for alleviating periodontitis-ulcerative colitis comorbidities: Killing two birds with one stone - Ya Cui; Shebin Hong; Weidong Jiang; Lixia Mao; Kaili Lin; Xudong Wang (Chemical Engineering Journal, 2025)

Chronic Anatabine Administration Attenuates Cardiovascular Activity by Targeting NF-κB/NLRP3/Caspase-1-Dependent Pyroptosis and Oxidative Stress in Paraventricular Nucleus of Hypertensive Rat - Qing Su; Shao-Jun Li; Jun-Yu Zhou; Jin-Bao Yang; Fang Zhao; Guo-Quan Zou; Jia-Xuan Ma; Qi Liu; Yuan-Yuan Feng; Cui-Ling Yang; Ying Li; Hong-Bao Li; et al. (Cardiovascular Toxicology, 2025)

Molecularly imprinted multifunctional polymer-modified single-atom-homojunctions for sensitive photoelectrochemical Escherichia coli O157:H7 sensing - Hong Zhou; Xufeng Zang; Bo Cui; Yizhong Shen; Haiteng Tao; Yishan Fang (Analytica Chimica Acta, 2025)

Trees suppress growth but sustain water consumption in response to flash drought in a subtropical forest - Yongqiang Zhang; Zeng Cui; Yun-Hao Bai; Hong-Tu Zhang; Zhiyao Tang (Agricultural and Forest Meteorology, 2025)

Corrigendum to “A combined process of reverse flotation and slurry electrolysis for step-by-step recovery of copper and gold from waste printed circuit boards” [Waste Manag. 198 (2025) 151–160] - Tingting Chen; Yutong Cui; Yifan Li; Xin Ma; Wei Shu; Zhanfang Cao; Hong Zhong; Shuai Wang (Waste Management, 2025)

Vibration energy transmission characteristics of vehicle-track coupled system considering dynamic viscoelasticity of vibration-damping pads - Weitao Cui; Liang Gao; Hong Xiao; Chaozhi Ma; Zhenyu Niu; Shuxin Zhao (Soil Dynamics and Earthquake Engineering, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Enhancing terrestrial net primary productivity estimation with EXP-CASA: A novel light use efficiency model approach - Guanzhou Chen; Kaiqi Zhang; Xiaodong Zhang; Hong Xie; Haobo Yang; Xiaoliang Tan; Tong Wang; Yule Ma; Qing Wang; Jinzhou Cao; Weihong Cui (Remote Sensing of Environment, 2025)

Impact of the environmental endocrine disruptor flutamide on cryptorchidism: Molecular mechanisms involving connexin-43 and p38-MAPK signaling - Yu Zhou; Yifan Hong; Shengwen Wang; Luna He; Yan Cui; Yinghua Wu; Fuli Yan; Chunlan Long; Jing Gao (Reproductive Toxicology, 2025)

Bridging the knowledge gap: From poly(butylene adipate-co-terephthalatebutylene) degradation to CO2-generating mineralization under the synergistic effect of bacteria and fungi - Yue Wang; Qi Liu; Chang-Hong Xie; Ruo-Tong Zhao; Qiu-Xiang Tang; Dong-Fei Han; Yi-Ning Xia; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Microwave-responsive ionic liquid with enhanced bactericidal, biocompatible and immunoregulatory properties for the prevention of abdominal adhesion - Wei Ye; Zhe Cui; Lingwan Hao; Xiaoli Han; Shenglin Ma; Liangju Duan; Zhizheng Zhou; Jie Zhao; Kun Hong; Liwei Sun; Rujian Jiang (Chemical Engineering Journal, 2025)

Enhancing Feammox efficiency through riboflavin and humic acid: Nitrogen and iron transformation, energy metabolism, and microbial response - Dun Guo; Lei Yang; Hao-Qi Lu; Yu-Chao Wang; Hong-Yan Meng; Pan Liang; Shen Cui; Zhang-Wei He; Jun Lan; Yong-Xiang Ren (Bioresource Technology, 2025)

Effects of MicroRNA-19b Carried by Endothelial Microparticles on the Phenotypic Switching of Vascular Smooth Muscle Cells and the Working Mechanism - Yuxia Cui; Junxian Song; Ting Ge; Manyan Wu; Chongyou Lee; Hong Chen (Bulletin of Experimental Biology and Medicine, 2025)

Molecular characterization of a novel mitovirus infecting the phytopathogenic fungus Colletotrichum camelliae - Hao Zeng; Bin Tian; Liangxuan Qu; Fuyin He; Wei Huang; Shuanglong Wang; Hong Liu; Lihong Cui (Archives of Virology, 2025)

A Channel-Aware AUV-Aided Data Collection Scheme Based on Deep Reinforcement Learning - Lizheng Wei; Minghui Sun; Zheng Peng; Jingqian Guo; Jiankuo Cui; Bo Qin; Jun-Hong Cui (Journal of Marine Science and Engineering, 2025)
Underwater sensor networks (UWSNs) play a crucial role in subsea operations like marine exploration and environmental monitoring. A major challenge for UWSNs is achieving effective and energy-efficient data collection, particularly in deep-sea mining, where energy limitations and long-term deployment are key concerns. This study introduces a Channel-Aware AUV-Aided Data Collection Scheme (CADC) that utilizes deep reinforcement learning (DRL) to improve data collection efficiency. It features an innovative underwater node traversal algorithm that accounts for unique underwater signal propagation characteristics, along with a DRL-based path planning approach to mitigate propagation losses and enhance data energy efficiency. CADC achieves a 71.2% increase in energy efficiency compared to existing clustering methods and shows a 0.08% improvement over the Deep Deterministic Policy Gradient (DDPG), with a 2.3% faster convergence than the Twin Delayed DDPG (TD3), and reduces energy cost to only 22.2% of that required by the TSP-based baseline. By combining a channel-aware traversal with adaptive DRL navigation, CADC effectively optimizes data collection and energy consumption in underwater environments.

Degradation of biodegradable plastic films in soil: microplastics formation and soil microbial community dynamics - Yue Wang; Run-Hao Bai; Qi Liu; Qiu-Xiang Tang; Chang-Hong Xie; Aurore Richel; Christophe Len; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Glandular trichome heads confer cadmium tolerance in Nicotiana tabacum L. via the co-regulation of JA and ABA signaling - Shuai Wang; Hong Cui; Yong Lin; Shiqiang Zhang; Yue Li; Meiqi Yan; Qi Wang; Chaoyi Zhou; Hongying Zhang (Journal of Hazardous Materials, 2025)

Assessment of geothermal waters in Yunnan, China: Distribution, quality and driving factors - Zhaojun Zeng; Li Yang; Yueju Cui; Xiaocheng Zhou; Miao He; Yuwen Wang; Yucong Yan; Bingyu Yao; Xiaojing Hu; Weiye Shao; Jian Li; Hong Fu (Geothermics, 2025)

Assessment of in vitro digestion properties and prebiotic potential of chayote (Sechium edule) pectin - Qing Guo; Xiaoxue Wang; Chun Yang; Jie Yu; Qiang Cui; Xiaoyan Hou; Guanghui Shen; Man Zhou; Hong Liu; Anjun Chen; Zhiqing Zhang (Food Bioscience, 2025)

High optical contrast and stable black electrochromic devices enabled by viologen and fluoran materials - Qilin Zhang; Xiong Liu; Yaowu He; Minming Yan; Imran Murtaza; Dongwen Zou; Tianhe Xu; Ying Cui; Lintao Zeng; Hong Meng (Chemical Engineering Journal, 2025)

Insight into algae-derived boron-doped biochar for efficient peroxydisulfate activation: The dominant effect of electron-transfer processes - Yu Chen; Yongqing Zhang; Hong Meng; Jiaqi Cui; Waseem Hayat; Yujun Zhuo; Charles Q. Jia (Journal of Environmental Chemical Engineering, 2025)

Montmorillonite-chitosan composite support enhances the electron transfer and stability of loaded copper nanoparticles during the catalytic reduction of Cr(VI) - Xiang-Zheng Cui; Yu Peng; Shuo Chen; Hong Jiang (Journal of Environmental Chemical Engineering, 2025)

Evaluating coarse PM composition and sources based on bulk and molecular speciation of PM2.5 and PM10 in Nanjing, East China - Wangnan Cui; Zishu Wang; Wei Feng; Chao Qin; Hong Liao; Yuhang Wang; Mingjie Xie (Journal of Environmental Sciences, 2025)

Hypoglycemic effects of Lactiplantibacillus plantarum B19 via promoting AMPK/PI3K/AKT signaling pathway - Mei-Jie Xiong; Rui Cui; Teng-Gen Hu; Hong Wu (Food Bioscience, 2025)

Preparation of chitosan/shellac nanoparticles-essential oil Pickering emulsion active film and its application in bread preservation - Jin-Ming Tan; Rui Cui; Teng-Gen Hu; Xiao-Xi Li; Hong Wu (Food Packaging and Shelf Life, 2025)

Experimental investigation of thermo-hydro-mechanical interactions in frozen soil using an integrated monitoring system - Bing Wu; Hong-Hu Zhu; Xu-Hui Guo; De-Yang Wang; Cui Wang; Mohamed A. Meguid (Engineering Geology, 2025)

Interfacial system optimization and dynamic self-healing for solid-state lithium metal batteries with high critical current density and long-term cycling stability - Kailiang Yu; Manying Cui; Qidi Wang; Hong Liu; Limin Liu; Yujia He; Pengfei Li; Juntao Gao; Xiangpeng Kong; Wandong Li; Caizhong Zhang; Kai Xi; et al. (Chemical Engineering Journal, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

RIG-I-driven CDKN1A stabilization reinforces cellular senescence - Cui Wang; Xiaoyu Jiang; Hong-Yu Li; Jianli Hu; Qianzhao Ji; Qiaoran Wang; Xiaoqian Liu; Daoyuan Huang; Kaowen Yan; Liyun Zhao; Yanling Fan; Si Wang; et al. (Science China Life Sciences, 2025)

Effect of culturing factors on the production of biomass and secondary metabolites in ginseng adventitious root cultures for new resource food - Hang-Lin Song; Zheng-Hai Cheng; Rong-De Jin; Chun-Guang Liu; Xiang-Hong Ma; Jun-Nan Wu; Xi-Hua Cui (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

The pharmacokinetics, pharmacodynamics and tolerability of SHR6508 in chinese healthy subjects: a randomized, placebo-controlled, double-blind, single-dose and dose-escalation phase I trial - Sheng-ting Zhang; Hong-yi Tan; Shuang Yang; Xiao-yan Yang; Chang Cui; Jie Huang; Guo-ping Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Global trends in staphylococcus aureus-related lower respiratory infections from 1990 to 2021: findings from the 2021 global burden of disease report - Hong Chen; Shuang Song; Rui Cui; Yong-Wang Feng; Peng Ge (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Unified Underwater Communication Positioning Navigation and Timing Network System Design and Application - Lipeng Huo; Mengzhuo Liu; Heng Wen; Zheng Peng; Yusha Liu; Xiaoxin Guo; Jun-Hong Cui (Journal of Marine Science and Engineering, 2025)
The dynamic and heterogeneous nature of marine environments, combined with severely constrained communication and energy resources, presents distinct challenges in constructing underwater Communication, Positioning, Navigation, and Timing (CPNT) systems compared to terrestrial Positioning, Navigation, and Timing (PNT) architecture. To address the inherent limitations of conventional decoupled CPNT systems – including high costs and low efficiency in communication and energy utilization – this study aims to propose a unified underwater CPNT (U2CPNT) system that coordinates multi-modal data and resource allocation, thereby optimizing CPNT service performance in harsh underwater conditions. In this study, Cramér-Rao Lower Bound (CRLB) formalization is applied to theoretically analyze the feasibility of U2CPNT system, and the design of U2CPNT system is presented to realize the integrated design of CPNT. To validate the system performance, a real U2CPNT system was built and sea trials were conducted. With U2CPNT architecture, the integrated CPNT service can be provided, the positioning error is lower, the positioning continuity has improved by 7.68%, the velocity estimation error is less than 1 m/s, making U2CPNT a potential solution for underwater CPNT service.

A combined process of reverse flotation and slurry electrolysis for step-by-step recovery of copper and gold from waste printed circuit boards - Tingting Chen; Yutong Cui; Yifan Li; Xin Ma; Wei Shu; Zhanfang Cao; Hong Zhong; Shuai Wang (Waste Management, 2025)

Effect of fault dislocation on the deformation and damage behavior of ballastless track structures in tunnels - Xuhao Cui; Yapeng Liu; Xiuli Du; Hong Xiao; Hongbin Xu; Yanliang Du (Transportation Geotechnics, 2025)

Enhancing the coupling coordination of soil–crop systems by optimising soil properties and crop production via subsoiling - Jingyi Shao; Ling Liu; Jichao Cui; Hong Yang; Yecheng Zhang; Ruxin Li; Yi Lv; Yifei Ma; Qin Fang; Shengkai Sun; Siyu Chen; Huifang Han (Soil and Tillage Research, 2025)

Climate change regulated carbonate production and accumulation in the Guaymas Basin over the past ca. 450,000 years - Hong Peng; Yuchen Zheng; Meng Zhou; Yasu Wang; Lihua Ran; Han Jiang; Ligia Pérez-Cruz; Rafael Venegas; Tobias Höfig; Andreas Teske; Daniel Lizarralde; Kathleen Marsaglia; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Recruitment of copiotrophic and autotrophic bacteria by hyperaccumulators enhances nutrient cycling to reclaim degraded soils at abandoned rare earth elements mining sites - Yong-He Han; Xi-Wen Cui; Hai-Yan Wang; Xiao-Bin Lai; Ying Zhu; Jia-Bing Li; Rong-Rong Xie; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2025)

The evolution of pore during the reduction of magnetite by H2 - Meijie Zhou; Liqun Ai; Lukuo Hong; Wenquan Cui; Caijiao Sun; Weijia An; Shuai Tong (Fuel, 2025)

Changes in volatile flavor compounds and metabolites during processing of Ginger milk curd from buffalo milk by GC-IMS and LC-MS - Dingyun Xu; Chuan Li; Hong Lan; Kuiqing Cui; Ling Li; Xier Luo; Hao Qi; Qingyou Liu (Food Research International, 2025)

Analysis of the antioxidant efficacy substances in fermented black mulberry juice and their preventive effects on oxidative stress in C2C12 cells - Mingshan Lv; Xiaolu Liu; Ruoqing Liu; Aihemaitijiang Aihaiti; Jingyang Hong; Li Zheng; Jun Xing; Yincang Cui; Liang Wang (Food Chemistry, 2025)

The transferrin a signaling pathway mediates uranium-induced hematopoietic dysfunction - Jin Gao; Fajian Luo; Qiu Chen; Na Chen; Jun Wan; Liang Sun; Yiyao Cao; Hong Ren; Yu Tu; Haiwen Huang; Fengmei Cui (Environmental Pollution, 2025)

Fossil leaf cuticle: Best practices for preparation and paleo-CO2 analysis - Xiaoqing Zhang; Dana L. Royer; Carina E. Colombi; Juan Martin Drovandi; Jennifer C. McElwain; Gaëtan Guignard; Qin Leng; Barry H. Lomax; Nathan D. Sheldon; Rebekah A. Stein; Garland R. Upchurch; Yongdong Wang; et al. (Earth-Science Reviews, 2025)

Altered 3D genome reorganization mediates precocious myeloid differentiation of aged hematopoietic stem cells in inflammation - Xinyu Cui; Yu Dong; Qiang Zhan; Yixin Huang; Qianshu Zhu; Zihao Zhang; Guang Yang; Liping Wang; Shijun Shen; Jia Zhao; Zhiyi Lin; Jiatong Sun; et al. (Science China Life Sciences, 2025)

The accumulation of major active ingredients associated to mutualistic endophytic fungi in the stem of Ephedra sinica with different growth years - Zhao-Qi Cui; Hong-He Xiao (Symbiosis, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Morphine Contributes to Epithelial-Mesenchymal Transition in Triple-Negative Breast Cancer Cells by Blocking COX-2 Methylation via Regulating the miR-23a-3p/DNMT3A Feedback - Jian Cui; Nina Ma; Xiaohui Li; Xuexin Chen; Junxia Zhang; Wenjuan Zhang; Hong Li (Cell Biochemistry and Biophysics, 2025)

Unveiling the role of exogenous cobalamin on anammox performance: Nitrogen removal, sludge and microbial characterization - Cui-Zhong Chen; Jin Wang; Ping-Juan Zheng; Jian-Hong He; Meng-Jiao Gao; Peng Yan; You-Peng Chen (Journal of Water Process Engineering, 2025)

Fertilization-recruited Actinomycetota enhances nutrient and energy metabolisms to favor plant growth and arsenic accumulation in Pteris vittata - Yong-He Han; Yi-Xi Li; Xi-Wen Cui; Ying Zhu; Hong Zhang; Yong Zhang (Journal of Environmental Chemical Engineering, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Extraction and immobilization of potato esterase and its application in the detection of potato glycoalkaloids - Qing Guo; Jing Li; Jie Yu; Qiang Cui; Xiaoyan Hou; Hong Liu; Man Zhou; Guanghui Shen; Zhiqing Zhang (Food Bioscience, 2025)

Acid-base interaction modulating the pH responsiveness of fluorescent carbon nanoparticles for time-resolved information encryption and anti-counterfeiting - Sha Luo; Haitao Deng; Junyi Chen; Shuqi Xu; Yong Tian; Fuhua Huang; Hong Wang; Jiaxi Cui; Jian Chen (Chemical Engineering Journal, 2025)

Microalgal biofilm cultivation on lignocellulosic based bio-carriers: Effects of material physical characteristics on microalgal biomass production and composition - Rumeng Lu; Biyuan Hong; Yunpu Wang; Xian Cui; Cuixia Liu; Yuhuan Liu; Xiaodan Wu; Roger Ruan; Qi Zhang (Chemical Engineering Journal, 2025)

A novel electrolytic gas lift reactor for efficient microbial electrosynthesis of hydrogen-oxidizing bacterial single-cell protein from CO2 - Jinpeng Yu; Kai Cui; Xiaona Hu; Hong Zhang; Gaoyuan Shang; Yuhan Guo; Kun Guo (Systems Microbiology and Biomanufacturing, 2025)

Histaminergic Innervation of the Ventral Anterior Thalamic Nucleus Alleviates Motor Deficits in a 6-OHDA-Induced Rat Model of Parkinson’s Disease - Han-Ting Xu; Xiao-Ya Xi; Shuang Zhou; Yun-Yong Xie; Zhi-San Cui; Bei-Bei Zhang; Shu-Tao Xie; Hong-Zhao Li; Qi-Peng Zhang; Yang Pan; Xiao-Yang Zhang; Jing-Ning Zhu (Neuroscience Bulletin, 2025)
The ventral anterior (VA) nucleus of the thalamus is a major target of the basal ganglia and is closely associated with the pathogenesis of Parkinson’s disease (PD). Notably, the VA receives direct innervation from the hypothalamic histaminergic system. However, its role in PD remains unknown. Here, we assessed the contribution of histamine to VA neuronal activity and PD motor deficits. Functional magnetic resonance imaging showed reduced VA activity in PD patients. Optogenetic activation of VA neurons or histaminergic afferents significantly alleviated motor deficits in 6-OHDA-induced PD rats. Furthermore, histamine excited VA neurons via H1 and H2 receptors and their coupled hyperpolarization-activated cyclic nucleotide-gated channels, inward-rectifier K + channels, or Ca 2+ -activated K + channels. These results demonstrate that histaminergic afferents actively compensate for Parkinsonian motor deficits by biasing VA activity. These findings suggest that targeting VA histamine receptors and downstream ion channels may be a potential therapeutic strategy for PD motor dysfunction.

Correction: Inhibition of 12/15 lipoxygenase by baicalein reduces myocardial ischemia/reperfusion injury via modulation of multiple signaling pathways - Lina Song; Hui Yang; Hong-Xia Wang; Cui Tian; Yu Liu; Xiang-Jun Zeng; Erhe Gao; Yu-Ming Kang; Jie Du; Hui-Hua Li (Apoptosis, 2025)

Hamiltonian based AUV navigation using adaptive finite-time trajectory tracking control - Jiankuo Cui; Mengxue Hou; Zheng Peng; Ying Wang; Jun-Hong Cui (Ocean Engineering, 2025)

Transcriptomic combined with molecular dynamics simulation analysis of the inhibitory mechanism of clove essential oil against Staphylococcus aureus biofilm and its application on surface of food contact materials - Hong Li; Jun Li; Zichun Hua; Tariq Aziz; Ebtihal Khojah; Haiying Cui; Lin Lin (Food and Bioproducts Processing, 2025)

Maternal green space exposure and congenital heart defects: A population-based study - Shihan Zhen; Lu Zheng; Qian Li; Zhouxin Yin; Hong Cui; Yan Li; Shuqi Wu; Kecheng Li; Ying Zhao; Fengchao Liang; Jiajin Hu (Environmental Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Comamonas squillarum sp. nov., Isolated from Intestine of Red Swamp Crayfish (Procambarus clarkii) - Shi Shi; Dao-Feng Zhang; Hong-Chuan Wang; Fu-Hui Jiang; Li-Fan Cui; Ying Huang (Current Microbiology, 2025)

Immobilized Chlorella salina for removing nitrogenous and phosphorous compounds from mariculture tail water - Pengbing Pei; Zijie Xie; Muhammad Aslam; Shuangcheng Jiang; Qi Lin; Hongli Cui; Hong Du (Algal Research, 2025)

The replication efficacy of NADC34-like porcine reproductive and respiratory syndrome virus 2 is not directly associated with the pathogenicity - Meng Cui; Ming Qiu; Shuai Yang; Yuejia Qiu; Wenhao Qi; Hong Lin; Zhe Sun; Wanglong Zheng; Jianzhong Zhu; Nanhua Chen (Veterinary Microbiology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Moxifloxacin plus Cordyceps polysaccharide ameliorate intestinal barrier damage due to abdominal infection via anti-inflammation and immune regulation under simulated microgravity - Hong-Yun Nie; Jun Ge; Kai-Ge Liu; Yuan Yue; Hao Li; Hai-Guan Lin; Tao Zhang; Hong-Feng Yan; Bing-Xin Xu; Hong-Wei Sun; Jian-Wu Yang; Shao-Yan Si; et al. (Life Sciences in Space Research, 2025)

An ultrathin Al2O3 ceramic membrane prepared by organic-inorganic blending with solvent evaporation and high-temperature sintering for highly efficient oil/water separation - Yixiao Wang; Zishang Chen; Yuxuan Zhu; Hong Wang; Zhenyu Cui; Xianhui Li; Jiahao Mo; Jianxin Li (Journal of Water Process Engineering, 2025)

Chayote pectin regulates blood glucose through the gut-liver axis: Gut microbes/SCFAs/FoxO1 signaling pathways - Qing Guo; Xiaoxue Wang; Jingxuan Ke; Xiaoyan Hou; Guanghui Shen; Shanshan Li; Hong Chen; Qiang Cui; Jie Yu; Qingying Luo; Hong Liu; Anjun Chen; et al. (Food Research International, 2025)

Cleaner preparation of N-lauroyl theanine with taste-enhancing properties and deciphering its taste-presenting mechanism - Lei Cai; Xiyu Mou; Jieshee Hong; Chun Cui (Food Chemistry, 2025)

Enhancement of antibacterial activity of cinnamaldehyde against Bacillus cereus by nanoemulsion and its application in milk - Rui Cui; Fu-Yu Liu; Hong Wu (Food Bioscience, 2025)

Synergistic effect of 2′-Fucosyllactose or galactooligosaccharide with Bifidobacterium bifidum DNG6 improves the intestinal barrier by modulating the SCFAs-TLR4/NF-κB cascade response in DSS-induced colitis in mice - Cui-Cui Sun; Yu-Qi Wang; Xin-Yu Wang; Guo-Fang Zhang; Hong-Fang Cao; Ge Song; Li-Bo Liu; Chun Li; Irina Valeryevna Boyarineva; Peng Du (Food Bioscience, 2025)

Improving the bactericidal activity of carvacrol against Bacillus cereus by the formation of sodium casein-stabilized nanoemulsion and its application in milk preservation - Jun Li; Fu-Yu Liu; Bao-Lin He; Rui Cui; Hong Wu (Food Hydrocolloids, 2025)

A carbon membrane-aerated electrochemical reactor for efficient electrosynthesis of H2O2 - Jiawei Dong; Minghui Du; Hong Wang; Zhengyu Cui; Shuanglin Gui; Qinliang Jiang; Jianxin Li (Chemical Engineering Journal, 2025)

Areal Health Risk Assessment Using Soil Bioaccessible Heavy Metal(loid)s Around Industrial Area in Nanjing, Southeast China - Yangxiaoxiao Shi; Yadan Wang; Xueqing Zhang; Feng Zhang; Jiaqi Cui; Zhineng Hong; Jun Jiang; Renkou Xu (Exposure and Health, 2025)

Inoculation of plant growth-promoting rhizobacteria and rhizobia changes the protist community of alfalfa rhizosphere soil under saline-alkali environment - Yang Sun; Lu Tang; Ying Cui; Dihe Yang; Hong Gao; Jiaxin Chen; Ziying Zheng; Changhong Guo (Applied Soil Ecology, 2025)

YOLOv10-UDFishNet: detection of diseased Takifugu rubripes juveniles in turbid underwater environments - Wan Tu; Hong Yu; Zijian Wu; Jian Li; Zhibo Cui; Zongyi Yang; Xin Zhang; Yue Wang (Aquaculture International, 2025)

Seipin Deficiency Impairs Motor Coordination in Mice by Compromising Spinal Cord Myelination - Hong Chen; Wenru Wang; Wenli Cui; Chuanyun Tu; Yuanyuan Han; Chengwu Zhang; Liu Yang; Xintao Huang; Qin Zhang; Li Lu (NeuroMolecular Medicine, 2025)

Optimized Bi-LSTM Model for Short-Term Predicting of Ship State with Definitions of Surf-Riding and Broaching - Yunlong Du; Meng Cui; Jinya Xu; Zhichao Hong; Jiaye Gong (Journal of Marine Science and Engineering, 2025)
This paper introduces a hybrid prediction method that combines the Bi-LSTM neural network with definitions of surf-riding, wave-blocking and broaching to enhance the safety and stability of ship navigation. The hybrid method can accurately predict ships’ attitude motions and states by recognizing ship states and encoding them into one-hot representations. The Bi-LSTM model’s bidirectional learning capability captures significant temporal dependencies, enabling precise and timely predictions of complex maritime events across various conditions. Additionally, the direct output approach of state features improves prediction accuracy by eliminating intermediate steps, allowing for the better anticipation of and response to critical events. Validated with ship navigation data from autopilot simulations in wave conditions, the hybrid method outperforms conventional methods based on LSTM and Bi-LSTM models, demonstrating strong generalization capabilities and significantly contributing to safer and more stable ship navigation.

Assessing wildfire susceptibility and spatial patterns in diverse forest ecosystems across China: An integrated geospatial analysis - Yuping Tian; Zechuan Wu; Shuai Cui; Woyuan Hong; Bin Wang; Mingze Li (Journal of Cleaner Production, 2025)

Application of multiple dynamic sensory techniques to N-lauroyl amino acids: Exposing the relationship between taste-enhancing properties and chemical structure - Lei Cai; Jieshee Hong; Chun Cui (Food Chemistry, 2025)

Fe, Cu dual-atom catalysts assisted molecularly imprinted electrochemiluminescence sensor for ultrasensitive detection of trichlorfon - Xinran Wang; Xufeng Zang; Hong Zhou; Na Wang; Yishan Fang; Bo Cui (Food Chemistry, 2025)

Effects of chitosan/eugenol-loaded IRMOF-3 nanoparticles composite films on reactive oxygen species metabolism and microbial community dynamics in postharvest strawberries - Yuyue Qin; Hongda Yu; Kejun Chen; Rui Cui; Jianxin Cao; Zhengxuan Wang; Zhi-Hong Zhang; Thanapop Soteyome (Food Bioscience, 2025)

Potential of probiotic-fermented Flos sophorae as a functional food: Enhanced anti-hyperuricemic activity and modulation of volatile components - Rui Cui; Cong Zhang; Zhen-Hui Pan; Teng-Gen Hu; Hong Wu (Food Bioscience, 2025)

Improved viability of probiotics by co-encapsulation of wheat germ oil under storage and gastrointestinal conditions: Effects of drying methods and wall composition - Bao-Lin He; Rui Cui; Teng-Gen Hu; Hong Wu (Food Hydrocolloids, 2025)

A QGIS framework for physically-based probabilistic modelling of landslide susceptibility: QGIS-FORM - Jian Ji; Bin Tong; Hong-Zhi Cui; Xin-Tao Tang; Marcel Hürlimann; Shigui Du (Environmental Modelling & Software, 2025)

Dynamic transport of Zn2+ in ionic liquid intercalated V2O5 cathode for high-performance aqueous Zn-ion batteries - Wenzhe Su; Zanyu Chen; Xingkai Wang; Peng Cui; Minjie Yao; Hui Sun; Hong Zhang; Yida Deng; Xiaopeng Han; Wenbin Hu (Chemical Engineering Journal, 2025)

Flower-structured CoP@MoS2-x S-scheme heterojunction photocatalysts for enhanced hydrogen evolution and selective biomass oxidation - Jia Zhang; Jiliang Ma; Rui Cui; Weikang Ling; Min Hong; Runcang Sun (Chemical Engineering Journal, 2025)

Starch/polyacrylamide hydrogels with flexibility, conductivity and sensitivity enhanced by two imidazolium-based ionic liquids for wearable electronics: Effect of anion structure - Ziling Zhang; Lu Lu; Bingbing Hong; Qichao Ye; Li Guo; Chao Yuan; Bo Liu; Bo Cui (Carbohydrate Polymers, 2025)

Integrating aromatic plants into indoor biophilic environments: Species selection based on psychophysiological effects and bioactive volatile compounds - Jingxian Cui; Zhaoming Li; Wenzhu Zhang; Lingshan Wang; Hong Liu; Hui Liu (Building and Environment, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)

Research on Path-Following Technology of a Single-Outboard-Motor Unmanned Surface Vehicle Based on Deep Reinforcement Learning and Model Predictive Control Algorithm - Bin Cui; Yuanming Chen; Xiaobin Hong; Hao Luo; Guanqiao Chen (Journal of Marine Science and Engineering, 2024)
Path following is one of the key technologies for unmanned surface vehicles (USVs). This paper proposes a path-tracking control method for a single-outboard-motor USV based on a Deep Deterministic Policy Gradient (DDPG) algorithm and model predictive control (MPC) algorithm. Initially, the motion model and outboard motor model of the USV are analyzed. Subsequently, simulation and real ship experiments provide a comprehensive performance comparison between the proposed DDPG-MPC method and the traditional ALOS-PID method. The results indicate that for straight path tracking, the DDPG-MPC algorithm achieves 37% and 21% reductions in the average cross error and heading angle error, respectively, compared to the ALOS-PID algorithm. The real ship experiments further validate the DDPG-MPC algorithm’s advantages in real-world environments. Specifically, under disturbances like wind, waves, and currents, the maximum cross error of the DDPG-MPC algorithm is one-third of the ALOS-PID algorithm. Additionally, the DDPG-MPC algorithm sustains a higher and more stable longitudinal velocity over extended periods, while the ALOS-PID algorithm shows greater instability and variability. Overall, the findings confirm the feasibility and effectiveness of the proposed approach, highlighting its potential for enhancing path-tracking control performance in single-outboard-motor USVs.

Interventions of river connectivity and land use on indices of biotic integrity (IBIs) in plain river networks - Yufan Lu; Yaoyi Liu; Hong Qin; Shasha Ma; Xuebing Bai; Feng Xu; Cui Wang; Lei Shi; Yue Che (Environmental Monitoring and Assessment, 2024)

Dynamic trends in maize diseases and pests across six regions in China over two decades - Hong-ying Cui; Amber Sciligo; Xiao-ling Tan; Cang Hui; Yong-sheng Zhang; Wei Li; Zi-qiao Zhou; Zhen-qing Peng; Ping Ma; Zhi-shu Xiao; Fang Ouyang (Crop Protection, 2024)

The intervention mechanism of Tanshinone IIA in alleviating neuronal injury induced by HMGB1 or TNF-α-mediated microglial activation - Yan-Zhu Quan; Jing-He Wang; Si-Hui Zhang; Guang-Nan Jin; Jing-Mei Lu; Yi-Ming Liu; Hong-Yan Gao; Jin-Yi Zhou; Bing-Zhe Wang; Yan Xin; Yue-Xian Cui; Xiang Xu; et al. (Toxicology in Vitro, 2024)

Coupling polyethylene microplastics with other pollutants: Exploring their combined effects on plant health and technologies for mitigating toxicity - Linmei Cui; Rong Liang; Chi Zhang; Ruifang Zhang; Hong Wang; Xin-Xin Wang (Science of The Total Environment, 2024)

Shifting agricultural land use and its unintended water consumption in the North China Plain - Liang Dong; Di Long; Caijin Zhang; Yingjie Cui; Yanhong Cui; Yiming Wang; Luoqi Li; Zhongkun Hong; Ling Yao; Jinling Quan; Liangliang Bai; Hao Wang; et al. (Science Bulletin, 2024)

Surface carbonate dynamics in a temperate coastal system in the Northern Yellow Sea, China - Yawen Wei; Wei Yang; Xue Deng; Taikun Jin; Fuxu Cui; Kuishuang Shao; Zongcai He; Hong Chen; Jianbo Han; Xuemei Xu (Regional Studies in Marine Science, 2024)

Numerical simulation and analysis of UUV docking with a Seabed Moored Floating Dock - Jingqian Guo; Hua Tan; Jun Liu; Wei Feng; Zheng Peng; Yusha Liu; Jun-Hong Cui (Ocean Engineering, 2024)

Association between indoor PM2.5 components and accelerated biological aging in schizophrenia patients: Evidence from multi-omics mechanisms - Rubing Pan; Xingxu Yi; Yanlong Xu; Jian Song; Weizhuo Yi; Jintao Liu; Rong Song; Xuanxuan Li; Li Liu; Jiajun Yuan; Ning Wei; Yuxing Huang; et al. (Journal of Hazardous Materials, 2024)

Antibiotic resistance at environmental multi-media interfaces through integrated genotype and phenotype analysis - Chen-Xi Fu; Chen Chen; Qian Xiang; Yi-Fei Wang; Lu Wang; Feng-Yuan Qi; Dong Zhu; Hong-Zhe Li; Li Cui; Wei-Li Hong; Matthias C. Rillig; Yong-Guan Zhu; et al. (Journal of Hazardous Materials, 2024)

Trade-offs between Cd bioconcentration and translocation and underlying physiological and rhizobacterial mechanisms in Phragmites australis - Meiqi Yin; Xiya Zhang; Hong Zhu; Wenyi Sheng; Yiming Wu; Dongzi Jiang; Qishen Wen; Hongjin Shao; Yaolin Guo; Cui Wang; Luyao Ma; Xiaona Yu; et al. (Journal of Environmental Management, 2024)

Metabolic pathway analysis of methane from methanol as substrate in microbial consortium - Chen Zhao; Aman Khan; Zhang Wei; Wang Jinghong; Zhang Fangzheng; Shen Guinan; Hong Yanhua; Wei Dan; Cui Zongjun; Wang Weidong (Bioresource Technology, 2024)

Comparative analysis of hydrogel-based thermotropic glazing and fixed horizontal overhangs in building performance - Xiaoqiang Hong; Xuan Yang; Yilin You; Feng Shi; Fan Yang; Chuanrong Cui; Yingming Gong; Dewei Qian (Building and Environment, 2024)

Effective law enforcement in gray zone operations: A Chinese perspective of coastguard law implementation in delimited maritime zones - Hong-Ming Cui; Khadija Zulfiqar (Marine Policy, 2024)

Damage mechanism of a shield tunnel with cavities behind the concrete lining: An insight from a scaled model test - Yunpeng Yue; Shangyang Zhang; Hai Liu; Fan Hong; Chao Liu; Jie Cui; Yanliang Du (Tunnelling and Underground Space Technology, 2024)

Spatial distribution, source apportionment, and risk assessment of perfluoroalkyl substances in urban soils of a typical densely urbanized and industrialized city, Northeast China - Wei Zhao; Jilong Lu; Qiaoqiao Wei; Jinxin Cao; Jiaxuan Cui; Yaru Hou; Kaiyu Zhang; Hong Chen; Wei Zhao (Science of The Total Environment, 2024)

Vegetation increases global climate vulnerability risk by shifting climate zones in response to rising atmospheric CO2 - Mingzhu He; Jiangpeng Cui; Yonghong Yi; Hans W. Chen; Qian Zhang; Lili Li; Ling Huang; Songbai Hong (Science of The Total Environment, 2024)

Elevated sea surface temperature and enhanced primary productivity during Ocean Anoxic Event 1d in the eastern Tethys: Calcareous nannofossil evidence from southern Tibet, China - Yasu Wang; Shijun Jiang; Ying Cui; Ruize Liang; Hong Su (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Influence of soil pH and organic carbon content on the bioaccessibility of lead and copper in four spiked soils - Jiaqi Cui; Hongbo Li; Yangxiaoxiao Shi; Feng Zhang; Zhineng Hong; Di Fang; Jun Jiang; Yujun Wang; Renkou Xu (Environmental Pollution, 2024)

In situ iron coating of amorphous boron and characterization of its energy release behavior - Hongyang Li; Hong Li; Chao Wang; Zhenfeng Shen; Shentao Zeng; Sujun Shi; Qing Cai; Wenqi Xu; Ran Wang; Cui Luo; Ying Liu (Chemical Engineering Journal, 2024)

Design of graphitic multichannel monolith electrode with in-situ transformed Ni-N-C sites for continuous electrolysis of CO2 - Xu Hu; Hong-Liang Xu; Ling-Yu Dong; Wen-Cui Li; Guang-Ping Hao; An-Hui Lu (Chemical Engineering Journal, 2024)

Mechanism of o-cresol polymerization and its carbon recovery from aqueous solution by a cathode/Fe2+/H2O2 process - Sui-Qin Yang; Yu-Hong Cui; Wei-Jun Xue; Zheng-Qian Liu; Rui Hu; Xiao-Qian Ye (Chemical Engineering Journal, 2024)

Advanced design of metal single-atom (Pt, Mn, Fe or Cu) loaded S-Ni(OH)2 nanosheets array catalysts to achieve high-performance overall water splitting - Wenhui Fang; Tingting Tang; Min Li; Shixian Xin; Ying Wu; Yutao Cao; Zhize Yu; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2024)

Comparative efficacy of alkaline slag, biomass ash, and biochar application for the amelioration of different acidic soils - Ernest Uwiringiyimana; Hong-wei Lai; Ni Ni; Ren-yong Shi; Xiao-ying Pan; Jia-ning Gao; Md Romel Biswash; Jiu-yu Li; Xiu-min Cui; Ren-kou Xu (Plant and Soil, 2024)

Time-varying characteristics of coherence for tri-directional seismic ground motions - M.Y. Xiao; X.Z. Cui; H.P. Hong (Soil Dynamics and Earthquake Engineering, 2024)

Effects of socioeconomic status and regional inequality on the association between PM2.5 and its components and cardiometabolic multimorbidity: A multicenter population-based survey in eastern China - Zhiqian Cui; Xinxu Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Rong Song; Jintao Liu; Rubing Pan; Weizhuo Yi; Xiaoyu Jin; Jian Song; et al. (Science of The Total Environment, 2024)

Roof greening in major Chinese cities possibly afford a large potential carbon sink - Chao Yang; Yinghui Zhang; Min Chen; Song Zhu; Yuzhi Tang; Zhixin Zhang; Wei Ma; Huizeng Liu; Junyi Chen; Bohui Tang; Dejin Zhang; Zhengdong Huang; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Hydrogen bonding-mediated interaction underlies the enhanced membrane toxicity of chemically transformed polystyrene microplastics by cadmium - Wanqing Zhao; Tong Ye; Jianwen Zhou; Xuan Zhang; Ke Wang; Hong Zhang; Jiansheng Cui; Shuping Zhang; Lixin Wang (Journal of Hazardous Materials, 2024)

Carbon allowance allocation and CO2 flows analysis in CCUS under the carbon market - Jun Zhou; Cui Liu; Guangchuan Liang; Shitao Liu; Cuicui Li; Bingyuan Hong (Journal of Cleaner Production, 2024)

Dicranopteris pedata improves soil quality by enhancing nutrient deposition, decreasing metal concentration, and boosting microbial diversity on abandoned rare earth elements mining sites - Xi-Wen Cui; Zhen-An Xu; Xian Chen; Zhi-Biao Chen; Jia-Bing Li; Rong-Rong Xie; Hong Zhang; Yong Zhang; Yong-He Han (Journal of Environmental Chemical Engineering, 2024)

Potentially toxic element source apportionment and risk assessment in agricultural soils around a large-scale Pb-Zn mine in Southwest China - Heng Wei; Xuekui Niu; Minmin Li; Canwen Cui; Zhonghua Wei; Wei Long; Man Tang; Hong Yu; Peng Zhang; Liping He; Bo Pan (Journal of Environmental Chemical Engineering, 2024)

Heterostructure-anchored 3D CNT-bridged graphene architecture via layer-by-layer structural engineering for thick electrodes of supercapacitors - Yanping Song; Nian Li; Jun Kang; Zhao Li; Na Hong; Shuai Han; Liqing Chen; Shudong Zhang; Cui Liu; Congfa Song; Jiakuan Zhang; Zhenyang Wang (Chemical Engineering Journal, 2024)

Unlocking the ultrafast laser response and low initiation energy of perchlorate-free tetrazine-based energetic coordination compounds - Hong-Yi Bian; Yun-Fan Yan; Meng Cui; Hao-Hui Xie; Tian-Tian Song; Xiao-Di Guo; Jian-Gang Xu; Fa-Kun Zheng; Guo-Cong Guo (Chemical Engineering Journal, 2024)

Loss of Tet hydroxymethylase activity causes mouse embryonic stem cell differentiation bias and developmental defects - Mengting Wang; Liping Wang; Yanxin Huang; Zhibin Qiao; Shanru Yi; Weina Zhang; Jing Wang; Guang Yang; Xinyu Cui; Xiaochen Kou; Yanhong Zhao; Hong Wang; et al. (Science China Life Sciences, 2024)

Application of unmanned aerial vehicle tilt photography technology in geological hazard investigation in China - Zhi-Hong Zhao; Hao Sun; Nian-Xiao Zhang; Tian-Hui Xing; Guan-Hua Cui; Jin-Xing Lai; Tong Liu; Yi-Bin Bai; Hai-Jun He (Natural Hazards, 2024)

Evaluating the impact of biochar amendment on antibiotic resistance genes and microbiome dynamics in soil, rhizosphere, and endosphere at field scale - Zhenchao Zhou; Erping Cui; Abbas Ali Abid; Lin Zhu; Jianming Xu; Hong Chen (Journal of Hazardous Materials, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Selenium alleviates pancreatic fibrosis in chickens caused by mercuric chloride: Involvement of the MAPK signaling pathway and selenoproteins - Yue Li; Han Cui; Dan Li; Hong-Yu Fu; Jiu-Zhi Li; Wan-Xue Xu; Rui-Feng Fan (Environmental Pollution, 2024)

Manganese (III) phthalocyanine complex nanoassembly: Oxygen-Independent generation of superoxide radicals and singlet oxygen for ultrasound-augmented chemodynamic therapy - Yun Sun; Chao Li; Zhaoyang Liu; Chaojie Tang; Zhankun Cui; Zhiguo Zhou; Qian Liu; Wu Wang; Shiping Yang; Hong Yang (Chemical Engineering Journal, 2024)

Dynamic Characteristic Analysis of Underwater Suspended Docking Station for Resident UUVs - Jingqian Guo; Lingshuai Meng; Mengmeng Feng; Jun Liu; Zheng Peng; Wei Feng; Jun-Hong Cui (Journal of Marine Science and Engineering, 2024)
The widespread use of Unmanned Underwater Vehicles (UUVs) in seafloor observatory networks highlights the need for docking stations to facilitate rapid recharging and effective data transfer. Floating docks are promising due to their flexibility, ease of deployment, and recoverability. To enhance understanding and optimize UUV docking with floating docks, we employ dynamic fluid body interaction (DFBI) to construct a seabed moored suspended dock (SMSD) model that features a guiding funnel, a suspended body, and a catenary of a mooring chain. This model simulates SMSD equilibrium stabilization in various ocean currents. Then, a UUV docking model with contact coupling is developed from the SMSD model to simulate the dynamic contact response during docking. The accuracy of the docking model was validated using previous experimental data. Through investigation of the UUV docking response results, sensitivity studies relating to volume, moment of inertia, mass, and catenary stiffness were conducted, thereby guiding SMSD optimization. Finally, sea tests demonstrated that the SMSD maintained stability before docking. During docking, the SMSD’s rotation facilitated smooth UUV entry. After the UUV docked, the SMSD was restored to its original azimuth, confirming its adaptability, stability, and reliability.

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

Discrete element analysis of the dynamic behavior of ballast track-subgrade system under train dynamic load - Xuhao Cui; Hong Xiao; Yang Xu; Peng Jing; Hao Fu; Zhihai Zhang; Yihao Chi (Soil Dynamics and Earthquake Engineering, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

A novel zwitterionic magnetic nanocomposite developed for non-invasive speciation analysis of inorganic chromium - Faisal Faiz; Yi-fan Pan; Sen Zhang; Jinxia Dai; Jun-qin Qiao; Hong-zhen Lian; Li Mao; Xiao-bing Cui (Journal of Hazardous Materials, 2024)

Integrated whole genome sequencing and transcriptomic analysis reveal the biodegradation mechanism of vanillic acid in Herbaspirillum aquaticum KLS-1 - Yong-He Han; Yi-Xi Li; Wen-Qian Qiu; Xi-Wen Cui; Xian Chen; Yong Zhang; Hong Zhang; Shan-Shan Wang (Journal of Environmental Chemical Engineering, 2024)

Realization of valence band convergence for high thermoelectric performance p-type PbS - Ming Wu; Hong-Hua Cui; Zixuan Chen; Jing Zhou; Hongwei Ming; Zhong-Zhen Luo; Zhigang Zou (Chemical Engineering Journal, 2024)

PVSPE: A pyramid vision multitask transformer network for spacecraft pose estimation - Hong Yang; Xueming Xiao; Meibao Yao; Yonggang Xiong; Hutao Cui; Yuegang Fu (Advances in Space Research, 2024)

IGFBP2 induces podocyte apoptosis promoted by mitochondrial damage via integrin α5/FAK in diabetic kidney disease - Xiaochen Wang; Yifan Zhang; Kun Chi; Yuwei Ji; Keying Zhang; Ping Li; Zhangning Fu; Xu Wang; Shaoyuan Cui; Wanjun Shen; Guangyan Cai; Xiangmei Chen; et al. (Apoptosis, 2024)

Somatic BrafV600E mutation in the cerebral endothelium induces brain arteriovenous malformations - Tianqi Tu; Jiaxing Yu; Chendan Jiang; Shikun Zhang; Jingwei Li; Jian Ren; Shiju Zhang; Yuan Zhou; Ziwei Cui; Haohan Lu; Xiaosheng Meng; Zhanjing Wang; et al. (Angiogenesis, 2024)

Pectin mediates the mechanism of host blood glucose regulation through intestinal flora - Qing Guo; Xiaoyan Hou; Qiang Cui; Shanshan Li; Guanghui Shen; Qingying Luo; Hejun Wu; Hong Chen; Yuntao Liu; Anjun Chen; Zhiqing Zhang (Critical Reviews in Food Science and Nutrition, 2024)

Maneuver Planning for Multiple Pursuit Intelligent Surface Vehicles in a Sequence of Zero-Sum Pursuit–Evasion Games - Le Hong; Weicheng Cui; Hao Chen; Changhui Song; Weikun Li (Journal of Marine Science and Engineering, 2024)
Unmanned surface pursuit is a complex and challenging engineering problem, especially when conducted by multiple intelligent surface vehicles (ISVs). To enhance the pursuit performance and facilitate strategic interaction during the target pursuit, this paper proposes a novel game theory-based maneuver planning method for pursuit ISVs. Firstly, a specific two-player zero-sum pursuit–evasion game (ZSPEG)-based target-pursuit model is formed. To ensure the vehicles reach a quick consensus, a target-guided relay-pursuit mechanism and the corresponding pursuit payoffs are designed. Meanwhile, under the fictitious play framework, the behavioral pattern and the strategies of the target could be fictitiously learned. Furthermore, mixed-strategy Nash equilibrium (MNE) is employed to determine the motions for the vehicles, the value of which is the best response in the proposed ZSPEG model. Finally, simulations verify the effectiveness of the above methods in multi-ISV surface pursuit.

The A subunit of vacuolar H+-ATPase gene (CmVHA-A) plays opposite roles in plant growth and drought tolerance of chrysanthemum under different growing conditions - Yan-Hong Liu; Zhen-Hao Zou; Man-Man Zhang; Zhang-Ji Guan; Lian-Da Du; Da-Gang Hu; Cheng-Shu Zheng; Cui-Hui Sun (Plant Science, 2024)

Transformation of metoprolol in UV/PDS process: Role and mechanisms of degradation and polymerization - Sui-Qin Yang; Rui-Qiu Ye; Yu-Hong Cui; Zheng-Qian Liu; Kai Sun; Yu-Ze Yu (Journal of Hazardous Materials, 2024)

Review on toxicology and activity of tomato glycoalkaloids in immature tomatoes - Li-hao Wang; De-hong Tan; Xue-song Zhong; Mei-qi Jia; Xue Ke; Yu-mei Zhang; Tong Cui; Lin Shi (Food Chemistry, 2024)

Effect of vegetable oils on the thermal gel properties of PSE-like chicken breast meat protein isolate-based emulsion gels - Ke Li; Lin-Meng Wang; Bing-Bing Cui; Bo Chen; Dian-Bo Zhao; Yan-Hong Bai (Food Chemistry, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

Engineering multifunctional phase change composites enabled by dual-interpenetrating hybrid scaffold for excellent thermal conductivity and electromagnetic absorption - Boyang Hu; Hong Guo; Ying Cui; Jiaye Li; Min Cao; Weiyan Qi; Xiwei Cao; Baoan Li (Chemical Engineering Journal, 2024)

Effect of temperature step-changes and ramps on physiological and psychological responses of occupants in office buildings in summer - Angchen Jiang; Yong Cheng; Yuxin Wu; Haijiao Cui; Guojian Li; Hong Liu; Baizhan Li (Building and Environment, 2024)

Fer-mediated activation of the Ras-MAPK signaling pathway drives the proliferation, migration, and invasion of endometrial carcinoma cells - Lifan Shen; Chen Zhang; Kaiying Cui; Xin Liang; Genhai Zhu; Lan Hong (Molecular and Cellular Biochemistry, 2024)

Investigation of the Inhibitory Effects of Illicium verum Essential Oil Nanoemulsion on Fusarium proliferatum via Combined Transcriptomics and Metabolomics Analysis - Cui-Qiong Ling; Hong-Xin Liao; Jin-Rui Wen; Hong-Yan Nie; Li-Yan Zhang; Fu-Rong Xu; Yong-Xian Cheng; Xian Dong (Current Microbiology, 2024)

NLRP3 inflammasome activation triggers severe inflammatory liver injury in N, N-dimethylformamide-exposed mice - Xiu-Ning Zhang; Yan-Jing Zhang; Lin Wang; Shu-Jun Hong; Cui-Li Zhang; Xiu-Lan Zhao; Tao Zeng (Science of The Total Environment, 2024)

Synergistic analysis of lignin degrading bacterial consortium and its application in rice straw fiber film - Jinghong Wang; Wei Zhang; Chenying Wu; Yanhua Hong; Guinan Shen; Weiwei Wang; Hongzhi Tang; Kazuhiro Mochidzuki; Zongjun Cui; Aman Khan; Weidong Wang (Science of The Total Environment, 2024)

Catalytic ozonation of reverse osmosis concentrate from coking wastewater reuse by surface oxidation over Mn-Ce/γ-Al2O3: Effluent organic matter transformation and its catalytic mechanism - Rui Hu; Jia-Ying Li; Qiyi Yu; Sui-Qin Yang; Xinbo Ci; Bing Qu; Liwei Yang; Zheng-Qian Liu; Hongquan Liu; Jingjing Yang; Shiquan Sun; Yu-Hong Cui (Journal of Hazardous Materials, 2024)

Clean and efficient preparation of metallic bismuth from methane-sulfonate electrolyte in the membrane electrolysis cell - Cong Chang; Shenghai Yang; Jie Dai; Jun Li; Caiping Fu; Jingtao Cui; Weizhi Zeng; Hong Liu; Jiaqi Qi; Wei Jin; Yongming Chen (Journal of Environmental Chemical Engineering, 2024)

Integrated metabolomics and transcriptomics to study mechanisms of Paecilomyces cicadae-fermented Radix astragali in the treatment of hyperuricemia - Hong Wang; Yufan Tao; Yifang Cui; Xianming Lan; Shuyi Song; Zhonglei Zhang; Shaoping Wang; Ailin Yang; Jiayu Zhang (Food Bioscience, 2024)

Mechanistic enhancement of emulsification function in zein/pectin complex nanoparticles by short linear glucan - Wenhui Li; Qing Hong; Mingzhou Yu; Jie Cui; Ye sun; Li Mi; Yiyang Yu; Jinchi Jiang; Wenge Yang; Yonghong Hu (Food Hydrocolloids, 2024)

Degradable ZIF-8/silica carriers with accropode-like structure for enhanced foliar affinity and responsive pesticide delivery - Menghui Wan; Yuting Zhang; Tao Hong; Junyan Cui; Yanbao Zhao; Zhihua Wang (Chemical Engineering Journal, 2024)

Positron Emission Tomography Imaging of Synaptic Dysfunction in Parkinson’s Disease - Jiaqi Niu; Yan Zhong; Chentao Jin; Peili Cen; Jing Wang; Chunyi Cui; Le Xue; Xingyue Cui; Mei Tian; Hong Zhang (Neuroscience Bulletin, 2024)

A Diagnostic Model for Parkinson’s Disease Based on Anoikis-Related Genes - Yiwen Bao; Lufeng Wang; Hong Liu; Jie Yang; Fei Yu; Can Cui; Dongya Huang (Molecular Neurobiology, 2024)

ResDeepSurv: A Survival Model for Deep Neural Networks Based on Residual Blocks and Self-attention Mechanism - Yuchen Wang; Xianchun Kong; Xiao Bi; Lizhen Cui; Hong Yu; Hao Wu (Interdisciplinary Sciences: Computational Life Sciences, 2024)

The Role of Macrophages in Lung Fibrosis and the Signaling Pathway - Xingmei Wang; Jiaxu Zhou; Xinrui Li; Chang Liu; Lan Liu; Hong Cui (Cell Biochemistry and Biophysics, 2024)

Antiproliferative polycyclic polyprenylated acylphloroglucinols from Garcinia paucinervis - Cui-Cui Jia; Jing-Jing Xue; Zhan-Lin Li; Da-Hong Li; Hui-Ming Hua (Natural Product Research, 2024)

Environmental impacts of ridesplitting considering modal substitution and associations with built environment - Zhe Zhang; Kun Gao; Hong-Di He; Shaohua Cui; Liyang Hu; Qing Yu; Zhong-Ren Peng (Transportation Research Part D: Transport and Environment, 2024)

Patient-derived pathogenic microbe deposition enhances exposure risk in pediatric clinics - Wan Wang; Zongyao Qiu; Hui Li; Xiaorong Wu; Ying Cui; Lixiang Xie; Bozhen Chang; Peipei Li; Hong Zeng; Tao Ding (Science of The Total Environment, 2024)

The effects of microgravity on stem cells and the new insights it brings to tissue engineering and regenerative medicine - Hong-Yun Nie; Jun Ge; Kai-Ge Liu; Yuan Yue; Hao Li; Hai-Guan Lin; Hong-Feng Yan; Tao Zhang; Hong-Wei Sun; Jian-Wu Yang; Jin-Lian Zhou; Yan Cui (Life Sciences in Space Research, 2024)

Photoelectrochemical sensor for the detection of Escherichia coli O157:H7 based on TPA-NO2 and dual-functional polythiophene films - Xiaoqing Wang; Huiyi Chen; Jihui Zhang; Hong Zhou; Xiangying Meng; Na Wang; Yishan Fang; Bo Cui (Food Chemistry, 2024)

Nutrient runoff and leaching under various fertilizer treatments and pedogeographic conditions: A case study in tobacco (Nicotiana tabacum L.) fields of the Erhai Lake basin, China - Chen Wang; Qi Miao; Zhibiao Wei; Yingxin Guo; Junying Li; Zhiyong Fan; Yanxia Hu; Hong Zhang; Junwei Sun; Zhenling Cui (European Journal of Agronomy, 2024)

Synergistic therapy for melanoma via bioactive compounds derived metal-phenolic networks - Zhenghao Zhou; Cong Li; Shuai Cui; Shian Sun; Shaowei Zhu; Qing Yu; Ning Ding; Hao Hong; Dongzhi Yang (Chemical Engineering Journal, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Seipin Deficiency Leads to Energy Dyshomeostasis via Inducing Hypothalamic Neuroinflammation and Aberrant Expression of Neuropeptides - Wenli Cui; Hong Chen; Lingfeng Lei; Wenru Wang; Kah-Leong Lim; Chengwu Zhang; Li Lu (NeuroMolecular Medicine, 2024)

Isolation and absolute configuration of alkylpyridine alkaloids from the marine sponge Hippospongia lachne - Dong-Xue Fan; Xiang-Chao Luo; Ya-Fang Ding; Li-Yun Liu; Xin Wang; Jia-Yan Pan; Yuan-Yuan Ji; Jie Wang; Cui Li; Li-Li Hong; Hou-Wen Lin (Phytochemistry, 2024)

Synthesis and antifungal activity of 2,4-diacetylphloroglucinol analogues - Xi-Long Guo; Chun-Yan Zhao; Cui-Ping Zhang; Yi Zhu; Qing-Rong Wu; Yuan-Qing Zhou; Ya-Hong Fei; Fang Ge; Wei Shi (Phytochemistry Letters, 2024)

Machine-learning-assisted hydrogen adsorption descriptor design for bilayer MXenes - Weizhi Tian; Gongchang Ren; Yuanting Wu; Sen Lu; Yuan Huan; Tiren Peng; Peng Liu; Jiangong Sun; Hui Su; Hong Cui (Journal of Cleaner Production, 2024)

Transcriptome analysis reveals the inhibitory mechanism of phloretin on virulence expression of Staphylococcus aureus and its application in cooked chicken - Hong Li; Changzhu Li; Ce Shi; Manal Y. Sameeh; Fahad Al-Asmari; Haiying Cui; Lin Lin (International Journal of Food Microbiology, 2024)

Phosphoproteomics analysis reveals the anti-bacterial and anti-virulence mechanism of eugenol against Staphylococcus aureus and its application in meat products - Hong Li; Changzhu Li; Ce Shi; Metab Alharbi; Haiying Cui; Lin Lin (International Journal of Food Microbiology, 2024)

Arsenic disturbs neural tube closure involving AMPK/PKB-mTORC1-mediated autophagy in mice - Xiujuan Li; Gexuan Li; Shuo Cui; Yue Hou; Zelin Li; Ziyi Yan; Tingjuan Huang; Taoran Zhao; Hongkai Su; Bingrui Zhou; Juan Zhang; Ruifang Ao; et al. (Food and Chemical Toxicology, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Energy consumption prediction and household feature analysis for different residential building types using machine learning and SHAP: Toward energy-efficient buildings - Xue Cui; Minhyun Lee; Choongwan Koo; Taehoon Hong (Energy and Buildings, 2024)

Hsa-miR-877-5p Expression in Acute Ischemic Stroke Based on Bioinformatics Analysis and Clinical Validation - Si-Shuo Zhang; Ji-Wei Zhang; Kai-Xin Zhang; Wen-Qiang Cui; Hong-Wei Zhi; Hai-Tao Li; Hong-Yun Wu; Ya-Han Wang (Molecular Neurobiology, 2024)

Synthesis, antitumor evaluation and computational study of thiazolidinone derivatives of dehydroabietic acid-based B ring-fused-thiazole - Nai-Yuan Chen; Cui-Ping Li; Hong-Fei Huang (Molecular Diversity, 2024)

Prediction of transformation in the histopathological growth pattern of colorectal liver metastases after chemotherapy using CT-based radiomics - Shengcai Wei; Xinyi Gou; Yinli Zhang; Jingjing Cui; Xiaoming Liu; Nan Hong; Weiqi Sheng; Jin Cheng; Yi Wang (Clinical & Experimental Metastasis, 2024)

Field test research on anti-crack performance of basalt fiber geogrid-reinforced semi-rigid base by optical fiber strain sensor - Jianyou Yu; Jiangping Gao; Mingkai Cui; Xin Sun; Hong Zhao; Yuan He (Arabian Journal of Geosciences, 2024)

Exogenous melatonin enhanced cadmium stress tolerance of cucumber seedlings (Cucumis sativus L.) - Xin Kang; Zi-Qi Pei; Ting-Ting Xu; Cui-Yun Dong; Xue Bai; Cheng Ma; Qiao Zhu; Cai-Hong Chai; Juan Wang; Sheng Zheng; Teng-Guo Zhang (Biologia, 2024)

uw-WiFi: Small-Scale Data Collection Network-Based Underwater Internet of Things - Jifeng Zhu; Xiaohe Pan; Zheng Peng; Mengzhuo Liu; Jingqian Guo; Jun-Hong Cui (Journal of Marine Science and Engineering, 2024)
The establishment of the Underwater Internet of Things (UIoT) and the realization of interconnection between heterogeneous underwater intelligent devices are urgent global challenges. Underwater acoustic networking is the most suitable technology to achieve UIoT for medium to long ranges. This paper presents an underwater Wi-Fi network, called uw-WiFi, that utilizes a master–slave mode architecture. uw-WiFi is dedicated to solving the problem of underwater acoustic networking with limited coverage range and number of nodes. To ensure the reliability of different types of data in the network, a reliable segmentation transmission protocol based on data type is designed. Additionally, on-demand scheduling based on the reservation MAC protocol is developed to solve the channel resource sharing problem. The uw-WiFi system has undergone shallow sea tests, and the experimental results demonstrate that the uw-WiFi network is capable of achieving a network throughput of 500 bps or higher, indicating superior network performance.

miR-15b-5p promotes HgCl2-induced chicken embryo kidney cells ferroptosis by targeting β-TrCP-mediated ATF4 ubiquitin degradation - Hong-Yu Fu; Yue Li; Han Cui; Jiu-Zhi Li; Wan-Xue Xu; Xi Wang; Rui-Feng Fan (Toxicology, 2024)

Decoding PFAS contamination via Raman spectroscopy: A combined DFT and machine learning investigation - Yangxiu Chen; Yanjun Yang; Jiaheng Cui; Hong Zhang; Yiping Zhao (Journal of Hazardous Materials, 2024)

Bamboo classification based on GEDI, time-series Sentinel-2 images and whale-optimized, dual-channel DenseNet: A case study in Zhejiang province, China - Bo Wang; Hong Zhao; Xiaoyi Wang; Guanting Lyu; Kuangmin Chen; Jinfeng Xu; Guishan Cui; Liheng Zhong; Le Yu; Huabing Huang; Qinghong Sheng (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Green space and its types can attenuate the associations of PM2.5 and its components with prediabetes and diabetes—— a multicenter cross-sectional study from eastern China - Zhiqian Cui; Rubing Pan; Jintao Liu; Weizhuo Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Li Liu; Ning Wei; Rong Song; Jiajun Yuan; et al. (Environmental Research, 2024)

Enhanced hydroisomerization of n-heptane over bifunctional catalysts with highly dispersed Pd nanoparticles supported on H-Yβ composite zeolite - Yu-Hong Kang; Xiao-Qi Zhang; Juan Gao; Guang-Hui Liu; Yan-Jun Li; Yong Gao; Jin-Jun Bai; Ai-Min Wang; Xian-Yong Wei; Cui-Ying Lu (Chemical Engineering Journal, 2024)

A multifunctional interface optimization strategy for efficient Quasi-2D blue perovskite Light-Emitting diodes - Yuliang Ye; Zhou Cui; Zunxian Yang; Zhiwei Zeng; Zongyi Meng; Hongyi Hong; Songwei Ye; Zhiming Cheng; Qianting Lan; Jiaxiang Wang; Ye Chen; Hui Zhang; et al. (Chemical Engineering Journal, 2024)

Effect of SARS-CoV-2 infection in early pregnancy on placental development - Shanru Yi; Liping Wang; Mengting Wang; Wei Hong; Ben Xu; Xiaoying He; Mengtian Yang; Zhiping Wu; Beiying Wang; Guang Yang; Shijun Shen; Xinyu Cui; et al. (Science China Life Sciences, 2024)

Moored underwater docking system for resident UUVs with acoustic guidance: Design and experiment - Jingqian Guo; Mengzhuo Liu; Xiaohe Pan; Jifeng Zhu; Jun Liu; Hongli Xu; Zheng Peng; Jun-Hong Cui (Ocean Engineering, 2024)

Simulated microgravity altered the gene expression profiles and inhibited the proliferation of Kupffer cells in the early phase by downregulating LMO2 and EZH2 - Jun Ge; Yuan Yue; Hong-Yun Nie; Kai-Ge Liu; Hao Li; Hai-Guan Lin; Tao Zhang; Hong-Feng Yan; Hong-Wei Sun; Jian-Wu Yang; Jin-Lian Zhou; Yan Cui (Life Sciences in Space Research, 2024)

Beneficial effects of short-term exposure to indoor biophilic environments on psychophysiological health: Evidence from electrophysiological activity and salivary metabolomics - Zhaoming Li; Wenzhu Zhang; Jingxian Cui; Hui Liu; Hong Liu (Environmental Research, 2024)

Experimental and numerical study on dynamic behavior of laminated glass window under combustible gas explosions - Wenju Liu; Yanchao Shi; Hong Hao; Jian Cui (Engineering Structures, 2024)

Effective removing of rotifer contamination in microalgal lab-scale raceway ponds by light-induced phototaxis coupled with high-voltage pulse electroshock - Ji Hong; Mostafa Sobhi; HongJing Zheng; Xinjuan Hu; Yi Cui; Zhen Yu; Xiangru Xu; Feifei Zhu; Shuhao Huo (Bioresource Technology, 2024)

Biophilic environment with visual-olfactory stimuli contributes to psychophysiological restoration and cognitive enhancement - Zhaoming Li; Wenzhu Zhang; Jingxian Cui; Lingshan Wang; Hui Liu; Hong Liu (Building and Environment, 2024)

Stytontriterpenes A−C, three unusual oleanane-derived triterpenoids from the resin of Styrax tonkinensis as potential immunosuppressive agents in atherosclerosis - Rui-Yan Jiang; Ling-Wen Yao; Yin-Hong Lv; Zhong-Tian Guo; Fei-Fei Wang; Hong-Hua Cui; Yuan-Yuan Cheng; Feng Wang (Phytochemistry, 2024)

Characteristic chromanone acids from Calophyllum membranaceum: Determination of C-3 configuration and anti-inflammatory activity - Wei Shen; Lun Li; Qing-He Liu; Jia-Min Cui; Wei Shi; Xin-Hong Shi; Xiao-Qi Zhang; Wen-Cai Ye; Xiao-Long Hu; Hao Wang (Phytochemistry, 2024)

Thin film composite polyamide nanofiltration membranes with interlayer constructed with core-shell structured polystyrene-polyacrylamide nanospheres for antibiotics separation - Ben-Qing Huang; Hong-Guang Cui; Tian-Yun Feng; Cai-Ling Yuan; Ai-Lian Chang; Ming-Lu Shao; Chi-Fan Zhu (Journal of Water Process Engineering, 2024)

Environmental insurance and green productivity: A firm-level evidence from China - Hong-xing Wen; Ting Cui; Xiao-qing Wu; Pu-yan Nie (Journal of Cleaner Production, 2024)

Hydrogel-immobilized nanotherapeutics: Inhibition of protective autophagy to amplify STING signals for postsurgical tumor immunotherapy - Hong Wang; Weikai Sun; Dawei Zhou; Yafei Qi; Zhiliang Gao; Jiwei Cui; Dexin Yu (Chemical Engineering Journal, 2024)

Synergistic effect between Ni single atoms and Ni nanoparticles for effectively boosting sustainable co-electrolysis of CO2 and hydrazine - Min Li; Ye Hu; Wenhui Fang; Shixian Xin; Ying Wu; Yutao Cao; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2024)

Thermo-responsive liposome nano-vesicles for co-delivery of emamectin benzoate and nitenpyram with synergistic pest control - Qian Du; Xi-Quan Ding; Fei Gao; Bo Cui; Ting-Yu Wang; Fang-Yuan Chen; Long Chen; Hong-Yan Chen; Hai-Xin Cui; Yan Wang; Zhang-Hua Zeng (Chemical Engineering Journal, 2024)

Allyl methyl disulfide (AMDS) prevents N,N-dimethyl formamide-induced liver damage by suppressing oxidative stress and NLRP3 inflammasome activation - Long-Xia Li; Lin Wang; Shuo Wang; Xiu-Ning Zhang; Hong Liu; Yan-Jing Zhang; Chuan-Tao Wu; Cui-Li Zhang; Tao Zeng (Food and Chemical Toxicology, 2023)

Effects of salinity on sulfur-dominated autotrophic denitrification microorganisms: Microbial community succession, key microorganisms and response mechanisms - Zhuo-Ran Li; Xue-Ning Zhang; Hong-Cheng Wang; Hao-Yi Cheng; Ai-Jie Wang; Yan-Qing Zhang; Chong-Wei Cui; Yi-Lu Sun (Chemical Engineering Journal, 2023)

Recent advances in enzymatic properties, preparation methods, and functions of glycoside hydrolase from Bifidobacterium: a review - Yanbo Hu; Huili Hong; Jianing Zhou; Yangyang Cui; Baochun Zhang; Jun Zhao (World Journal of Microbiology and Biotechnology, 2023)

PPAR-γ promotes the polarization of rat retinal microglia to M2 phenotype by regulating the expression of CD200-CD200R1 under hypoxia - Yiyi Hong; Li Jiang; Fen Tang; Mingyuan Zhang; Ling Cui; Haibin Zhong; Fan Xu; Min Li; Changzheng Chen; Lifei Chen (Molecular Biology Reports, 2023)

Micropeptides: origins, identification, and potential role in metabolism-related diseases - Yirui Lu; Yutong Ran; Hong Li; Jiao Wen; Xiaodong Cui; Xiaoyun Zhang; Xiumei Guan; Min Cheng (Journal of Zhejiang University-SCIENCE B, 2023)

5-HT4 Receptor is Protective for MPTP-induced Parkinson’s Disease Mice Via Altering Gastrointestinal Motility or Gut Microbiota - Chun Cui; Yun Shi; Hui Hong; Yu Zhou; Chenmeng Qiao; Liping Zhao; Xuebing Jia; Weijiang Zhao; Yanqin Shen (Journal of Neuroimmune Pharmacology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

A novel approach to the automatic classification of wireline log-predicted sedimentary microfacies based on object detection - Zhong Hong; Guo-Liang Yan; Xiang-Li Cui; Gai Gao; Guang-Min Hu (Applied Geophysics, 2023)

Implementation of an Efficient Image Transmission Algorithm for Unmanned Surface Vehicles Based on Semantic Communication - Yuanming Chen; Xiaobin Hong; Bin Cui; Rongfa Peng (Journal of Marine Science and Engineering, 2023)
With the increasingly maturing technology of unmanned surface vehicles (USVs), their applications are becoming more and more widespread. In order to meet operational requirements in complex scenarios, the real-time interaction and linkage of a large amount of information is required between USVs, between USVs and mother ships, and between USVs and shore-based monitoring systems. Visual images are the main perceptual information gathered from USVs, and their efficient transmission and recognition directly affect the real-time performance of information exchange. However, poor maritime communication signals, strong channel interference, and low bandwidth pose great challenges to efficient image transmission. Traditional image transmission methods have difficulty meeting the real-time and image quality requirements of visual image transmissions from USVs. Therefore, this paper proposes an efficient method for visual image transmission from USVs based on semantic communication. A self-encoder network for semantic encoding which compresses the image into low-dimensional latent semantics through the encoding end, thereby preserving semantic information while greatly reducing the amount of data transmitted, is designed. On the other hand, a generative adversarial network is designed for semantic decoding. The decoding end decodes and reconstructs high-quality images from the semantic information transmitted through the channel, thereby improving the efficiency of image transmission. The experimental results show that the performance of the algorithm is significantly superior to traditional image transmission methods, achieving the best image quality while transmitting the minimum amount of data. Compared with the typical BPG algorithm, when the compression ratio of the proposed algorithm is 51.6% of that of the BPG algorithm, the PSNR and SSIM values are 7.6% and 5.7% higher than the BPG algorithm, respectively. And the average total time of the proposed algorithm is only 59.4% of that of the BPG algorithm.

Phytoplankton interspecific interactions modified by symbiotic fungi and bacterial metabolites under environmentally relevant hydrogen peroxide concentrations stress - Zhe Li; Hua Ma; Zhicheng Hong; Ting Zhang; Mingxing Cao; Fuyi Cui; Hans-Peter Grossart (Water Research, 2023)

Mid-Holocene pine forest expansion caused by the weakening of the East Asian winter monsoon and linked to climate change in the North Atlantic region - Jing Wu; Wei-he Ren; Qiao-yu Cui; Yu-zhen Ma; Laurent Marquer; Hong-wei Meng; Ze-yang Zhu; Guo-qiang Chu; Jia-qi Liu (Quaternary Science Reviews, 2023)

Residues of sulfoxaflor and its metabolites in floral and extrafloral nectar from Hibiscus rosa-sinensis L. (Malvaceae) with or without co-application of tebuconazole - Hong-Xia Zhou; Man-Huan Cheng; Juan-Lin Pan; Peng Cui; Yue-Qin Song; Ying Yu; Jun Cao; Hong-Guang Zha (Pesticide Biochemistry and Physiology, 2023)

The Dof transcription factor COG1 acts as a key regulator of plant biomass by promoting photosynthesis and starch accumulation - Zhuoyun Wei; Haoyong Zhang; Meng Fang; Shuyuan Lin; Mingsong Zhu; Yuxiu Li; Limin Jiang; Tianliang Cui; Yanwei Cui; Hong Kui; Liang Peng; Xiaoping Gou; et al. (Molecular Plant, 2023)

Heating performance, exergy, and economic analysis of a heat pump drying system with an independent operating ability for drying shiitake mushrooms - Taiyang Xiao; Rong Feng; Xingchen Zhao; Yang Han; Machao Guo; Jiahui Wu; Hong Cui (Journal of Cleaner Production, 2023)

T4PPVB-COP composite-driven innovative electrochemiluminescence aptasensor for ultra-sensitive detection of chlorpyrifos - Yanping Li; Qiong Hu; Jihui Zhang; Hong Zhou; Na Wang; Yishan Fang; Bo Cui (Food Chemistry, 2023)

Identification of circRNAs and circRNA-mRNA network of Epinephelus coioides during Singapore grouper iridovirus infection - Yi-Jie Cai; Wei Huang; Liang-Yuan Zhu; Yun-Xiang Lin; Cui-Fen Huang; Wen-Feng Yang; Jia-Lin Zhou; Jun-De Dong; Wei-Hua Zhou; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2023)

Enhancing biomass oxidation with carbon nitride nanosheets ring inserted on C. I. Pigment Yellow 53 photocatalysts for simultaneous CO and lactic acid production - Weikang Ling; Jiliang Ma; Zhendong Liu; Rui Cui; Junqiang Zhang; Xinze Li; Min Hong; Runcang Sun (Chemical Engineering Journal, 2023)

Retraction Note: A Fluorescent Zn(II) Coordination Polymer: Sensitive Detection of Cr2O72− in Water and Prevention Activity on the Deep Vein Thrombosis in Orthopedic Nursing - Yu Zhou; Li Cui; Yan Zhang; Yu Liu; Dai-Hong Ji (Journal of Fluorescence, 2023)

Elemental sulfur-driven autotrophic denitrification process for effective removal of nitrate in mariculture wastewater: Performance, kinetics and microbial community - Lu Wang; Jun Liu; Yongfu Li; Zhihao Liu; Long Zhang; Hong Che; Hongwu Cui; Ying Zhang (Chemosphere, 2023)

NAT10 regulates the repair of UVB-induced DNA damage and tumorigenicity - Zizhao Yang; Emma Wilkinson; Yan-Hong Cui; Haixia Li; Yu-Ying He (Toxicology and Applied Pharmacology, 2023)

Vehicle-bridge dynamic response analysis under copula-coupled wind and wave actions - Chen Guo; Bo Zhang; Hong Guo; Shengai Cui; Bing Zhu (Ocean Engineering, 2023)

Integrated MOVES model and machine learning method for prediction of CO2 and NO from light-duty gasoline vehicle - Run Liu; Hong-di He; Zhe Zhang; Cui-lin Wu; Jin-ming Yang; Xing-hang Zhu; Zhong-ren Peng (Journal of Cleaner Production, 2023)

Responses of soil biochemical and microbial properties to vegetation combinations of quarry restoration strategies in mountainous areas in China - Hui Han; Hong Yao; Cui-lan Wei; Jianjun Ma (Ecological Engineering, 2023)

Response Surface Methodology and Artificial Neural Network Modeling for the Removal of Volatile Organic Compounds in Biotrickling Filters - Tianqiu Hong; Lin Wei; Kangping Cui; Yugang Dong; Lei Luo; Tingting Zhang; Ruolan Li; Ziyue Li; Yiming Tang (Water, Air, & Soil Pollution, 2023)

Cosmogenic 10Be dating of the oldest moraine in the Hengduan Mountains - Zhigang Zhang; Jiahong Zheng; Haitao Cui; Zhijun Zhao; Xinggong Kong; Chaogang Zheng; Hong Zhang; Fei Guo; Zhiyang Chang; Xue Yuan; Mingyang Yan; Jie Zhang; et al. (Science China Earth Sciences, 2023)

The combined effects of North Atlantic Oscillation and Western Pacific teleconnection on winter temperature in Eastern Asia during 1980–2021 - Ziqun Zhang; Hongyan Cui; Baoxu Chen; Hong Cai; Pin Li (Acta Oceanologica Sinica, 2023)

Biodegradability enhancement of waste lubricating oil regeneration wastewater using electrocoagulation pretreatment - Li-li Shan; Zhao Tan; Yu Chen; Ruo-shan Wang; Meng Zhang; Chang-long Pang; Yu-Hong Cui; Zhi-min Liao; Hong-qiang Ma; Ze-bing Zhu (Environmental Science and Pollution Research, 2023)

Three new compounds with their anti-glioma effects from the roots of Arnebia guttata Bunge - Yu-Mei Yan; Lin-Jun Zou; Min-Hui Li; Zhao-Cui Sun; Min Zhang; Xu-Dong Xu; Chun-Hong Zhang (Natural Product Research, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Real-time missing seedling counting in paddy fields based on lightweight network and tracking-by-detection algorithm - Jinrong Cui; Hong Zheng; Zhiwei Zeng; Yuling Yang; Ruijun Ma; Yuyuan Tian; Jianwei Tan; Xiao Feng; Long Qi (Computers and Electronics in Agriculture, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Microgravity stress alters bacterial community assembly and co-occurrence networks during wheat seed germination - Jingjing Cui; Zhihao Yi; Dengbo Chen; Yuming Fu; Hong Liu (Science of The Total Environment, 2023)

Vegetation structural shift tells environmental changes on the Tibetan Plateau over 40 years - Yanfen Wang; Kai Xue; Ronghai Hu; Boyang Ding; Hong Zeng; Ruijin Li; Bin Xu; Zhe Pang; Xiaoning Song; Congjia Li; Jianqing Du; Xiuchun Yang; et al. (Science Bulletin, 2023)

“Mini-community” simulation revealed the differences of endophytic fungal communities between the above- and below-ground tissues of Ephedra sinica Stapf - Xi Liu; Jin-Long Cui; Zhong-Ya Zhou; Zong-Bao Zhang; Xuan-Ge Cui; Bo Han; Jun-Hong Wang; Meng-Liang Wang; Yi-Min Li (Fungal Biology, 2023)

Ultra-high output hybrid nanogenerator for self-powered smart mariculture monitoring and warning system - Liqiang Liu; Jun Li; Zhengxin Guan; Leilei Zhao; Zhiyu Tian; Shouchuang Jia; Hongxin Hong; Zeyu He; Haiyang Wen; Ruiyuan Huang; Hui Cui; Wei Ou-Yang; et al. (Chemical Engineering Journal, 2023)

Copper Azide-based Complexes without Repulsive Steric Clashes between Azides for Advanced Primary Explosives - Yun-Fan Yan; Qian-You Wang; Meng Cui; Hong-Yi Bian; Yong-Fang Han; Jian-Gang Xu; Fa-Kun Zheng; Guo-Cong Guo (Chemical Engineering Journal, 2023)

Orally Induced High Serum Level of Trimethylamine N-oxide Worsened Glial Reaction and Neuroinflammation on MPTP-Induced Acute Parkinson’s Disease Model Mice - Chen-Meng Qiao; Wei Quan; Yu Zhou; Gu-Yu Niu; Hui Hong; Jian Wu; Li-Ping Zhao; Ting Li; Chun Cui; Wei-Jiang Zhao; Yan-Qin Shen (Molecular Neurobiology, 2023)

Molybdenum-Induced Apoptosis of Splenocytes and Thymocytes and Changes of Peripheral Blood in Sheep - Shu-gang Cui; Yu-ling Zhang; Hong-wei Guo; Bian-hua Zhou; Er-jie Tian; Jing Zhao; Lin Lin; Hong‑wei Wang (Biological Trace Element Research, 2023)

A Distributed Intelligent Buoy System for Tracking Underwater Vehicles - Mengzhuo Liu; Jifeng Zhu; Xiaohe Pan; Guolin Wang; Jun Liu; Zheng Peng; Jun-Hong Cui (Journal of Marine Science and Engineering, 2023)
Underwater vehicles play a crucial role in various underwater applications, such as data collection in underwater sensor networks, target detection and tracking, and underwater pipeline monitoring. Real-time acquisition of their states, particularly their location and velocity, is vital for their operation and navigation. Consequently, the development of a remote tracking system to monitor these states is essential. In this paper, we propose a system that can track the underwater vehicle’s location and velocity. We take a systematic approach that encompasses the system architecture, system composition, signal processing, and mobility state estimation. We present the system architecture and define its components, along with their relationships and interfaces. The beacon signal employed in the system features dual-hyperbolic-frequency-modulated (HFM) waveform and an OFDM symbol with cyclic prefix (CP). Based on this beacon signal, we demonstrate how signal processing techniques are utilized to precisely determine the time of arrival and reduce false alarm rates in underwater acoustic channels affected by impulsive noise. Additionally, we explain how the CP-OFDM symbol is used to measure the Doppler scaling factor and transmit essential information for localization and velocity estimation purposes. Utilizing the measurements obtained through signal processing, least squares estimators are used for estimating both the location and velocity. To validate the effectiveness of our approach, we implement the system and conduct field trials. Two separate experiments were conducted in which the diagonal lengths of the square topology were designed to be 1000 m and 800 m. The minimum/maximum root mean square error of localization in the first and second experiment is 2.36/2.91 m and 1.47/2.49 m, respectively. And the minimum/maximum root mean square error of velocity estimation in the first and second experiment is 0.16/0.47 m/s and 0.21/0.76 m/s, respectively. Results confirm the effectiveness of the proposed method in estimating the location and velocity of the underwater vehicle. Overall, this paper provides a practical and effective design of a system to track the location and velocity of underwater vehicles. By leveraging the proposed system, signal processing, and mobility state estimation methods, our work offers a systematic solution. And, the successful field experiment serves as evidence of the feasibility and effectiveness of the proposed system, making it a valuable contribution to the field of tracking underwater vehicles.

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

The characteristics of CDOM structural composition and the effect on indirect photodegradation of sulfamerazine - Ying Bai; Zhengguo Cui; Dongsheng Ding; Chenfei Hong; Hongwu Cui; Qingjing Hu; Mingying Zhou; Keming Qu (Science of The Total Environment, 2023)

Promotion or hindrance? Exploring the bidirectional causality between geopolitical risk and green bonds from an energy perspective - Kai-Hua Wang; Cui-Ping Wen; Hong-Wen Liu; Lu Liu (Resources Policy, 2023)

A novel strategy to control Pseudomonas syringae through inhibition of type III secretion system - Lu-Lu He; Xin Wang; Dylan O'Neill Rothenberg; Xiaoli Xu; Hai-Hong Wang; Xin Deng; Zi-Ning Cui (Pesticide Biochemistry and Physiology, 2023)

A complete assembly of the rice Nipponbare reference genome - Lianguang Shang; Wenchuang He; Tianyi Wang; Yingxue Yang; Qiang Xu; Xianjia Zhao; Longbo Yang; Hong Zhang; Xiaoxia Li; Yang Lv; Wu Chen; Shuo Cao; et al. (Molecular Plant, 2023)

Combined effect of simulated microgravity and low-dose ionizing radiation on structure and antibiotic resistance of a synthetic community model of bacteria isolated from spacecraft assembly room - Yueying Lu; Yifan Fu; Letian Chen; Jingjing Cui; Min Huang; Yuming Fu; Hong Liu (Life Sciences in Space Research, 2023)

Optimization of near-infrared reflectance models in determining flavonoid composition of okra (Abelmoschus esculentus L.) pods - Yutong Cui; Jianguo Wu; Yingying Chen; Fangchen Ji; Xinyuan Li; Jing Yang; Seung-Beom Hong; Zhujun Zhu; Yunxiang Zang (Food Chemistry, 2023)

Understanding the digestibility of wheat starch- caffeic acid complexes prepared by hot-extrusion 3D printing technology - Xin-Ru Cui; Yu-Sheng Wang; Yan Chen; Hong-Yan Mu; Hai-Hua Chen (Food Hydrocolloids, 2023)

Fabrication of modified electrode by reduced graphene oxide (rGO) and polyaniline (PANI) for enhancing azo dye decolorization in bio-electrochemical systems (BESs) - Ai-Hong Chen; Yue-Jia Yang; Shuai Wang; Li-Ming Yang; Xue-Yun Gao; Dan Cui (Environmental Research, 2023)

Evaluation of the respective contribution of anode and cathode for triclosan degradation in a bioelectrochemical system - Min-Hua Cui; Qian Zhang; John Justo Ambuchi; Lan-Ying Liu; Lei Chen; Shi-Ming Niu; Chao Zhang; Hong-Bo Liu; Chao Tie; Xue-Juan Bi; He Liu; Ai-Jie Wang (Bioresource Technology, 2023)

The potential oncogenic effect of tissue-specific expression of JC polyoma T antigen in digestive epithelial cells - Hua-chuan Zheng; Hang Xue; Hong-zhi Sun; Wen-jing Yun; Zheng-guo Cui (Transgenic Research, 2023)
JC polyoma virus (JCPyV), a ubiquitous polyoma virus that commonly infects people, is identified as the etiologic factor for progressive multifocal leukoencephalopathy and has been closely linked to various human cancers. Transgenic mice of CAG-loxp-Laz-loxp T antigen were established. T-antigen expression was specifically activated in gastroenterological target cells with a LacZ deletion using a cre-loxp system. Gastric poorly-differentiated carcinoma was observed in T antigen-activated mice using K19-cre (stem-like cells) and PGC-cre (chief cells), but not Atp4b-cre (parietal cells) or Capn8-cre (pit cells) mice. Spontaneous hepatocellular and colorectal cancers developed in Alb-cre (hepatocytes)/T antigen and villin-cre (intestinal cells)/T antigen transgenic mice respectively. Gastric, colorectal, and breast cancers were observed in PGC-cre/T antigen mice. Pancreatic insulinoma and ductal adenocarcinoma, gastric adenoma, and duodenal cancer were detected in Pdx1-cre/T antigen mice. Alternative splicing of T antigen mRNA occurred in all target organs of these transgenic mice. Our findings suggest that JCPyV T antigen might contribute to gastroenterological carcinogenesis with respect to cell specificity. Such spontaneous tumor models provide good tools for investigating the oncogenic roles of T antigen in cancers of the digestive system.

Loss of swallow tail sign on susceptibility-weighted imaging in neurosyphilis mimicking Alzheimer’s disease: a case report - Xiao-Li Cui; Shen Liu; Yi-Ming Zhang; Hong-Dong Zhao; Jian-Quan Shi (Acta Neurologica Belgica, 2023)

Long-term exposure to arsenic in drinking water leads to myocardial damage by oxidative stress and reduction in NO - Yi-Xin Cui; Lu Dong; Meng Zhang; Yi-Nan Liu; Yong-Hui Chen; Ming-Zhao Jia; Kun-Pan Chen; Hui Wang; Ya-Wen Shi; Tian-You Ma; Jing-Hong Chen (Toxicology, 2023)

Characteristics and emissions of isoprene and other non-methane hydrocarbons in the Northwest Pacific Ocean and responses to atmospheric aerosol deposition - Ying-Cui Wu; Xu-Xu Gao; Hong-Hai Zhang; Yong-Zheng Liu; Jian Wang; Feng Xu; Gui-Ling Zhang; Zhao-Hui Chen (Science of The Total Environment, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

Insight into micropollutant abatement during ultraviolet light-emitting diode combined electrochemical process: Reaction mechanism, contributions of reactive species and degradation routes - Rui Hu; Sui-Qin Yang; Jia-Ying Li; Fengyi Sun; Zheng-Qian Liu; Jingjing Yang; Yu-Hong Cui; Beiping Zhang (Science of The Total Environment, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)

Rice genotypes and root-associated niches shifted bacterial community in response to pollution of di-(2-ethylhexyl) phthalate (DEHP) for promoting DEHP removal - Cui-Lan Zhu; Hui-Xiong Lü; Yu-Hong Huang; Ji-liang Cheng; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

Use of nano titanium hydroxide and nano zirconium hydroxide fixed filter paper for rapid detection of Staphylococcus aureus in dairy products by PCR without pre-enrichment - Chun Wang; Ruohong Zhang; Xiaofang Wang; Rui Xu; Hejing Yan; Xiaoran Li; Shaojun Liu; Shuren Yin; Hong Yao; Yang Yang; Shenghui Cui; Yunchang Guo (Food Control, 2023)

Vancomycin Pretreatment on MPTP-Induced Parkinson’s Disease Mice Exerts Neuroprotection by Suppressing Inflammation Both in Brain and Gut - Chun Cui; Hui Hong; Yun Shi; Yu Zhou; Chen-Meng Qiao; Wei-Jiang Zhao; Li-Ping Zhao; Jian Wu; Wei Quan; Gu-Yu Niu; Yi-Bo Wu; Chao-Sheng Li; et al. (Journal of Neuroimmune Pharmacology, 2023)

Recycling sewage sludge into ceramic materials: A review - Haobo Mao; Yingyi Zhang; Hong Wang; Kunkun Cui; Laihao Yu; Tianbiao Tan (Environmental Chemistry Letters, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Colonic mechanism of serum NAD+ depletion induced by DEHP during pregnancy - Yun Hong; Xia Ning; Yue-yue Liang; Xiao-lu Li; Ya Cui; Wei Wu; Yang Cai; Shuai Zhao; Meng Zhu; Tian-xiao Zhong; Hua Wang; De-xiang Xu; et al. (Science of The Total Environment, 2023)

Behaviour of reinforced mortarless interlocking brick wall under cyclic loading - Guanyu Xie; Xihong Zhang; Hong Hao; Tingwei Shi; Liuliang Cui; Joyis Thomas (Engineering Structures, 2023)

Distribution characteristics and environmental effects of non-methane hydrocarbons in the East China Sea - Wen-Zhu Qiao; Ying-Cui Wu; Ping Wang; Jian Wang; Li-Min Zhou; Si-Tong Li; Hong-Hai Zhang (Continental Shelf Research, 2023)

Molecular mechanism of adsorbing triclocarban by the activated sludge in wastewater treatment systems - Hao Wang; Hanlin Cui; Xiaodan Ma; Carolyn R. Cornell; Liying Zhang; Yijun Ren; Minghan Li; Ying Liu; Shu-Hong Gao; Zhiling Li; Ai-Jie Wang; Jizhong Zhou; et al. (Chemical Engineering Journal, 2023)

Enzymatic hydrolysis lignin dissolution and low-temperature solvolysis in ethylene glycol - Yushuai Sang; Yuhan Ma; Gen Li; Kai Cui; Mingze Yang; Hong Chen; Yongdan Li (Chemical Engineering Journal, 2023)

The effect of episodic foresight on intertemporal decision-making: the role of future self-continuity and perceived control - Hong-Yue Sun; Yuan-Ping Jiang; Xin Wang; Li-Ying Cui; Hong-Mei Sun (Cognitive Processing, 2023)

A uw-Cellular Network: Design, Implementation and Experiments - Jifeng Zhu; Xiaohe Pan; Zheng Peng; Mengzhuo Liu; Jingqian Guo; Tong Zhang; Yu Gou; Jun-Hong Cui (Journal of Marine Science and Engineering, 2023)
The most significant increase of current task is in the desire for operational flexibility and agility in large-scale underwater network application scenarios in recent years. In order to address the challenging problems in Underwater Wireless Sensor Networks (UWSNs), we propose a large-scale UWSN based on the cellular network architecture called Underwater Cellular (uw-Cellular) network. It is designed especially for application scenarios where a large number of both fixed and mobile network nodes exist in a wide area to monitor the underwater environment. We also design protocols in each network layer in order to ensure reasonable channel sharing, data forwarding path selection and data reliability. The purpose of the simulation study we implement is to evaluate the performance of the CLA routing strategy compared to the VBF and the MFLOOD protocols in the uw-Cellular network. We also deploy a twenty-node uw-Cellular network in the real-world environment as the field case study. The experimental results showed that the Data Rate between any nodes could reach above 500 bps, and the network Average Throughput was no less than 550 bps under various load situations.

A general way to manipulate electrical conductivity of graphene - Liqing Chen; Nian Li; Xinling Yu; Shudong Zhang; Cui Liu; Yanping Song; Zhao Li; Shuai Han; Wenbo Wang; Pengzhan Yang; Na Hong; Sarmad Ali; et al. (Chemical Engineering Journal, 2023)

To what extent the traffic restriction policies can improve its air quality? An inspiration from COVID-19 - Si-qing Xu; Hong-di He; Ming-ke Yang; Cui-lin Wu; Xing-hang Zhu; Zhong-ren Peng; Yuya Sasaki; Kenji Doi; Shinji Shimojo (Stochastic Environmental Research and Risk Assessment, 2023)

Identification of rocky ledge on steep, high slopes based on UAV photogrammetry - Xuan-hao Wang; Wei Cui; Gui-ke Zhang; Hong Yang (Natural Hazards, 2023)

Chinese young people’s perceptions and preferences with regard to various edible urban plants - Wenzhu Zhang; Zhaoming Li; Jingxian Cui; Lingshan Wang; Hui Liu; Hong Liu (Journal of Zhejiang University-SCIENCE B, 2023)

Azospirillum Aestuarii sp. nov., a Novel Nitrogen-Fixting and Aerobic Denitrifying Bacteria Isolated from an Estuary of a Freshwater River - Can-Hai Xu; Gen Chen; Yan Liu; Wei Xiao; Xiao-Long Cui; Zhang-Gui Ding; Wei-Hong Liu; Yong-Xia Wang (Current Microbiology, 2023)

Correction to: Geographical, Sex, Age, and Seasonal Differences in Serum Manganese Status Among Chinese Adults with Hypertension - Hong Chen; Zhixin Cui; Wenhai Lu; Ping Wang; Jia Wang; Ziyi Zhou; Nan Zhang; Zhuo Wang; Tengfei Lin; Yun Song; Lishun Liu; Xiao Huang; et al. (Biological Trace Element Research, 2023)

Organics abatement and recovery from wastewater by a polymerization-based electrochemically assisted persulfate process: Promotion effect of chloride ion and its mechanism - Sui-Qin Yang; Zheng-Qian Liu; Yu-Hong Cui; Ming-Kui Wang (Journal of Hazardous Materials, 2023)

One-step synthesis of aldehyde-functionalized dual-emissive carbon dots for ratiometric fluorescence detection of bisulfite in food samples - Cui Cui Deng; Zi Yi Xu; Zhe Sun; Jia Hao Xie; Hong Qun Luo; Nian Bing Li (Food Chemistry, 2023)

A hybrid deep learning model for regional O3 and NO2 concentrations prediction based on spatiotemporal dependencies in air quality monitoring network - Cui-lin Wu; Hong-di He; Rui-feng Song; Xing-hang Zhu; Zhong-ren Peng; Qing-yan Fu; Jun Pan (Environmental Pollution, 2023)

SecReT6 update: a comprehensive resource of bacterial Type VI Secretion Systems - Jianfeng Zhang; Jiahao Guan; Meng Wang; Gang Li; Marko Djordjevic; Cui Tai; Hui Wang; Zixin Deng; Zhaoyan Chen; Hong-Yu Ou (Science China Life Sciences, 2023)

The real-time detection of acupuncture-induced extracellular ATP mobilization in acupoints and exploration of its role in acupuncture analgesia - Wei-Min Zuo; Yu-Jia Li; Kai-Yu Cui; Dan Shen; Di Zhang; Ya-Wen Zheng; Meng Huang; Yong Wu; Xue-Yong Shen; Li-Na Wang; Guang-Hong Ding (Purinergic Signalling, 2023)

A review: structure–activity relationship between saponins and cellular immunity - Xuetao Cui; Xumin Ma; Chunhai Li; Hong Meng; Chunchao Han (Molecular Biology Reports, 2023)

Human milk-derived extracellular vesicles alleviate high fat diet-induced non-alcoholic fatty liver disease in mice - Xue Jiang; Yangyang Wu; Hong Zhong; Xiaoxiao Zhang; Xingzhen Sun; Li Liu; Xianwei Cui; Xia Chi; Chenbo Ji (Molecular Biology Reports, 2023)

Recent advances in application of heterogeneous electro-Fenton catalysts for degrading organic contaminants in water - Wenjing Chen; Danlian Huang; Cui Lai; Yukui Fu; Wenfang Chen; Haoyang Ye; Huan Yi; Bisheng Li; Ling Li; Fanzhi Qin; Hong Qin; Lei Qin (Environmental Science and Pollution Research, 2023)

Ecological toxicity of Cd, Pb, Zn, Hg and regulation mechanism in Solanum nigrum L. - Rui Zhao; Xiufeng Cao; Xinxin Li; Tao Li; Hong Zhang; Xiaowei Cui; Zhaojie Cui (Chemosphere, 2023)

Roles of substrates in removing antibiotics and antibiotic resistance genes in constructed wetlands: A review - Erping Cui; Zhenchao Zhou; Feng Gao; Hong Chen; Jianan Li (Science of The Total Environment, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Adaptation of bacterial community in maize rhizosphere for enhancing dissipation of phthalic acid esters in agricultural soil - Yu-Hong Huang; Yu-Jie Yang; Xiaolian Wu; Cui-Lan Zhu; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2023)

Human platelet mitochondria improve the mitochondrial and cardiac function of donor heart - Zhi Jun Lin; Soomin Kim; Hui Xing Cui; Kyuboem Han; Hong Kyu Lee; Chun-Hyung Kim; Young Cheol Kang; Yin Hua Zhang (Pflügers Archiv - European Journal of Physiology, 2023)

Effect of biochar incorporation on phosphorus supplementation and availability in soil: a review - Yangxiaoxiao Shi; Yuanchun Yu; E Chang; Ruhai Wang; Zhineng Hong; Jiaqi Cui; Feng Zhang; Jun Jiang; Renkou Xu (Journal of Soils and Sediments, 2023)

The age of onset and cognitive impairment at the early stage of schizophrenia - Yi Yin; Shuangshuang Li; Jinghui Tong; Junchao Huang; Baopeng Tian; Song Chen; Yimin Cui; Shuping Tan; Zhiren Wang; Fude Yang; Yongsheng Tong; L. Elliot Hong; et al. (Cognitive Neurodynamics, 2023)

Experimental Inactivation of Microalgae in Marine Ballast Water by Microbubbles Generated through Hydrodynamic Cavitation - Baojun Wang; Hao Lu; Hongpeng Zhang; Wei Li; Jiaju Hong; Mingsheng Cui (Journal of Marine Science and Engineering, 2023)
This paper presents a novel approach to microbubble technology for the treatment of aquatic invasive organisms in ship ballast water. The microbubbles are produced by hydrodynamic cavitation with a sudden and dramatic water pressure drop. The air and ozone microbubbles, respectively, verified the bioavailability of ship ballast water treatment using marine microalgae as an indicator. Besides the effects of an ozone injection dose, the morphological changes of cells and the effluent toxicity were investigated. Compared with the ozone microbubble treatment, the inactivation of marine microalgae by air microbubbles required a long treatment time. In the storage experiment, it was found that air microbubbles did not inhibit the growth of microalgae cells, and that the injection of active matter such as ozone was still necessary to ensure the validity of biological invasion. However, even with very low doses of ozone, the inactivation effect of ozone microbubbles was still very evident. Overall, it helps to minimize the use of active matter to reduce the toxicity of treated water, and this has the capability to develop into an environmentally acceptable and practical ballast water treatment technology.

An Underwater Wet-Mateable Electrical Connector with Dual-Bladder Pressure-Balanced Oil-Filled (PBOF) Technology - Wentao Song; Cuibo Yang; Weicheng Cui; Changhui Song; Ping Yang; Jin Hong; Yi Lei; Qimeng Liu; Zhenhua Wang (Journal of Marine Science and Engineering, 2023)
Underwater wet-mateable connectors have been widely used to reduce the cost and the time of installation, maintenance and reconfiguration in many fields, such as the oil and gas (O&G) industry, offshore renewable energy (ORE), and undersea observatories. In the past few years, the authors’ group has made some efforts in developing wet-mateable connectors. This paper presents a methodology for designing and testing a wet-mateable electrical connector. First, an innovative wet-mateable electrical connector with dual-bladder pressure-balanced oil-filled (PBOF) technology is proposed. Second, the generalized equations of differential pressure are derived. Then, a procedure of thermal-electric-structure (TES) coupling simulation is proposed, and a series of finite element analysis (FEA) involving coupled multi-field problems is conducted, including thermal-electric coupling analysis, static structural analysis, and dynamic analysis. Finally, a prototype of the proposed connector is developed successfully, and its electrical performance is verified by the online test in a hydrostatic pressure environment with an ocean depth of 3000 m, which has reached the leading level in China. This paper is the first discloser on wet-mateable connectors in the aspects of design, theory, simulation and testing, which might be helpful to many ocean scientists in developing countries who are technically blocked or could not afford the high cost.

EMX2OS targeting IGF2BP1 represses Wilms’ tumour stemness, epithelial–mesenchymal transition and metastasis - Hong-Mei Zhang; Ming-Yu Cui; Zhi-Hong Chen (Journal of Genetics, 2023)

E2F4 regulates cell cycle to mediate embryonic development in pigs - Wen-Jie Jiang; Ming-Hong Sun; Xiao-Han Li; Song-Hee Lee; Geun Heo; Dongjie Zhou; Xiang-Shun Cui (Theriogenology, 2023)

Joint role of land cover types and microbial processing on molecular composition of dissolved organic matter in inland lakes - Zhicheng Hong; Hua Ma; Ting Zhang; Qianru Wang; Yilin Chang; Yingyue Song; Zhe Li; Fuyi Cui (Science of The Total Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Optimal local skin temperatures for mean skin temperature estimation and thermal comfort prediction of seated person in thermally stratified environments - Yuxin Wu; Zixuan Zhang; Hong Liu; Haijiao Cui; Yong Cheng (Journal of Thermal Biology, 2023)

Impact of air pollutants on influenza-like illness outpatient visits under urbanization process in the sub-center of Beijing, China - Zhong-Song Zhang; Lu Xi; Li-Li Yang; Xin-Yao Lian; Juan Du; Yan Cui; Hong-Jun Li; Wan-Xue Zhang; Chao Wang; Bei Liu; Yan-Na Yang; Fuqiang Cui; et al. (International Journal of Hygiene and Environmental Health, 2023)

Carbon capture and storage technology by steel-making slags: Recent progress and future challenges - Yingyi Zhang; Laihao Yu; Kunkun Cui; Hong Wang; Tao Fu (Chemical Engineering Journal, 2023)

High performance carbon dioxide electroreduction in ionic liquids with in situ shell-isolated nanoparticle-enhanced Raman spectroscopy - Ye Hu; Zhongdong Gan; Shixian Xin; Wenhui Fang; Min Li; Yanlei Wang; Wei Cui; Hong Zhao; Zengxi Li; Xiangping Zhang (Chemical Engineering Journal, 2023)

Passivation of positively charged cationic defects in perovskite with nitrogen-donor crown ether enabling efficient perovskite solar cells - Yuxuan Yang; Tao Zhao; Ming-Hua Li; Xiaoxue Wu; Mingyue Han; Shih-Chi Yang; Qiaoling Xu; Lede Xian; Xiang Chi; Ning-Jiu Zhao; Hong Cui; Sihan Li; et al. (Chemical Engineering Journal, 2023)

Geographical, Sex, Age, and Seasonal Differences in Serum Manganese Status Among Chinese Adults with Hypertension - Hong Chen; Zhixin Cui; Wenhai Lu; Ping Wang; Jia Wang; Ziyi Zhou; Nan Zhang; Zhuo Wang; Tengfei Lin; Yun Song; Lishun Liu; Xiao Huang; et al. (Biological Trace Element Research, 2023)

Rose Bengal inhibits β-amyloid oligomers-induced tau hyperphosphorylation via acting on Akt and CDK5 kinases - Chen-Ye Mou; Yan-Fei Xie; Jia-Xin Wei; Qi-Yao Wang; Jing-Yang Le; Yong-Jie Bao; Pan-Pan Zhang; Yue-Chun Mao; Xing-Han Huang; Han-Bo Pan; C. Benjamin Naman; Lin Liu; et al. (Psychopharmacology, 2022)

LncRNA RMRP Contributes to the Development and Progression of Spinal Cord Injury by Regulating miR-766-5p/FAM83A Axis - Hongxiang Hong; Guanhua Xu; JiaJia Chen; Jinlong Zhang; Chu Chen; Chunshuai Wu; Jiawei Jiang; Zhiming Cui (Molecular Neurobiology, 2022)

Cumulative risk assessment of dietary exposure to phthalates in pregnant women in Beijing, China - Danping Shan; Tao Zhang; Ludi Li; Yuqing Sun; Di Wang; Yingzi Li; Zheng Yang; Kanglong Cui; Shaowei Wu; Lei Jin; Bo Hong; Xuejun Shang; et al. (Environmental Science and Pollution Research, 2022)

Control, Treatment and Restoration of Contaminated Soils - Hong-Bo Li; Changsheng Qu; Xinyi Cui; Yang Song; Chao Wang; Cheng Gu (Bulletin of Environmental Contamination and Toxicology, 2022)

Screening for SH3TC2 variants in Charcot–Marie–Tooth disease in a cohort of Chinese patients - Bo Sun; Zheng-Qing He; Yan-Ran Li; Jiong-Ming Bai; Hao-Ran Wang; Hong-Fen Wang; Fang Cui; Fei Yang; Xu-Sheng Huang (Acta Neurologica Belgica, 2022)

Quantitative analysis of lake-cooling effect in Hefei City, China, based on multispectral remote sensing and its response to urban expansion - Xuening Lin; Yuhuan Cui; Shuang Hao; Hong Hong; Man Zhang; Jingdong Zhang; Ruonan Li; Mengyu Liu (Environmental Science and Pollution Research, 2022)

Two new species of Amanita section Amanita from Central China - Yu-Ting Su; Qing Cai; Wei-Qiang Qin; Yang-Yang Cui; Zuo-Hong Chen; Zhu L. Yang (Mycological Progress, 2022)

Fine mapping of the tiller inhibition gene TIN5 in Triticum urartu - Yaoqi Si; Qiao Lu; Shuiquan Tian; Jianqing Niu; Man Cui; Xiaolin Liu; Qiang Gao; Xiaoli Shi; Hong-Qing Ling; Shusong Zheng (Theoretical and Applied Genetics, 2022)

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Simulated microgravity shapes the endophytic bacterial community by affecting wheat root metabolism - Jingjing Cui; Zhihao Yi; Yuming Fu; Hong Liu (Environmental Microbiology, 2022)
Summary To improve nutrient utilization and pathogenic resistance of plants in space, it is crucial to understand the effects of microgravity on the plant root microbiome. However, the finer details of whether and how microgravity affects the root microbiome remain unclear. Here, we found that simulated microgravity elicits no significant changes in fungal community composition and diversity, whether rhizosphere or endophytic. However, simulated microgravity caused a significant change in the composition and diversity of endophytic bacteria of wheat seedlings, but not in rhizosphere bacteria. The alteration of endophytic bacterial communities demonstrates that wheat seedlings adopt strategies to recruit additional endophytic Enterobacteriaceae and increase the stability of the endophytic bacterial network to respond to the challenge of simulated microgravity. Furthermore, our results also suggest that the corresponding changes in endophytic bacteria under simulated microgravity are closely related to a significant decrease in metabolites of the host's carbon metabolism, flavonoid biosynthesis, benzoxazinoid biosynthesis, and tryptophan metabolism pathways. Our findings reveal details important to our understanding of the impact of gravity on the microbial community of plant seedlings and the theoretical basis for manipulation of microorganisms to ensure efficient plant production in space.

Research on Multi-Ship Target Detection and Tracking Method Based on Camera in Complex Scenes - Xiaobin Hong; Bin Cui; Weiguo Chen; Yinhui Rao; Yuanming Chen (Journal of Marine Science and Engineering, 2022)
Aiming at the problem that multi-ship target detection and tracking based on cameras is difficult to meet the accuracy and speed requirements at the same time in some complex scenes, an improved YOLOv4 algorithm is proposed, which simplified the network of the feature extraction layer to obtain more shallow feature information and avoid the disappearance of small ship target features, and uses the residual network to replace the continuous convolution operation to solve the problems of network degradation and gradient disappearance. In addition, a nonlinear target tracking model based on the UKF method is constructed to solve the problem of low real-time performance and low precision in multi-ship target tracking. Multi-ship target detection and tracking experiments were carried out in many scenes with large differences in ship sizes, strong background interference, tilted images, backlight, insufficient illumination, and rain. Experimental results show that the average precision of the detection algorithm of this paper is 0.945, and the processing speed is about 34.5 frame per second, where the real-time performance is much better than other algorithms while maintaining high precision. Furthermore, the multiple object tracking accuracy (MOTA) and the multiple object tracking precision (MOTP) of this paper algorithm are 76.4 and 80.6, respectively, which are both better than other algorithms. The method proposed in this paper can realize the ship target detection and tracking well, with less missing detection and false detection, and also has good accuracy and real-time performance. The experimental results provide a valuable theoretical reference for the further practical application of the method.

Pelagic cyanobacterial nitrogen fixation in lakes and ponds of different latitudinal zones - Yan Li; Ye-Xin Yu; Shuo-Nan Ma; Rui-Ting Qiao; Yong-De Cui; Hai-Jun Wang; Hong-Zhu Wang (Aquatic Sciences, 2022)

Remarkable enhancement of bleomycin production through precise amplification of its biosynthetic gene cluster in Streptomyces verticillus - Hong Li; Wenyan Gao; Yifan Cui; Yuanyuan Pan; Gang Liu (Science China Life Sciences, 2022)

Different Surface Appearances Caused by Unbalanced Mn2+ Accumulation in Gallstones Consisting of Cholesterol and CaCO3 Obtained from a Patient After Cholecystectomy - Da-Yong Lu; Jin Zhang; Qiao-Li Liu; Hong-Guang Wang; Meng Cui (Biological Trace Element Research, 2022)

Comment on “Relationship of Circulating Copper Level with Gestational Diabetes Mellitus: a Meta-analysis and Systemic Review” - Shu-ping Li; Xiao-ping Zhang; Xin-hong Cui; Li-juan Zhao; Yan-jun Rong (Biological Trace Element Research, 2022)

Landslides triggered by the 1970 Ms 7.7 Tonghai earthquake in Yunnan, China: an inventory, distribution characteristics, and tectonic significance - Yu-long Cui; Jun-hong Hu; Chong Xu; Hai-bo Miao; Jun Zheng (Journal of Mountain Science, 2022)

Stochastic modelling of the pulse-like near-fault ground motions with time-frequency representation - Y. X. Liu; X. Z. Cui; H. P. Hong (Journal of Seismology, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Comparative Assessment and Parametric Optimisation of Large Marine Two-Stroke Engines with Exhaust Gas Recirculation and Alternative Turbocharging Systems - Daoyi Lu; Gerasimos Theotokatos; Jundong Zhang; Hong Zeng; Keying Cui (Journal of Marine Science and Engineering, 2022)
Although the exhaust gas recirculation (EGR) technology has been proven effective to decrease the marine engine’s nitrogen oxides (NOx) emissions, it is associated with a considerable fuel consumption increase and challenges to the engine–turbocharger matching. This study aims to parametrically optimise the EGR and turbocharging system settings of a large marine two-stroke engine with the objective of obtaining the highest engine efficiency whilst ensuring compliance with the prevailing NOx emissions limits. Two typical configurations of the investigated engine (baseline and alternative) are modelled in the GT-SUITE software. Parametric simulations are performed with EGR rates up to 40% along with cylinder bypass rates up to 50%, and the simulation results are analysed to quantify the impact of the engine operation with EGR on the performance and NOx emissions parameters. For the baseline engine configuration, the EGR rate increase considerably deteriorates the brake specific fuel consumption (BSFC), which is attenuated by opening the cylinder bypass valve. The optimal combinations of the EGR and cylinder bypass rates for each operating point are identified for both configurations. Following the comparative assessment between the two engine configurations, recommendations for the engine operating modes are proposed, leading to BSFC improvement in the region of 0.7 to 2.9 g/kWh. This study provides insights for the operational settings optimisation of two-stroke engines equipped with EGR systems, contributing towards the reduction of the associated environmental carbon footprint.

Effectiveness of Disinfectants Suitable for Inactivating SARS-CoV-2 at Cold-Chain Temperature - Xiaosong Wu; Yin Chen; Ling Wang; Xiling Guo; Lunbiao Cui; Yiming Shen; Fang Li; Hong Sun; Liubo Zhang; Jin Shen; Yan Xu (Food and Environmental Virology, 2022)

Genetic diversity among a collection of bitter gourd (Momordica charantia L.) cultivars - Junjie Cui; Yinhui Zhou; Jian Zhong; Chengcheng Feng; Yu Hong; Kailin Hu; Yi Cao (Genetic Resources and Crop Evolution, 2022)

Distribution of Coomassie Blue Stainable Particles in the Pearl River Estuary, China, Insight Into the Nitrogen Cycling in Estuarine System - Cui-Ci Sun; Wei-Zhong Yue; You-Shao Wang; Wei-Hong He; Yi-Guo Hong; Fu-Lin Sun; Hao Cheng; Mei-Lin Wu; Zhao-Yu Jiang; Fei Jiao; Yu-Tu Wang (Frontiers in Marine Science, 2022)
Distributions of Coomassie Blue stainable particles (CSP), the sources and transports, as well as their implications for nitrogen biogeochemical cycles in the Pearl River estuary (PRE) were investigated during two cruises in August 2016 and January 2017. CSP color concentrations (CSP concentration determined spectrophotometrically) were 73.7–685.3 μg BSA eq L –1 [μg Bovine serum albumin (BSA) equivalent liter –1 ] in August 2016 and 100.6–396.4 μg BSA eq L –1 in January 2017, respectively. CSP concentrations were high in low-salinity waters (<5), and declined from the river to the middle estuary by 80% in the wet season and 55.6% in the dry season, respectively, then increased again in the lower estuary due to high primary production. CSP concentrations were mainly associated with chlorophyll a (Chl a ) concentration except for the turbid mixing zone, suggesting that autochthonous phytoplankton production served as the primary source of CSP in the PRE. The concentrations of nitrogen (N) as CSP in the PRE were comparable to the nitrogen content of particulate hydrolysable amino acids (PHAA). Pictures of CSP taken by microscopy and the correlation between composition of PHAA and the ratio of Chl a /CSP color showed that CSP were relatively degraded due to delivery of old terrestrial protein to river section and extensive microbial degradation during mixing at the upper and middle parts of the estuary, whereas CSP in lower estuary appeared to be more labile due to higher fresh algal production. The contribution of CSP nitrogen (CSP-N) to the particulate nitrogen (PN) pool was 34.98% in summer and 30.8% in winter. The conservative estimate of CSP-N input flux in the Pearl River Delta was about 6 × 10 6 mol N d –1 . These results suggested that CSP was a significant pool of organic nitrogen in the PRE. The study of CSP composition in terms of nitrogen provides new insight into the roles of CSP on nitrogen biogeochemical processes in the turbid and productive estuarine system.

Secondary metabolites isolated from Agrimonia pilosa Ledeb. - Hong-Rui Li; Yu-Kui Li; Jian Xiao; Cui Yang; Meng-Yuan Jiang; Kai Tian; Wei Wang; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2022)

NtCycB2 negatively regulates tobacco glandular trichome formation, exudate accumulation, and aphid resistance - Zhaojun Wang; Xiaoxiao Yan; Hongying Zhang; Ying Meng; Yang Pan; Hong Cui (Plant Molecular Biology, 2022)

Methyl jasmonate treatment, aphid resistance assay, and transcriptomic analysis revealed different herbivore defensive roles between tobacco glandular and non-glandular trichomes - Zhaojun Wang; Yanhua Li; Hongying Zhang; Xiaoxiao Yan; Hong Cui (Plant Cell Reports, 2022)

Microbial controls on heavy metals and nutrients simultaneous release in a seasonally stratified reservoir - Xuecheng Zhang; Shiyuan Ding; Hong Lv; Gaoyang Cui; Mengdi Yang; Yiyao Wang; Tianhao Guan; Xiao-Dong Li (Environmental Science and Pollution Research, 2022)

External evaluation of published population pharmacokinetic models of polymyxin B - Ya-qian Li; Kai-feng Chen; Jun-jie Ding; Hong-yi Tan; Nan Yang; Ya-qi Lin; Cui-fang Wu; Yue-liang Xie; Guo-ping Yang; Jing-Jing Liu; Qi Pei (European Journal of Clinical Pharmacology, 2021)

1,4-Dioxane Degradation Performance of Tetrahydrofuran-Grown Arthrobacter sp. WN18 - Peng Wang; Tingchen Cui; Jialu Li; Na Liu; Mei Hong (Water, Air, & Soil Pollution, 2021)

Tacrolimus Decreases Cognitive Function by Impairing Hippocampal Synaptic Balance: a Possible Role of Klotho - Yoo Jin Shin; Sun Woo Lim; Sheng Cui; Eun Jeong Ko; Byung Ha Chung; Hong Lim Kim; Tae Ryong Riew; Mun Yong Lee; Chul Woo Yang (Molecular Neurobiology, 2021)

Time-resolved Fluorescence Immunoassay (TRFIA) for the Simultaneous Detection of MMP-9 and Lp-PLA2 in Serum - Hong-yan Ma; Qian Mao; Yan-bin Zhu; Chun-li Cong; Shi-yu Zheng; Qi Zhang; Cui-cui Chen; Lai-qing Li (Journal of Fluorescence, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

Understanding the Yanshan volcano eruption in the Chaihe–Arxan volcanic field, northeastern China - Xiao-ge Cui; Jian-dong Xu; Hong-mei Yu; Bo Zhao; Wen-jian Yang (Arabian Journal of Geosciences, 2021)

A new ergostane derivative from the leaves of Heynea trijuga Roxburgh - Shou-Bai Liu; Zheng Cui; Hui-Qin Chen; Hao Wang; Wen-Hua Dong; Cai-Hong Cai; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2021)

Function identification of miR394 in tomato resistance to Phytophthora infestans - Yuan-Yuan Zhang; Yu-Hui Hong; Ya-Rong Liu; Jun Cui; Yu-Shi Luan (Plant Cell Reports, 2021)

Regional brain network and behavioral alterations in EGR3 gene transfected rat model of schizophrenia - Wenwen Gao; Guangfei Li; Xiaowei Han; Zeyu Song; Shuai Zhao; Feiyi Sun; Hong Ma; Ailing Cui; Yige Wang; Xiuxiu Liu; Yue Chen; Lu Zhang; et al. (Brain Imaging and Behavior, 2021)

Yeast YPK9 deficiency results in shortened replicative lifespan and sensitivity to hydrogen peroxide - Wei Zhao; Fang Guo; Lingyue Kong; Jiaxin Liu; Xiaoshan Hong; Zhiwen Jiang; Haochang Song; Xiaojing Cui; Jie Ruan; Xinguang Liu (Biogerontology, 2021)

Magnetic Resonance Imaging-Guided and Navigated Individualized Repetitive Transcranial Magnetic Stimulation for Cognitive Impairment in Schizophrenia - Xu-Sha Wu; Tian-Cai Yan; Xian-Yang Wang; Yang Cao; Xiao-Fan Liu; Yu-Fei Fu; Lin Wu; Yin-Chuan Jin; Hong Yin; Long-Biao Cui (Neuroscience Bulletin, 2021)

Identification of unstable bedrock promontory on steep slope based on UAV photogrammetry - Wei Cui; Xuan-hao Wang; Gui-ke Zhang; Hong-bi Li (Bulletin of Engineering Geology and the Environment, 2021)

Isolation and phylogenetic analysis of strains of feline calicivirus in Beijing, China - Zhaoyang Wang; Ting Xin; Jin Wei; Yajun Jiang; Xueting Liu; Wenjing Song; Xiaoyu Guo; Weifeng Yuan; Yanbin Cui; Hongfei Zhu; Hong Jia (Archives of Virology, 2021)

A Novel Multi-Robot Task Allocation Model in Marine Plastics Cleaning Based on Replicator Dynamics - Le Hong; Weicheng Cui; Hao Chen (Journal of Marine Science and Engineering, 2021)
As marine plastic pollution threatens the marine ecosystem seriously, the government needs to find an effective way to clean marine plastics. Due to the advantages of easy operation and high efficiency, autonomous underwater vehicles (AUVs) have been applied to clean marine plastics. As for the large-scale marine environment, the marine plastic cleaning task needs to be accomplished through the collaborative work of multiple AUVs. Assigning the cleaning task to each AUV reasonably and effectively has an essential impact on improving cleaning efficiency. The coordination of AUVs is subjected to harsh communication conditions. Therefore, to release the dependence on the underwater communications among AUVs, proposing a reliable multi-robot task allocation (MRTA) model is necessary. Inspired by the evolutionary game theory, this paper proposes a novel multi-robot task allocation (MRTA) model based on replicator dynamics for marine plastic cleaning. This novel model not only satisfies the minimization of the cost function, but also reaches a relatively stable state of the task allocation. A novel optimization algorithm, equilibrium optimizer (EO), is adopted as the optimizer. The simulation results validate the correctness of the results achieved by EO and the applicability of the proposed model. At last, several valuable conclusions are obtained from the simulations on the three different assumed AUVs.

Gut Microbial Metabolites in Parkinson’s Disease: Implications of Mitochondrial Dysfunction in the Pathogenesis and Treatment - Yixuan Liang; Li Cui; Jiguo Gao; Mingqin Zhu; Ying Zhang; Hong-Liang Zhang (Molecular Neurobiology, 2021)
The search for therapeutic targets for Parkinson’s disease (PD) is hindered by the incomplete understanding of the pathophysiology of the disease. Mitochondrial dysfunction is an area with high potential. The neurobiological signaling connections between the gut microbiome and the central nervous system are incompletely understood. Multiple lines of evidence suggest that the gut microbiota participates in the pathogenesis of PD. Gut microbial dysbiosis may contribute to the loss of dopaminergic neurons through mitochondrial dysfunction. The intervention of gut microbial metabolites via the microbiota-gut-brain axis may serve as a promising therapeutic strategy for PD. In this narrative review, we summarize the potential roles of gut microbial dysbiosis in PD, with emphasis on microbial metabolites and mitochondrial function. We then review the possible ways in which microbial metabolites affect the central nervous system, as well as the impact of microbial metabolites on mitochondrial dysfunction. We finally discuss the possibility of gut microbiota as a therapeutic target for PD.

Safety evaluation and ibuprofen removal via an Alternanthera philoxeroides-based biochar - Yuan-da Du; Xin-qian Zhang; Li Shu; Yu Feng; Cui Lv; Hong-qiang Liu; Fei Xu; Qian Wang; Cong-cong Zhao; Qiang Kong (Environmental Science and Pollution Research, 2021)

A catastrophic natural disaster chain of typhoon-rainstorm-landslide-barrier lake-flooding in Zhejiang Province, China - Yu-long Cui; Jun-hong Hu; Chong Xu; Jun Zheng; Jiang-bo Wei (Journal of Mountain Science, 2021)

Maricaulis alexandrii sp. nov., a novel active bioflocculants-bearing and dimorphic prosthecate bacterium isolated from marine phycosphere - Xiao-ling Zhang; Min Qi; Qiu-hong Li; Zhen-dong Cui; Qiao Yang (Antonie van Leeuwenhoek, 2021)

Three new 5,6,7,8-tetrahydro-2-(2-phenylethyl)chromones and one new dimeric 2-(2-phenylethyl)chromone from agarwood of Aquilaria crassna Pierre ex Lecomte in Laos - Yang-Mei Zhao; Li Yang; Fan-Dong Kong; Wen-Hua Dong; Wei Li; Hui-Qin Chen; Hao Wang; Cai-Hong Cai; Cui-Juan Gai; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2021)

Eutrophication regulation of Wuxing Lake based on eco-dynamics model - Feng Gao; Hong Cui; Suiju Lv; Ying Qiao (Arabian Journal of Geosciences, 2021)

Occurrence and cycle of dimethyl sulfide in the western Pacific Ocean - Feng Xu; Shi‐Bo Yan; Hong‐Hai Zhang; Ying‐Cui Wu; Qian‐Yao Ma; Yu‐Chen Song; Guang‐Chao Zhuang; Gui‐Peng Yang (Limnology and Oceanography, 2021)
Oceanic production and occurrence of dimethyl sulfide (DMS) and its subsequent ventilation to the atmosphere significantly contribute to the global sulfur cycle and impact the climate regulation. Spatial distributions of DMS, dimethylsulfoniopropionate (DMSP, precursor of DMS), and dimethyl sulfoxide (DMSO, oxidation product of DMS), production and removal processes of DMS (including biological production, microbial consumption, photo‐degradation, and sea‐to‐air exchange), and biogenic contributions to the atmospheric sulfate burden were simultaneously studied in the western Pacific Ocean during winter. Sea surface DMS, DMSP, and DMSO were strongly correlated and had similar distribution patterns. The DMS photo‐degradation efficiency ratio (normalized using incident photon flux density) for ultraviolet B radiation (UVB): ultraviolet A radiation (UVA): photosynthetically active radiation (PAR) was 391: 36: 1. However, considering the solar spectral composition, the actual contributions of UVB, UVA, and PAR to DMS photo‐degradation in surface waters were 40.6% ± 10.7%, 41.2% ± 15.6%, and 18.2% ± 7.2%, respectively. When integrated across the entire mixed layer, UVA and PAR became the dominant drivers, accounting for 45.2% ± 18.0% and 38.0% ± 17.3% of DMS photo‐degradation, respectively, as UVB was significantly attenuated in seawater. The DMS budget of the entire mixed layer indicated that microbial consumption, photo‐degradation, and ventilation accounted for about 74.3% ± 11.9%, 19.3% ± 9.3%, and 6.5% ± 4.0% of total DMS removal, respectively. Even if ventilation was a minor DMS removal pathway, DMS emissions still contributed approximately 45.2% ± 25.6% of the atmospheric non‐sea‐salt sulfate burden over the western Pacific Ocean.

Retrieval of sea surface temperature from the scanning microwave radiometer aboard HY-2B - Shu-Bo Liu; Xin-Dong Cui; Yi-Nan Li; Xu Jin; Wu Zhou; Hong-Xing Dang; Hao Li (International Journal of Remote Sensing, 2021)

Ziziphus jujuba Mill., a plant used as medicinal food: a review of its phytochemistry, pharmacology, quality control and future research - Shi-Jun Liu; Yan-Ping Lv; Zhi-Shu Tang; Yu Zhang; Hong-Bo Xu; Dong-Bo Zhang; Chun-Li Cui; Hong-Bo Liu; Huan-Huan Sun; Zhong-Xing Song; Si-Min Wei (Phytochemistry Reviews, 2021)

A Well Temperature Correction Based on the Least Squares Method and its Application in a Coal Mining Area, China - Yan Guo; Jiuchuan Wei; Herong Gui; Huang Hong; Chunhui Ren; Yali Cui; Qingshan Lu; Jiwen Wu; Tao Peng; Zhan Liang; Lixiang Zhao (Natural Resources Research, 2021)

DNA Methyltransferase 1 Is Dysregulated in Parkinson’s Disease via Mediation of miR-17 - Hong-Qiu Zhang; Jian-Yong Wang; Zhao-Feng Li; Lei Cui; Shi-Shi Huang; Lan-Bing Zhu; Yue Sun; Rui Yang; Hui-Hui Fan; Xiong Zhang; Jian-Hong Zhu (Molecular Neurobiology, 2021)

A Simplified Calculation Method for Ultimate Mining Dimension in Thin Coal Seam - Yuxin Ban; Xiang Fu; Qiang Xie; Jianfeng Cui; Hong Xu (Geotechnical and Geological Engineering, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Detection and genetic characteristics of porcine bocavirus in central China - Lan-Lan Zheng; Jian-Tao Cui; Han Qiao; Xin-Sheng Li; Xiao-Kang Li; Hong-Ying Chen (Archives of Virology, 2021)

Design and Characterization of a Novel Hybrid Antimicrobial Peptide OM19R Based on Oncocin and MDAP-2 - Lei Liu; Jie Liu; Qi Cui; Bo-Yan Jia; Zhi-Hua Pei; Kokou Ayefounin Odah; Yi-Ming Wang; Wen-Long Dong; Ling-Cong Kong; Hong-Xia Ma (International Journal of Peptide Research and Therapeutics, 2020)

Rock Mass Quality Prediction of Open-Pit Gold Mine Slope Based on the Kriging Interpolation Method - Zhigang Tao; Xuebin Cui; Xiaoming Sun; Jiong Wang; Kuiming Liu; Hong Chen (Geotechnical and Geological Engineering, 2020)

Induced sputum metabolomic profiles and oxidative stress are associated with chronic obstructive pulmonary disease (COPD) severity: potential use for predictive, preventive, and personalized medicine - Tao Zhu; Shanqun Li; Jiajia Wang; Chunfang Liu; Lei Gao; Yuzhen Zeng; Ruolin Mao; Bo Cui; Hong Ji; Zhihong Chen (EPMA Journal, 2020)
Chronic obstructive pulmonary disease (COPD) is a highly heterogeneous disease, and metabolomics plays a hub role in predictive, preventive, and personalized medicine (PPPM) related to COPD. This study thus aimed to reveal the role of induced sputum metabolomics in predicting COPD severity. In this pilot study, a total of 20 COPD patients were included. The induced sputum metabolites were assayed using a liquid chromatography-mass spectrometry (LC-MS/MS) system. Five oxidative stress products (myeloperoxidase (MPO), superoxide dismutase (SOD), glutathione (GSH), neutrophil elastase (NE), and 8-iso-PGF2α) in induced sputum were measured by ELISA, and the metabolomic profiles were distinguished by principal component analysis (PCA) and orthogonal projections to latent structures discriminant analysis (OPLS-DA). The Kyoto Encyclopedia of Genes and Genomes (KEGG) was used for pathway enrichment analysis, and a significant difference in induced sputum metabolomics was observed between moderate and severe COPD. The KEGG analysis revealed that the glycerophospholipid metabolism pathway was downregulated in severe COPD. Due to the critical role of glycerophospholipid metabolism in oxidative stress, significant negative correlations were discovered between glycerophospholipid metabolites and three oxidative stress products (SOD, MPO, and 8-iso-PGF2α). The diagnostic values of SOD, MPO, and 8-iso-PGF2α in induced sputum were found to exhibit high sensitivities and specificities in the prediction of COPD severity. Collectively, this study provides the first identification of the association between induced sputum metabolomic profiles and COPD severity, indicating the potential value of metabolomics in PPPM for COPD management. The study also reveals the correlation between glycerophospholipid metabolites and oxidative stress products and their value for predicting COPD severity.

Larger regional volume of the thalamus in diarrhea-predominant irritable bowel syndrome: a cross-sectional study - Cui Ping Mao; Fen Rong Chen; Hong Hong Sun; Mei Juan Shi; Hua Juan Yang; Xiao Hui Li; Dun Ding (Brain Imaging and Behavior, 2020)

A novel alkaloid glycoside isolated from Atalantia buxifolia - Hui-Xian Liang; Jing-Jing Sun; Zhi-Bin Shen; Bang-Wei Yu; Hong-Hua Cui; Yong-Qin Yin (Natural Product Research, 2020)

Systemic effect of dietary lipid levels and α-lipoic acid supplementation on nutritional metabolism in zebrafish (Danio rerio): focusing on the transcriptional level - Chen-cui Huang; Jian Sun; Hong Ji; Gen Kaneko; Xing-da Xie; Zhi-guang Chang; Wei Deng (Fish Physiology and Biochemistry, 2020)

Characteristics of the spike and ORF3 genes of porcine epidemic diarrhea virus in Henan and Shanxi provinces of China - Jian-tao Cui; Han Qiao; Cheng-yao Hou; Hui-Hua Zheng; Xin-Sheng Li; Lan-lan Zheng; Hong-Ying Chen (Archives of Virology, 2020)

RETRACTED ARTICLE: A Fluorescent Zn(II) Coordination Polymer: Sensitive Detection of Cr2O72− in Water and Prevention Activity On the Deep Vein Thrombosis in Orthopedic Nursing - Yu Zhou; Li Cui; Yan Zhang; Yu Liu; Dai-Hong Ji (Journal of Fluorescence, 2020)

Heat-air-moisture coupled model for radon migration in a porous media - Yu Cui; Shengyang Feng; Puxin Chen; Yongjun Ye; Yurong Wu; Ce Li; Rong Yang; Hong Wang (Environmental Science and Pollution Research, 2020)

CSF Brain-Reactive Autoantibodies are Elevated in Patients with Viral Encephalitis - Zhong-Yuan Yu; Jian-Hong Wang; Wei-Wei Li; Ye-Ran Wang; Noralyn B. Mañucat-Tan; Jun Wang; Ju Wang; Gao-Yu Cui; Jie-Xiang Pan; Shui-Xian Zhang; Zu-Juan Liu; Liang Tan; et al. (Neuroscience Bulletin, 2020)

Machine learning–based operation skills assessment with vascular difficulty index for vascular intervention surgery - Shuxiang Guo; Jinxin Cui; Yan Zhao; Yuxin Wang; Youchun Ma; Wenyang Gao; Gengsheng Mao; Shunming Hong (Medical & Biological Engineering & Computing, 2020)

A new bis-γ-pyrone polypropionate of onchidiol family from marine pulmonate mollusk Onchidium sp - Song-Wei Li; Wan-Xiang Cui; Xia-Juan Huan; Margherita Gavagnin; Ernesto Mollo; Ze-Hong Miao; Li-Gong Yao; Xu-Wen Li; Yue-Wei Guo (Natural Product Research, 2020)

Correction to: Simulated microgravity significantly altered metabolism in epidermal stem cells - Bin-Bin Li; Zheng-Yang Chen; Nan Jiang; Song Guo; Jia-Qi Yang; Shao-Bin Chai; Hong-Feng Yan; Pei-Ming Sun; Gang Hu; Tao Zhang; Bing-Xin Xu; Hong-Wei Sun; et al. (In Vitro Cellular & Developmental Biology - Animal, 2020)

MicroRNA-625-5p Sponges lncRNA MALAT1 to Inhibit Cervical Carcinoma Cell Growth by Suppressing NF-κB Signaling - Yujiao Li; Yumei Ding; Ning Ding; Hong Zhang; Ming Lu; Xiaorong Cui; Xiaohui Yu (Cell Biochemistry and Biophysics, 2020)

Concentration-Dependent Regulation of TiAl6V4 Particles on the Osteogenesis Potential of Human Bone Marrow Mesenchymal Stem Cells - Hongxiang Hong; Guanhua Xu; Hongjian Deng; Xiaogang Zhou; Wei Liu; Zhiming Cui (Biological Trace Element Research, 2020)

Two new aromatic polyketides from a deep-sea fungus Penicillium sp. SCSIO 06720 - Cui Guo; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Xian-Wen Yang; Xin-Peng Tian; Jun-Feng Wang; Yong-Hong Liu (Natural Product Research, 2020)

High-frequency direct shoot organogenesis from garlic (Allium sativum L.) inflorescence and clonal fidelity assessment in regenerants - Yan-Bin Wen; Xiao-Xue Liu; Hong-Jiu Liu; Cui-Nan Wu; Huan-Wen Meng; Zhi-Hui Cheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Effect of different light intensity on physiology, antioxidant capacity and photosynthetic characteristics on wheat seedlings under high CO2 concentration in a closed artificial ecosystem - Zhihao Yi; Jingjing Cui; Yuming Fu; Hong Liu (Photosynthesis Research, 2020)

Simulated microgravity significantly altered metabolism in epidermal stem cells - Bin-Bin Li; Zheng-Yang Chen; Nan Jiang; Song Guo; Jia-Qi Yang; Shao-Bin Chai; Hong-Feng Yan; Pei-Ming Sun; Gang Hu; Tao Zhang; Bing-Xin Xu; Hong-Wei Sun; et al. (In Vitro Cellular & Developmental Biology - Animal, 2020)
Simulated microgravity can significantly affect various cell types and multiple systems of the human body, such as cardiovascular system, skeletal muscle system, and immune system, and is known to cause anemia and loss of electrolyte and fluids. Epidermal stem cells (EpSCs) were cultured in a rotary cell culture system (RCCS) bioreactor to simulate microgravity. The metabolites of EpSCs were identified by liquid chromatography-mass spectrometry (LC-MS). Compared with normal gravity (NG) group, a total of 57 different metabolites of EpSCs were identified ( P < 0.05, VIP > 1), including lipids and lipid-like molecules (51 molecules), amino acids (5 molecules), nucleosides, nucleotides, and analogues (1 molecule). According to the partial least squares discriminant analysis (PLS-DA) score plot, a VIP > 1 and P < 0.05 were obtained for the 57 different metabolites, of which 23 molecules were significantly downregulated and 34 were significantly upregulated in simulated microgravity (SMG) group. These results showed that SMG has a significant impact on different pathways, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis indicated that multiple pathways were involved, mainly the amino acid metabolism pathway, lipid metabolism pathway, membrane transport pathway, and cell growth and death pathways. Thus, the metabolic profile of EpSCs was changed under SMG. Exploring the metabolic profile of EpSCs would be helpful to further understand the growth characteristics of EpSCs under SMG, which will provide a new approach to explore the metabolomics mechanism of stress injury and repair trauma under SMG.

Chemical content and source apportionment of 36 heavy metal analysis and health risk assessment in aerosol of Beijing - Limeng Cui; Zhuona Wu; Peng Han; Yasuyuki Taira; Huan Wang; Qinghua Meng; Zechen Feng; Shuguang Zhai; Jun Yu; Weijie Zhu; Yuxia Kong; Hongfang Wang; et al. (Environmental Science and Pollution Research, 2020)

A new nucleoside and two new pyrrole alkaloid derivatives from Cordyceps militaris - Yafu Xue; Leilei Wu; Yulian Ding; Xinming Cui; Zhuzhen Han; Hong Xu (Natural Product Research, 2020)

Genome-Wide Association Study of Cerebral Microbleeds on MRI - Hong-Qi Li; Wen-Jie Cai; Xiao-He Hou; Mei Cui; Lan Tan; Jin-Tai Yu; Qiang Dong (Neurotoxicity Research, 2020)

Plant regeneration in Ixora chinensis from young leaves - TingGe Li; Hong Cai; TongXin Wang; YingGe Fu; WenHan Yang; AnJin Zhao; Zheng Cui; Jian Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Expressional and Functional Verification of the Involvement of CmEXPA4 in Chrysanthemum Root Development - Hong Ren; Li-zhu Wen; Yun-hui Guo; Yuan-yuan Yu; Cui-hui Sun; Hong-mei Fan; Fang-fang Ma; Cheng-shu Zheng (Journal of Plant Growth Regulation, 2019)

Comparative transcriptome analysis of male and female gonads reveals sex-biased genes in spotted scat (Scatophagus argus) - Fei-Xiang He; Dong-Neng Jiang; Yuan-Qing Huang; Umar Farouk Mustapha; Wei Yang; Xue-Fan Cui; Chang-Xu Tian; Hua-Pu Chen; Hong-Juan Shi; Si-Ping Deng; Guang-Li Li; Chun-Hua Zhu (Fish Physiology and Biochemistry, 2019)

Experimental study on the physical modeling of loess tunnel-erosion rate - Li Wang; Xi-An Li; Lin-Cui Li; Bo Hong; Jia Liu (Bulletin of Engineering Geology and the Environment, 2019)

Cardiopulmonary Comorbidity, Radiomics and Machine Learning, and Therapeutic Regimens for a Cerebral fMRI Predictor Study in Psychotic Disorders - Xiao-Hui Wang; Angela Yu; Xia Zhu; Hong Yin; Long-Biao Cui (Neuroscience Bulletin, 2019)

Choline, not folate, can attenuate the teratogenic effects ofdibutyl phthalate (DBP) during early chick embryo development - Rui Wang; Da-Guang Sun; Ge Song; Chun Yi Guan; Yi Cui; Xu Ma; Hong-Fei Xia (Environmental Science and Pollution Research, 2019)

Climatic change and the rise of the Manchu from Northeast China during AD 1600–1650 - Jianxin Cui; Hong Chang; George S. Burr; Xiaolong Zhao; Baoming Jiang (Climatic Change, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

Experimental study on the disintegration of loess in the Loess Plateau of China - Xi-An Li; Li Wang; Yong-li Yan; Bo Hong; Lin-Cui Li (Bulletin of Engineering Geology and the Environment, 2019)

Estimation of genetic parameters for upper thermal tolerances and growth-related traits in turbot Scophthalmus maximus - Xin’an Wang; Aijun Ma; Zhihui Huang; Zhibin Sun; Wenxiao Cui; Jiangbo Qu; Hong Yu (Journal of Oceanology and Limnology, 2019)

The orphan nuclear receptor NUR77 promotes trophoblast invasion at early pregnancy through paracrine placental growth factor - Xiao-Cui Li; Xiang-Jie Yin; Wei Hong; Jie Liu; Feng Jin; Bei-Ying Wang; Yu-Mei Wang; Fu-Ju Tian (Journal of Molecular Medicine, 2019)

Influence of Tacrolimus on Depressive-Like Behavior in Diabetic Rats Through Brain-Derived Neurotrophic Factor Regulation in the Hippocampus - Yoo Jin Shin; Yeon Tae Chun; Sun Woo Lim; Kang Luo; Yi Quan; Sheng Cui; Eun Jeong Ko; Byung Ha Chung; Jiyeong Lee; Seongno Hong; Mun Yong Lee; Hee Gyoo Kang; et al. (Neurotoxicity Research, 2019)

MicroRNAs Involved in the Regulation of LC-PUFA Biosynthesis in Teleosts: miR-33 Enhances LC-PUFA Biosynthesis in Siganus canaliculatus by Targeting insig1 which in Turn Upregulates srebp1 - Jun Jun Sun; Li Guo Zheng; Cui Ying Chen; Jin Ying Zhang; Cui Hong You; Qing Hao Zhang; Hong Yu Ma; Óscar Monroig; Douglas R. Tocher; Shu Qi Wang; Yuan You Li (Marine Biotechnology, 2019)

Estrogen modulation of visceral pain - Li-hong Sun; Wen-xin Zhang; Qi Xu; Hui Wu; Cui-cui Jiao; Xin-zhong Chen (Journal of Zhejiang University-SCIENCE B, 2019)

Favus of Scrotum Due to Trichophyton rubrum in Immunocompetent Patients: A Clinical, Mycological and Ultrastructural Study - Ze-Hu Liu; Xiu-Jiao Xia; Yong Zhang; Yan Zhong; Bo Sang; Qiu-Ping Li; Mei Wang; Wen-Wen Lv; Hui-Lin Zhi; Xiang-Dong Wang; Cui-Ping Guan; Hong Shen (Mycopathologia, 2019)

Crosstalk Between Inflammation and Glutamate System in Depression: Signaling Pathway and Molecular Biomarkers for Ketamine’s Antidepressant Effect - Wenyan Cui; Yuping Ning; Wu Hong; Ju Wang; Zhening Liu; Ming D. Li (Molecular Neurobiology, 2019)

Intestinal Methylation and Demethylation of Mercury - Hong Li; Xiaoying Lin; Jiating Zhao; Liwei Cui; Liming Wang; Yuxi Gao; Bai Li; Chunying Chen; Yu-Feng Li (Bulletin of Environmental Contamination and Toxicology, 2019)

A novel SGNH family hydrolase Ali5 with thioesterase activity and a GNSL motif but without a classic GDSL motif from Altererythrobacter ishigakiensis - Li-Guo Hong; Shu-Ling Jian; Ying-Yi Huo; Hong Cheng; Xiao-Jian Hu; Jixi Li; Heng-Lin Cui; Xue-Wei Xu (Biotechnology Letters, 2019)

Chronic stress impairs the aquaporin-4-mediated glymphatic transport through glucocorticoid signaling - Fang Wei; Jian Song; Cui Zhang; Jun Lin; Rong Xue; Li-Dong Shan; Shan Gong; Guo-Xing Zhang; Zheng-Hong Qin; Guang-Yin Xu; Lin-Hui Wang (Psychopharmacology, 2019)

Analysis and preliminary validation of the molecular mechanism of fat deposition in fatty and lean pigs by high-throughput sequencing - Jing Xiang Cui; Qi Fan Zeng; Wei Chen; Hong Zhang; Yong Qing Zeng (Mammalian Genome, 2019)

Yeast molecular chaperone gene SSB2 is involved in the endoplasmic reticulum stress response - Wei Zhao; Hong-Jing Cui; Kun-Pei Qiu; Tao Zhou; Xiao-Shan Hong; Xin-Guang Liu (Antonie van Leeuwenhoek, 2019)

Chinese society of cardiology expert consensus statement on the diagnosis and treatment of adult fulminant myocarditis - Daowen Wang; Sheng Li; Jiangang Jiang; Jiangtao Yan; Chunxia Zhao; Yan Wang; Yexin Ma; Hesong Zeng; Xiaomei Guo; Hong Wang; Jiarong Tang; Houjuan Zuo; et al. (Science China Life Sciences, 2019)

Differentiations of geographic distribution and subsistence strategies between Tibetan and other major ethnic groups are determined by the physical environment in Hehuang Valley - Xin Jia; Harry F. Lee; Mengchun Cui; Guoquan Cheng; Yang Zhao; Hong Ding; Ricci P. H. Yue; Huayu Lu (Science China Earth Sciences, 2019)

Chronic Intracerebroventricular Infusion of Metformin Inhibits Salt-Sensitive Hypertension via Attenuation of Oxidative Stress and Neurohormonal Excitation in Rat Paraventricular Nucleus - Xiao-Jing Yu; Ya-Nan Zhao; Yi-Kang Hou; Hong-Bao Li; Wen-Jie Xia; Hong-Li Gao; Kai-Li Liu; Qing Su; Hui-Yu Yang; Bin Liang; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Benzene metabolite 1,2,4-benzenetriol changes DNA methylation and histone acetylation of erythroid-specific genes in K562 cells - Chun-Hong Yu; Yang Li; Xiao Zhao; Shui-Qing Yang; Lei Li; Ning-Xuan Cui; Long Rong; Zong-Chun Yi (Archives of Toxicology, 2019)

Phosphorus Enhances Cr(VI) Uptake and Accumulation in Leersia hexandra Swartz - Chan-Cui Wu; Jie Liu; Xue-Hong Zhang; Shi-Guang Wei (Bulletin of Environmental Contamination and Toxicology, 2018)

Incomplete species lists derived from global and regional specimen‐record databases affect macroecological analyses: A case study on the vascular plants of China - Hong Qian; Tao Deng; Jan Beck; Hang Sun; Cui Xiao; Yi Jin; Keping Ma (Journal of Biogeography, 2018)
Aim Online species distribution data, global or regional, are increasingly used in biodiversity studies although data limitations have been reported. We explore, for the two major databanks in our research region, how incomplete data are at a large taxonomic and geographic scale, how it is affected by spatial grain, and to what degree it affects inference from analyses of richness or turnover and the environment. Location China. Major taxa studied Vascular plants. Methods We assembled species lists of all vascular plants from the Global Biodiversity Information Facility ( GBIF ) and the National Specimen Information Infrastructure ( NSII ) at three spatial scales (national, provincial, county). We determined the completeness of each compilation by comparing the number of species with that from inventory‐based species list (for 28 provinces, 14 counties, and 146 nature reserves within counties). We related richness from each of the data sources ( GBIF , NSII , inventory) to environmental variables (temperature, precipitation, elevational range) and compared regression models among the three data sources. We quantified floristic similarity between regions based on the three data sources and related species turnover to geographic and environmental distances. Results Data incompleteness was prevalent at all spatial grains, but it increased with decreasing grain and it was higher for GBIF than for NSII . At the national scale, GBIF included 64.1% and NSII included 89.4% of true species richness in China. At the county scale these figures dropped to an average of 12.7% for GBIF and 60.0% for NSII . This changed the order and significance of environmental determinants of richness in regression models. The relationship between floristic similarity and geographic or environmental distance was shallower for GBIF and NSII , compared to inventory data. When the GBIF data were supplemented with the NSII data, the data completeness of GBIF increased from 64.1% to 90.8% at the national scale, from 37.2% to 89.0% at the province scale, and from 12.7% to 63.0% at the county scale. Main conclusions Main specimen‐record databases are incomplete, which has the potential to heavily affect ecological patterns and mechanisms inferred from these data. Biodiversity analyses based on raw species lists from such sources should be viewed with utmost caution.

Structure–activity relationship investigation of coumarin–chalcone hybrids with diverse side-chains as acetylcholinesterase and butyrylcholinesterase inhibitors - Lu Kang; Xiao-Hui Gao; Hao-Ran Liu; Xue Men; Hong-Nian Wu; Pei-Wu Cui; Eric Oldfield; Jian-Ye Yan (Molecular Diversity, 2018)

Compression reference of soil structure evaluation with reconstituted clays at different initial water contents - Ling-Ling Zeng; Zhen-Shun Hong; Yu-Jun Cui; Martin D. Liu (Marine Georesources & Geotechnology, 2018)

Lack of Association Between DNMT3B Polymorphisms and Sporadic Parkinson’s Disease in a Han Chinese Population - Hong Pan; Jun-Yi Shen; Juan-Juan Du; Shi-Shuang Cui; Jin Liu; Yi-Qi Lin; Yi-Xi He; Yang Fu; Chao Gao; Gen Li; Sheng-Di Chen; Jian-Fang Ma (Neuroscience Bulletin, 2018)

Rainfall and inflow effects on soil erosion for hillslopes dominated by sheet erosion or rill erosion in the Chinese Mollisol region - Hai-ou Shen; Lei-lei Wen; Yun-feng He; Wei Hu; Hong-li Li; Xiao-cui Che; Xin Li (Journal of Mountain Science, 2018)

Perfluoroalkyl acid exposure induces protective mitochondrial and endoplasmic reticulum autophagy in lung cells - Yan Xin; Bin Wan; Yu Yang; Xue-Jing Cui; Yi-Chun Xie; Liang-Hong Guo (Archives of Toxicology, 2018)

Ascidiaceibacter salegens gen. nov., sp. nov., isolated from an ascidian - Lei Chen; Shi-Cheng Wang; Cui-Hong Ma; Dong-Xu Zheng; Zong-Jun Du; Guang-Yu Wang (Antonie van Leeuwenhoek, 2018)

Ancylomarina psychrotolerans sp. nov., isolated from sediments of Fildes Peninsula and emended the description of genus Ancylomarina - Chao Jia; Hong-chang Cui; Yan-qiong Han; Tian-yu Fu; Rui Du; Xiao-lei Wang; Xiao-chong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2018)

Rare Earth Elements Geochemistry and Nd Isotopes in the Mississippi River and Gulf of Mexico Mixing Zone - Segun B. Adebayo; Minming Cui; Travis Hong; Christopher D. White; Ellen E. Martin; Karen H. Johannesson (Frontiers in Marine Science, 2018)

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

Fate of antibiotic and metal resistance genes during two-phase anaerobic digestion of residue sludge revealed by metagenomic approach - Ying Wu; Erping Cui; Yiru Zuo; Weixiao Cheng; Hong Chen (Environmental Science and Pollution Research, 2018)

Yield enhancement strategies of rare pharmaceutical metabolites from endophytes - Fangxue Xu; Shiyuan Wang; Yujuan Li; Mengmeng Zheng; Xiaozhi Xi; Hui Cao; Xiaowei Cui; Hong Guo; Chunchao Han (Biotechnology Letters, 2018)

Functional Investigation of a GRIN2A Variant Associated with Rolandic Epilepsy - Xing-Xing Xu; Xiao-Rong Liu; Cui-Ying Fan; Jin-Xing Lai; Yi-Wu Shi; Wei Yang; Tao Su; Jun-Yu Xu; Jian-Hong Luo; Wei-Ping Liao (Neuroscience Bulletin, 2018)

Anomalous gray matter structural networks in recent onset post-traumatic stress disorder - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Jian Zhang; Fan Guo; Qing-Rong Tan; Mei Shi; Kang Liu; Yi-Bin Xi; Nan-Yin Zhang; Xiao-Liang Zhang; Yong He; et al. (Brain Imaging and Behavior, 2018)

Occurrence and Partition of Perfluorinated Compounds (PFCs) in Water and Sediment from the Songhua River, China - Weihua Dong; Baolin Liu; Yang Song; Hong Zhang; Juying Li; Xiaoyu Cui (Archives of Environmental Contamination and Toxicology, 2018)

Comparative studies of leaf surface chemical biosynthesis in different tobacco cultivars - Mingyue Huang; Hongying Zhang; Zhaojun Wang; Dexin Niu; Yanhua Li; Hong Cui (Acta Physiologiae Plantarum, 2018)

Design, synthesis and anti-cancer evaluation of novel podophyllotoxin derivatives as potent tubulin-targeting agents - Cui Hu; Xiang Zhu; Gu-Hao Wang; Xun Wu; Hong-Wei Han; Gui-Hua Lu; Jin-Liang Qi; Yan-Jun Pang; Rong-Wu Yang; Xiao-Ming Wang; Yong-Hua Yang (Medicinal Chemistry Research, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Association of lactase 13910 C/T polymorphism with bone mineral density and fracture risk: a meta-analysis - Yougen Wu; Yinghua Li; Yunqing Cui; Yunjiao Zhou; Qingqing Qian; Yang Hong (Journal of Genetics, 2017)

Constituents from solid-cultured Antrodia camphorata - Zong-Bo Tong; Xu-Hong Cui; Jie Wang; Cun-Li Zhang; Yan-Yan Zhang; Zhan-Jun Ren (Natural Product Research, 2017)

Estimating cadmium concentration in the edible part of Capsicum annuum using hyperspectral models - Ting Wang; Hong Wei; Cui Zhou; Yanwen Gu; Rui Li; Hongchun Chen; Wenchao Ma (Environmental Monitoring and Assessment, 2017)

Cerebral perfusion alterations in type 2 diabetes and its relation to insulin resistance and cognitive dysfunction - Ying Cui; Xia Liang; Hong Gu; Yuzheng Hu; Zhen Zhao; Xiang-Yu Yang; Cheng Qian; Yihong Yang; Gao-Jun Teng (Brain Imaging and Behavior, 2017)

Methane enhances aluminum resistance in alfalfa seedlings by reducing aluminum accumulation and reestablishing redox homeostasis - Weiti Cui; Hong Cao; Ping Yao; Jincheng Pan; Quan Gu; Sheng Xu; Ren Wang; Zhaozeng Ouyang; Qingya Wang; Wenbiao Shen (BioMetals, 2017)

Erratum to: Characteristics and triggering mechanism of Xinmo landslide on 24 June 2017 in Sichuan, China - Li-jun Su; Kai-heng Hu; Wei-feng Zhang; Jiao Wang; Yu Lei; Chong-lei Zhang; Peng Cui; Alessandro Pasuto; Quan-hong Zheng (Journal of Mountain Science, 2017)

Toxicity comparison of different active fractions extracted from radix Sophorae tonkinensis in zebrafish - Hong-cui Liu; Xiao-yu Zhu; Jiang-hua Chen; Sheng-ya Guo; Chun-qi Li; Zhong-ping Deng (Journal of Zhejiang University-SCIENCE B, 2017)

Hydrogen Peroxide and Strigolactones Signaling Are Involved in Alleviation of Salt Stress Induced by Arbuscular Mycorrhizal Fungus in Sesbania cannabina Seedlings - Cun-Cui Kong; Cheng-Gang Ren; Run-Zhi Li; Zhi-Hong Xie; Ji-Ping Wang (Journal of Plant Growth Regulation, 2017)

Characteristics and triggering mechanism of Xinmo landslide on 24 June 2017 in Sichuan, China - Li-jun Su; Kai-heng Hu; Wei-feng Zhang; Jiao Wang; Yu Lei; Chong-lei Zhang; Peng Cui; Alessandro Pasuto; Quan-hong Zheng (Journal of Mountain Science, 2017)

Insecticide resistance status and detoxification enzymes of wheat aphids Sitobion avenae and Rhopalosiphum padi - Liuping Zhang; Hong Lu; Kun Guo; Shumin Yao; Feng Cui (Science China Life Sciences, 2017)

Transcriptomic responses of three aphid species to chemical insecticide stress - Kun Guo; Pengcheng Yang; Jun Chen; Hong Lu; Feng Cui (Science China Life Sciences, 2017)

Effects of endogenous hormones on variation of shoot branching in a variety of non-heading Chinese cabbage and related gene expression - Xue-Wei Cao; Hong-Mi Cui; Yuan Yao; Ai-Sheng Xiong; Xi-Lin Hou; Ying Li (Journal of Plant Biology, 2017)

Bisphenol A Represses Dopaminergic Neuron Differentiation from Human Embryonic Stem Cells through Downregulating the Expression of Insulin-like Growth Factor 1 - Boxian Huang; Song Ning; Qinjing Zhang; Aiqin Chen; Chunyan Jiang; Yugui Cui; Jian Hu; Hong Li; Guoping Fan; Lianju Qin; Jiayin Liu (Molecular Neurobiology, 2017)

Multi-locus phylogeny and morphology reveal five new species of Fomitiporia (Hymenochaetaceae) from China - Hong Chen; Bao-Kai Cui (Mycological Progress, 2017)

Response mechanism of post-earthquake slopes under heavy rainfall - Hong-zhi Qiu; Ji-ming Kong; Ren-chao Wang; Yun Cui; Sen-wang Huang (Journal of Seismology, 2017)

Phytochemicals and biological activities of Artemisia sieversiana - Shi-Jun Liu; Zhi-Xin Liao; Zhi-Shu Tang; Chun-Li Cui; Hong-Bo Liu; Yan-Ni Liang; Yu Zhang; Huan-Xian Shi; Yao-Run Liu (Phytochemistry Reviews, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Involvement of the miR-462/731 cluster in hypoxia response in Megalobrama amblycephala - Cui-Hong Huang; Nan Chen; Chun-Xiao Huang; Bao Zhang; Meng Wu; Lei He; Hong Liu; Rong Tang; Wei-Min Wang; Huan-Ling Wang (Fish Physiology and Biochemistry, 2017)

The behavior of antibiotic resistance genes and arsenic influenced by biochar during different manure composting - Erping Cui; Ying Wu; Yanan Jiao; Yiru Zuo; Christopher Rensing; Hong Chen (Environmental Science and Pollution Research, 2017)

Characterization of a Gallid herpesvirus 2 strain with novel reticuloendotheliosis virus long terminal repeat inserts - Yan-ping Zhang; Ke-yan Bao; Guo-rong Sun; Hong-chao Lv; Hong-yu Cui; Yu-long Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2017)

A novel beta-galactose-specific lectin of the tubeworm, Ridgeia piscesae, from the hydrothermal vent - Lingwei Ruan; Haipeng Xu; Wenyang Lin; Hong Shi; Zhizhong Cui; Xun Xu (Acta Oceanologica Sinica, 2017)

Fractal features of soil particle-size distributions and their relationships with soil properties in gravel-mulched fields - Wen-ju Zhao; Zhen Cui; Hong Ma (Arabian Journal of Geosciences, 2017)

Three new resin glycosides compounds from Argyreia acuta and their α -glucosidase inhibitory activity - Li Wang; You-Shao Yan; Hong-Hua Cui; Yong-Qin Yin; Jie-Tao Pan; Bang-Wei Yu (Natural Product Research, 2017)

Chemical constituents from the roots of Ampelopsis delavayana and their antibacterial activities - Shuang-Xi Mei; Xu-Hong Li; Li-Guo Yang; Xiao-Hui Li; Jia-Ying Xie; Qi Yao; Mei Su; Tao Cui; Jing-Kun Wang; Zhao-Yun Zhu (Natural Product Research, 2017)

Biodegradation of saline phenolic wastewater in a biological contact oxidation reactor with immobilized cells of Oceanimonas sp. - Songwen Tan; Xuncai Chen; Chunzhi Cui; Yang Hou; Weiguo Li; Hong You (Biotechnology Letters, 2017)

Synergistic Interactions Between Salt-tolerant Rhizobia and Arbuscular Mycorrhizal Fungi on Salinity Tolerance of Sesbania cannabina Plants - Cheng-Gang Ren; Yue-Jie Bai; Cun-Cui Kong; Bian Bian; Zhi-Hong Xie (Journal of Plant Growth Regulation, 2016)

Characterization, promoter analysis and expression of the interleukin-6 gene in blunt snout bream, Megalobrama amblycephala - Xiaoqin Fu; Zhujin Ding; Jun Fan; Huanling Wang; Fengjuan Zhou; Lei Cui; Chen Boxiang; Weimin Wang; Hong Liu (Fish Physiology and Biochemistry, 2016)

The accumulation and health risk of heavy metals in vegetables around a zinc smelter in northeastern China - Bo Li; Yanhong Wang; Yong Jiang; Guochen Li; Jiehua Cui; Ying Wang; Hong Zhang; Shicheng Wang; Sheng Xu; Ruzhen Wang (Environmental Science and Pollution Research, 2016)

Application of high resolution SNP arrays in patients with congenital oral clefts in south China - TING-YING LEI; HONG-TAO WANG; FAN LI; YING-QIU CUI; FANG FU; RU LI; CAN LIAO (Journal of Genetics, 2016)

Multi-resolution graph-based clustering analysis for lithofacies identification from well log data: Case study of intraplatform bank gas fields, Amu Darya Basin - Yu Tian; Hong Xu; Xing-Yang Zhang; Hong-Jun Wang; Tong-Cui Guo; Liang-Jie Zhang; Xing-Lin Gong (Applied Geophysics, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

NF-κB Blockade in Hypothalamic Paraventricular Nucleus Inhibits High-Salt-Induced Hypertension Through NLRP3 and Caspase-1 - Jie Qi; Xiao-Jing Yu; Xiao-Lian Shi; Hong-Li Gao; Qiu-Yue Yi; Hong Tan; Xiao-Yan Fan; Yan Zhang; Xin-Ai Song; Wei Cui; Jin-Jun Liu; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Combined treatment with parathyroid hormone (1–34) and beta-tricalcium phosphate had an additive effect on local bone formation in a rat defect model - Zhou-Shan Tao; Kai-kai Tu; Zheng-Liang Huang; Qiang Zhou; Tao Sun; Hong-Ming Xu; Yu-Long Zhou; Yang-Xun Lv; Wei Cui; Lei Yang (Medical & Biological Engineering & Computing, 2016)

Synthesis process and photocatalytic properties of BiOBr nanosheets for gaseous benzene - Yu Liu; Yongquan Yin; Xueqing Jia; Xiangyu Cui; Canrui Tian; Yuanhua Sang; Hong Liu (Environmental Science and Pollution Research, 2016)

A graphical model for haloanhydrite components and P-wave velocity: A case study of haloanhydrites in Amu Darya Basin - Tong-Cui Guo; Hong-Jun Wang; Long-Xin Mu; Xing-Yang Zhang; Zhi Ma; Yu Tian; Hao-Chen Li (Applied Geophysics, 2016)

Evolutionary direction of processed pseudogenes - Guoqing Liu; Xiangjun Cui; Hong Li; Lu Cai (Science China Life Sciences, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Roseomonas chloroacetimidivorans sp. nov., a chloroacetamide herbicide-degrading bacterium isolated from activated sludge - Cui-Wei Chu; Qing Chen; Cheng-Hong Wang; Hong-Mei Wang; Zhong-Guan Sun; Qin He; Jian He; Jin-Gang Gu (Antonie van Leeuwenhoek, 2016)

Morphological observation, life history and rbc L gene sequence analysis of a new species, Grateloupia variata sp. nov. (Halymeniaceae, Rhodophyta) from Qingdao, China - Cui Cui Cao; Ya Zhuo Li; Hong Wei Wang (Marine Biology Research, 2016)

Factors Associated with Thrombolysis Outcome in Ischemic Stroke Patients with Atrial Fibrillation - Qiuyun Zhao; Xiaobo Li; Wanli Dong; Min Ye; Yongjun Cao; Meijuan Zhang; Qiantao Cheng; Junshan Zhou; Guofang Chen; Ming Yu; Shanshan Hong; Xiue Wei; et al. (Neuroscience Bulletin, 2016)

MdSOS2L1 phosphorylates MdVHA-B1 to modulate malate accumulation in response to salinity in apple - Da-Gang Hu; Cui-Hui Sun; Mei-Hong Sun; Yu-Jin Hao (Plant Cell Reports, 2016)

Designer Self-Assemble Peptides Maximize the Therapeutic Benefits of Neural Stem Cell Transplantation for Alzheimer’s Disease via Enhancing Neuron Differentiation and Paracrine Action - Guo-hong Cui; Shui-jin Shao; Jia-jun Yang; Jian-ren Liu; Hai-dong Guo (Molecular Neurobiology, 2016)

Transgenic NfFeSOD Sedum alfredii plants exhibited profound growth impairments and better relative tolerance to long-term abiotic stresses - Xiang Gao; Wen-Li Ai; Huan Gong; Li-Juan Cui; Bo-Xia Chen; Hong-Yi Luo; Zhong-Chun Zhang; Bao-Sheng Qiu (Plant Biotechnology Reports, 2016)

Role of microRNA-195 in cardiomyocyte apoptosis induced by myocardial ischaemia–reperfusion injury - CHANG-KUI GAO; HUI LIU; CHENG-JI CUI; ZHAO-GUANG LIANG; HONG YAO; YE TIAN (Journal of Genetics, 2016)

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

Developing antibodies from cholinesterase derived from prokaryotic expression and testing their feasibility for detecting immunogen content in Daphnia magna - Hong-cui Liu; Bing-qiang Yuan; Shao-nan Li (Journal of Zhejiang University-SCIENCE B, 2016)

Molecular and pathogenicity characterization of Gallid herpesvirus 2 newly isolated in China from 2009 to 2013 - Yan-ping Zhang; Hong-chao Lv; Ke-yan Bao; Yu-long Gao; Hong-lei Gao; Xiao- le Qi; Hong-yu Cui; Yong-qiang Wang; Kai Li; Li Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2016)

Two pentasaccharide resin glycosides from Argyreia acuta - Yong-Qin Yin; Jie-Tao Pan; Bang-Wei Yu; Hong-Hua Cui; You-Shao Yan; Yan-Fen Chen (Natural Product Research, 2016)

Trends in the prevalence of heart diseases over a ten-year period from single-center observations based on a large echocardiographic database - Hao Lu; Wen-zhi Pan; Quan Wan; Lei-lei Cheng; Xian-hong Shu; Cui-zhen Pan; Ju-ying Qian; Jun-bo Ge (Journal of Zhejiang University-SCIENCE B, 2016)

A novel Halomonas ventosae-specific virulent halovirus isolated from the Qiaohou salt mine in Yunnan, Southwest China - Chao-Qun Fu; Qin Zhao; Zhi-Ying Li; Yong-Xia Wang; Shi-Ying Zhang; Yong-Hong Lai; Wei Xiao; Xiao-Long Cui (Extremophiles, 2016)

PPR protein PDM1/SEL1 is involved in RNA editing and splicing of plastid genes in Arabidopsis thaliana - Hong-Dao Zhang; Yong-Lan Cui; Chao Huang; Qian-Qian Yin; Xue-Mei Qin; Te Xu; Xiao-Fang He; Yi Zhang; Zi-Ran Li; Zhong-Nan Yang (Photosynthesis Research, 2015)

Potential candidate cells for constructing tissue-engineered lacrimal duct epithelium: a histological and cytological study in rabbits - Chen Xie; Xiu-yi Li; Hong-guang Cui (Journal of Zhejiang University-SCIENCE B, 2015)

Improved properties of bone and cartilage tissue from 3D inkjet-bioprinted human mesenchymal stem cells by simultaneous deposition and photocrosslinking in PEG-GelMA - Guifang Gao; Arndt F. Schilling; Karen Hubbell; Tomo Yonezawa; Danh Truong; Yi Hong; Guohao Dai; Xiaofeng Cui (Biotechnology Letters, 2015)

New norditerpenoid alkaloids from Aconitum vilmorinianum Komarov - Cui-Ling Chen; Wen-Hong Tan; Yan Wang; Zhi-Ge Xue; Chun-Ping Wan; Zhu-Ya Yang; Zhi-Hong Zhou; Xiao-Xia Ma (Journal of Natural Medicines, 2015)

Pb uptake and tolerance in the two selected mangroves with different root lignification and suberization - Hao Cheng; You-Shao Wang; Yong Liu; Zhi-Hong Ye; Mei-Lin Wu; Cui-Ci Sun (Ecotoxicology, 2015)

The diversity of coral associated bacteria and the environmental factors affect their community variation - Yan-Ying Zhang; Juan Ling; Qing-Song Yang; You-Shao Wang; Cui-Ci Sun; Hong-Yan Sun; Jing-Bin Feng; Yu-Feng Jiang; Yuan-Zhou Zhang; Mei-Lin Wu; Jun-De Dong (Ecotoxicology, 2015)

Therapeutic potential of human umbilical cord blood mesenchymal stem cells on erectile function in rats with cavernous nerve injury - Jian-Qiang Zhu; Hong-Kai Lu; Zhi-Qiang Cui; Yong-Chuan Wang; Yong-Hui Li; Weixin Zhao; Qiang Fu; Yue-Min Xu; Yong Xu; Lu-Jie Song (Biotechnology Letters, 2015)

Phylogeny and taxonomy of the genus Abundisporus (Polyporales, Basidiomycota) - Chang-Lin Zhao; Hong Chen; Jie Song; Bao-Kai Cui (Mycological Progress, 2015)

Isolation and full-genome sequence of two reticuloendotheliosis virus strains from mixed infections with Marek’s disease virus in China - Ke-yan Bao; Yan-ping Zhang; Hui-wen Zheng; Hong-chao Lv; Yu-long Gao; Jing-fei Wang; Hong-lei Gao; Xiao-le Qi; Hong-yu Cui; Yong-qiang Wang; Xian-gang Ren; Xiao-mei Wang; et al. (Virus Genes, 2015)

Activation of NOD1 by DAP contributes to myocardial ischemia/reperfusion injury via multiple signaling pathways - Hui Yang; Nan Li; Li-Na Song; Lei Wang; Cui Tian; Chao-Shu Tang; Jie Du; Hui-Hua Li; Xiao-Hong Yu; Hong-Xia Wang (Apoptosis, 2015)

Characteristics of porosity and permeability layer of fossil Halimeda reef mineral rock of Miocene in the Xisha Islands and its genetic model - Hong Xu; Yurui Zhu; G. P. Eberli; Wei Luo; Xinwei Zhao; Ying Cai; Xinyu Liu; Guijing Yan; Bolin Zhang; Kai Wei; Ruyong Cui (Acta Oceanologica Sinica, 2015)

Methane-rich water induces cucumber adventitious rooting through heme oxygenase1/carbon monoxide and Ca2+ pathways - Weiti Cui; Fang Qi; Yihua Zhang; Hong Cao; Jing Zhang; Ren Wang; Wenbiao Shen (Plant Cell Reports, 2015)

Morphological characters and molecular data reveal two new species of Postia (Basidiomycota) from China - Lu-Lu Shen; Hong-Xia Liu; Bao-Kai Cui (Mycological Progress, 2015)

Comparison of chemical, electrical, and combined activation methods for in vitro matured porcine oocytes - Shuai Liu; Kuiqing Cui; Hong Li Li; Jun Ming Sun; Xing Rong Lu; Kai Yuan Shen; Qing You Liu; De Shun Shi (In Vitro Cellular & Developmental Biology - Animal, 2015)

Alpha-Synuclein Oligomerization in Manganese-Induced Nerve Cell Injury in Brain Slices: A Role of NO-Mediated S-Nitrosylation of Protein Disulfide Isomerase - Bin Xu; Cui-Hong Jin; Yu Deng; Wei Liu; Tian-Yao Yang; Shu Feng; Zhao-Fa Xu (Molecular Neurobiology, 2014)

Genomewide identification and expression analysis of the ARF gene family in apple - XIAO-CUI LUO; MEI-HONG SUN; RUI-RUI XU; HUAI-RUI SHU; JIA-WEI WANG; SHI-ZHONG ZHANG (Journal of Genetics, 2014)

Knockdown of NOB1 expression inhibits the malignant transformation of human prostate cancer cells - Xiangmin Zhang; Dongxu Zhang; Fajun Qu; Yi Hong; Jianwei Cao; Xiuwu Pan; Lin Li; Yi Huang; Hai Huang; Lei Yin; Lu Chen; Jizhong Ren; et al. (Molecular and Cellular Biochemistry, 2014)

Role of spinal GABAA receptor reduction induced by stress in rat thermal hyperalgesia - Xuelian Ma; Weiying Bao; Xiujun Wang; Zhilong Wang; Qiaoran Liu; Zhenyu Yao; Di Zhang; Hong Jiang; Shuang Cui (Experimental Brain Research, 2014)

Ameliorating Effects of Combined Curcumin and Desferrioxamine on 6-OHDA-Induced Rat Mode of Parkinson’s Disease - Hua Lv; Jun Liu; Li Wang; Hong Zhang; Shuqi Yu; Zhiwei Li; Feng Jiang; Yu Niu; Jie Yuan; Xiaoli Cui; Wenxiu Wang (Cell Biochemistry and Biophysics, 2014)

Protective Effect of Recombinant Human Brain Natriuretic Peptide on Acute Renal Injury Induced by Endotoxin in Canines - Nan Li; Hong-Xu Jin; Zhi Song; Chuan-Zhe Bai; Yan Cui; Yan Gao (Cell Biochemistry and Biophysics, 2014)

Cloning and characterization of SnRK2 subfamily II genes from Nicotiana tabacum - Hongying Zhang; Hongfang Jia; Guoshun Liu; Shengnan Yang; Songtao Zhang; Yongxia Yang; Peipei Yang; Hong Cui (Molecular Biology Reports, 2014)

The checkpoint 1 kinase inhibitor LY2603618 induces cell cycle arrest, DNA damage response and autophagy in cancer cells - Feng-Ze Wang; Hong-rong Fei; Ying-Jie Cui; Ying-Kun Sun; Zhao-Mei Li; Xue-Ying Wang; Xiao-Yi Yang; Ji-Guo Zhang; Bao-Liang Sun (Apoptosis, 2014)

Molecular cloning and characterization of NPR1 gene from Arachis hypogaea - Qi Wu; Xiu Zhen Wang; Yue Yi Tang; Hong Tao Yu; Yu Fei Ding; Chuan De Yang; Feng Gao Cui; Jian Cheng Zhang; Chuan Tang Wang (Molecular Biology Reports, 2014)

Hydrogen sulfide delays nicotinamide-induced premature senescence via upregulation of SIRT1 in human umbilical vein endothelial cells - Meihua Zheng; Weili Qiao; Jie Cui; Lei Liu; Hong Liu; Zhirong Wang; Changdong Yan (Molecular and Cellular Biochemistry, 2014)

Halomonas qiaohouensis sp. nov., isolated from salt mine soil in southwest China - Yong-Xia Wang; Wei Xiao; Ming-Hua Dong; Qin Zhao; Zhi-Ying Li; Yong-Hong Lai; Xiao-Long Cui (Antonie van Leeuwenhoek, 2014)

Overexpression of Glycine soja WRKY20 enhances both drought and salt tolerance in transgenic alfalfa (Medicago sativa L.) - Lili Tang; Hua Cai; Hong Zhai; Xiao Luo; Zhenyu Wang; Lin Cui; Xi Bai (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Characterizing the heavy metal-complexing potential of fluorescent water-extractable organic matter from composted municipal solid wastes using fluorescence excitation–emission matrix spectra coupled with parallel factor analysis - Xiao-Song He; Bei-Dou Xi; Hong-Wei Pan; Xiang Li; Dan Li; Dong-Yu Cui; Wen-Bin Tang; Ying Yuan (Environmental Science and Pollution Research, 2014)

Cloning and characterization of NtSnRK2.7 and NtSnRK2.8 genes involved in abiotic stress responses from Nicotiana tabacum - Hongying Zhang; Hongfang Jia; Guoshun Liu; Shengnan Yang; Songtao Zhang; Yongxia Yang; Hong Cui (Acta Physiologiae Plantarum, 2014)

Analysis of synonymous codon usage in enterovirus 71 - Hua Zhang; Hong-wei Cao; Feng-qi Li; Zi-ye Pan; Zhi-jun Wu; Yan-hong Wang; Yu-dong Cui (VirusDisease, 2014)

Increased body weight induced by perinatal exposure to bisphenol A was associated with down-regulation zinc-alpha2-glycoprotein expression in offspring female rats - Ling Zhang; Hong Yuan Zhang; Cui Cui Ma; Wei Wei; Li Hong Jia (Molecular & Cellular Toxicology, 2014)

M3 mAChR-mediated IL-8 expression through PKC/NF-κB signaling pathways - Zu-Peng Xu; Yun Song; Kai Yang; Wei Zhou; Li-Na Hou; Liang Zhu; Hong-Zhuan Chen; Yong-Yao Cui (Inflammation Research, 2014)

Influence of the composition and removal characteristics of organic matter on heavy metal distribution in compost leachates - Xiao-Song He; Bei-Dou Xi; Dan Li; Xu-Jing Guo; Dong-Yu Cui; Hong-Wei Pan; Yan Ma (Environmental Science and Pollution Research, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Molecular cloning and characterization of 5-enolpyruvylshikimate-3-phosphate synthase gene from Convolvulus arvensis L. - Zhao-Feng Huang; Chao-Xian Zhang; Hong-Juan Huang; Shou-Hui Wei; Yan Liu; Hai-Lan Cui; Jing-Chao Chen; Long Yang; Jin-Yi Chen (Molecular Biology Reports, 2014)

Detection of quantitative trait loci (QTLs) for seedling traits and drought tolerance in wheat using three related recombinant inbred line (RIL) populations - Hong Zhang; Fa Cui; Honggang Wang (Euphytica, 2014)

Inhibition of 12/15 lipoxygenase by baicalein reduces myocardial ischemia/reperfusion injury via modulation of multiple signaling pathways - Lina Song; Hui Yang; Hong-Xia Wang; Cui Tian; Yu Liu; Xiang-Jun Zeng; Erhe Gao; Yu-Ming Kang; Jie Du; Hui-Hua Li (Apoptosis, 2014)

Comparison of organic acid levels and L-IdnDH expression in Chinese-type and European-type grapes - Ya-Qin Wen; Jing Cui; Ye Zhang; Chang-Qing Duan; Qiu-Hong Pan (Euphytica, 2014)

Association of functional polymorphisms in the MxA gene with susceptibility to enterovirus 71 infection - Xiaoai Zhang; Hongmei Xu; Xiaodan Chen; Xiujun Li; Xianjun Wang; Shujun Ding; Renli Zhang; Lijuan Liu; Cui He; Lu Zhuang; Hao Li; Panhe Zhang; et al. (Human Genetics, 2014)

A new rainwater harvesting and recycling system for transforming sloping land into terraced farmland - Yuan-zhi Shi; Yue-hong Wang; Yuan-lai Cui; Shi-wu Wang; Yu-shuai Zhang (Journal of Mountain Science, 2014)

Socio-demographic and clinical characteristics of heavy and non-heavy smokers among schizophrenia inpatients in a Chinese Han population - Xiang Yang Zhang; Da Chun Chen; Yun Long Tan; Mei Hong Xiu; Jingyi Cui; Li Hui; Fu De Yang; Thomas R Kosten (Psychopharmacology, 2014)

An improved culture solution technique for Plasmodiophora brassicae infection and the dynamic infection in the root hair - Hong-chun Luo; Guo-kang Chen; Cui-ping Liu; Yun Huang; Chong-gang Xiao (Australasian Plant Pathology, 2014)

Characterization of OsMIK in a rice mutant with reduced phytate content reveals an insertion of a rearranged retrotransposon - Hai-Jun Zhao; Hai-Rui Cui; Xiu-Hong Xu; Yuan-Yuan Tan; Jun-Jie Fu; Guo-Zhen Liu; Yves Poirier; Qing-Yao Shu (Theoretical and Applied Genetics, 2013)

Effect of bisphenol A exposure during early development on glucose metabolism and adipokine expression in adolescent female rats - Ling Zhang; Hong Yuan Zhang; Cui Cui Ma; Ling Ling Zhai; Li Hong Jia (Molecular & Cellular Toxicology, 2013)

Survey of mycotic mastitis in dairy cows from Heilongjiang Province, China - Yulong Zhou; Yachao Ren; Chunling Fan; Hong Shao; Zecai Zhang; Wenbin Mao; Chunbo Wei; Hongbo Ni; Zhanbo Zhu; Xilin Hou; Fanze Piao; Yudong Cui (Tropical Animal Health and Production, 2013)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

3-O-Acetyloleanolic acid exhibits anti-angiogenic effects and induces apoptosis in human umbilical vein endothelial cells - En-Ji Cui; Jeon Hwang-Bo; Jong-Hwa Park; Nam-In Baek; Jiyoung Kim; Seong Gil Hong; In Sik Chung (Biotechnology Letters, 2013)

Eremophilane derivatives from Senecio dianthus - Shuai Huang; Xian-li Zhou; Hong-yan Wang; Cui-juan Wang; Xiao-li Zhou; Feng Xiao; Jie Weng (Journal of Natural Medicines, 2013)

Rapid development of 36 polymorphic microsatellite markers for Tetranychus truncatus by transferring from Tetranychus urticae - Cheng Ge; Jing-Tao Sun; Yu-Nan Cui; Xiao-Yue Hong (Experimental and Applied Acarology, 2013)

Genomic sequence analysis of a new reassortant infectious bursal disease virus from commercial broiler flocks in central China - Pei Cui; Shi-Jie Ma; Yu-Geng Zhang; Xin-Sheng Li; Xiao-Yun Gao; Bao-An Cui; Hong-Ying Chen (Archives of Virology, 2013)

Conditional and unconditional QTL mapping of drought-tolerance-related traits of wheat seedling using two related RIL populations - HONG ZHANG; FA CUI; LIN WANG; JUN LI; ANMING DING; CHUNHUA ZHAO; YINGUANG BAO; QIUPING YANG; HONGGANG WANG (Journal of Genetics, 2013)

Verapamil reverses cardiac iron overload in streptozocin-induced diabetic rats - Hong-li Shan; Yan Wang; Jian-wei Wu; Peng-zhou Hang; Xin Li; Li-hua Sun; Jian-cui Qi; Yu-ying Mao; Zhi-dan Sun; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

A novel steroidal alkaloid from Fritillaria shuchengensis - Shuai Huang; Xian-li Zhou; Juan Wen; Cui-juan Wang; Hong-yan Wang; Lian-hai Shan; Jie Weng (Journal of Natural Medicines, 2013)

Molecular detection and genomic characterization of Torque teno sus virus 1 and 2 from domestic pigs in central China - Kun Li; Lin-Qing Wang; Yu-Yang Wu; An-Jun Chao; Quan-Wei Lu; Zhan-Yong Wei; Bao-An Cui; Hong-Ying Chen (Virus Genes, 2013)

MicroRNA-185 suppresses proliferation, invasion, migration, and tumorigenicity of human prostate cancer cells through targeting androgen receptor - Fajun Qu; Xingang Cui; Yi Hong; Junkai Wang; Yao Li; Lu Chen; Yushan Liu; Yi Gao; Danfeng Xu; Quanxing Wang (Molecular and Cellular Biochemistry, 2013)

The possible climate impact on the collapse of an ancient urban city in Mu Us Desert, China - Jianxin Cui; Hong Chang (Regional Environmental Change, 2013)

Duration of sucrose preculture is critical for shoot regrowth of in vitro-grown apple shoot-tips cryopreserved by encapsulation-dehydration - Chao-Hong Feng; Zhen-Hua Cui; Bai-Quan Li; Long Chen; Yan-Li Ma; Yan-Hua Zhao; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Effect of sinomenine on vascular smooth muscle cell dedifferentiation and neointima formation after vascular injury in mice - Lihua Zhu; Yarong Hao; Hongjing Guan; Changping Cui; Song Tian; Da Yang; Xinan Wang; Shuming Zhang; Lang Wang; Hong Jiang (Molecular and Cellular Biochemistry, 2013)

Low nitrogen-induced expression of cyclophilin in Nicotiana tabacum - Huijuan Yang; Li Xu; Hong Cui; Boxiong Zhong; Guoshun Liu; Hongzhi Shi (Journal of Plant Research, 2013)

Cerium Chloride Improves Protein and Carbohydrate Metabolism of Fifth-Instar Larvae of Bombyx mori Under Phoxim Toxicity - Bing Li; Yi Xie; Zhe Cheng; Jie Cheng; Rengping Hu; Xuezi Sang; Suxin Gui; Qingqing Sun; Xiaolan Gong; Yaling Cui; Weide Shen; Fashui Hong (Biological Trace Element Research, 2012)

Beta2-Adrenergic Receptor and Astrocyte Glucose Metabolism - Jun-hong Dong; Xin Chen; Min Cui; Xiao Yu; Qi Pang; Jin-peng Sun (Journal of Molecular Neuroscience, 2012)

Increased Th17 cell frequency concomitant with decreased Foxp3+ Treg cell frequency in the peripheral circulation of patients with carotid artery plaques - Zhen-dong Liu; Lin Wang; Fang-hong Lu; Hui Pan; Ying-xin Zhao; Shu-jian Wang; Shang-wen Sun; Cui-ling Li; Xiao-liang Hu (Inflammation Research, 2012)

Functional recombinant human anti-HBV antibody expressed in milk of transgenic mice - Ran Zhang; Dan Cui; Hong Wang; Chuan Li; Xin Yao; Yaofeng Zhao; Mifang Liang; Ning Li (Transgenic Research, 2012)

Detection of Autoantibodies and Increased Concentrations of Interleukins in Plasma from Patients with Tourette's Syndrome - Yu-hang Cheng; Yi Zheng; Fan He; Jian-hong Yang; Wen-biao Li; Min-ling Wang; De-yan Cui; Ying Chen (Journal of Molecular Neuroscience, 2012)

Characteristics and assessment of phthalate esters in urban dusts in Guangzhou city, China - Qing Lan; Kunyan Cui; Feng Zeng; Fang Zhu; Hong Liu; Hongli Chen; Yongqing Ma; Jiaxin Wen; Tiangang Luan; Guoquan Sun; Zunxiang Zeng (Environmental Monitoring and Assessment, 2012)

Erratum to: The Toxicological Effects in Brain of Mice Following Exposure to Cerium Chloride - Haiquan Zhao; Zhe Cheng; Jie Cheng; Renping Hu; Yi Che; Yaling Cui; Ling Wang; Fashui Hong (Biological Trace Element Research, 2012)

Effects of Added CeCl3 on Resistance of Fifth-Instar Larvae of Silkworm to Bombyx mori Nucleopolyhedrovirus Infection - Bing Li; Yi Xie; Zhe Cheng; Jie Cheng; Rengping Hu; Yaling Cui; Xiaolan Gong; Weide Shen; Fashui Hong (Biological Trace Element Research, 2012)

Upregulation of Heme Oxygenase-1 by Acteoside Through ERK and PI3 K/Akt Pathway Confer Neuroprotection Against Beta-Amyloid-Induced Neurotoxicity - Hong-Quan Wang; Yu-Xia Xu; Cui-Qing Zhu (Neurotoxicity Research, 2012)

Optimization of ethylenediamine-grafted multiwalled carbon nanotubes for solid-phase extraction of lead cations - Zhang-Jun Hu; Yang Cui; Shan Liu; Yuan Yuan; Hong-Wen Gao (Environmental Science and Pollution Research, 2012)

Molecular characterization of two prunus necrotic ringspot virus isolates from Canada - Hongguang Cui; Ni Hong; Guoping Wang; Aiming Wang (Archives of Virology, 2012)

TNF-α Increases Bone Marrow Mesenchymal Stem Cell Migration to Ischemic Tissues - Qiong Xiao; Shi-kun Wang; Hua Tian; Li Xin; Zhi-geng Zou; Yan-lai Hu; Cui-ming Chang; Xue-ying Wang; Qun-sheng Yin; Xiang-hong Zhang; Li-yan Wang (Cell Biochemistry and Biophysics, 2012)

Inhibitor of DNA-binding-1/inhibitor of differentiation-1 (ID-1) is implicated in various aspects of gastric cancer cell biology - Wei Li; Chun-Hua Zhang; Yi-Lin Hong; Jun Li; Yong-Mei Hu; Cui-Fen Zhao (Molecular Biology Reports, 2012)

Transdifferentiation of human adipose-derived stem cells into urothelial cells: potential for urinary tract tissue engineering - Jian-Guo Shi; Wei-Jun Fu; Xiao-Xiong Wang; Yong-De Xu; Gang Li; Bao-Fa Hong; Kun Hu; Fu-Zhai Cui; Yan Wang; Xu Zhang (Cell and Tissue Research, 2012)

Physiological responses to salt stress of T2 alfalfa progenies carrying a transgene for betaine aldehyde dehydrogenase - Li-Ping Yan; Cui-Lan Liu; Hui-Min Liang; Xiu-Hong Mao; Fei Wang; Cai-Hong Pang; Jing Shu; Yang Xia (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Soluble expression and purification of Brucella cell surface protein (BCSP31) of Brucella melitensis and preparation of anti-BCSP31 monoclonal antibodies - Lei Zhang; Xing An Wu; Fang Lin Zhang; Cui Hong An; Yang Xin Sun; Wen Tao Bai; Zhi Kai Xu (Molecular Biology Reports, 2012)

Ethyl pyruvate reduces myocardial ischemia and reperfusion injury by inhibiting high mobility group box 1 protein in rats - Xiaorong Hu; Bo Cui; Xiaoya Zhou; Changwu Xu; Zhibing Lu; Hong Jiang (Molecular Biology Reports, 2012)

The Ran-binding protein RanBPM can depress the NF-κB pathway by interacting with TRAF6 - Lan Wang; Chengbo Fu; Yingbin Cui; Yunfei Xie; Yuhe Yuan; Xin Wang; Hong Chen; Bing-Ren Huang (Molecular and Cellular Biochemistry, 2012)

A Promising CdSe@CdS-Quantum Dots-Cysteine for the Determination of Trace IgE by Solid Substrate Room Temperature Phosphorescence Immunoassay - Jia-Ming Liu; Li-ping Lin; Zhen-Bo Liu; Min-Lan Yang; Xin-xing Wang; Li-hong Zhang; Ma-lin Cui; Li Jiao (Journal of Fluorescence, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Liver Injury and Its Molecular Mechanisms in Mice Caused by Exposure to Cerium Chloride - Haiquan Zhao; Jie Cheng; Jingwei Cai; Zhe Cheng; Yaling Cui; Guodong Gao; Renping Hu; Xiaolan Gong; Ling Wang; Fashui Hong (Archives of Environmental Contamination and Toxicology, 2012)

The Co-expression of USP22 and BMI-1 May Promote Cancer Progression and Predict Therapy Failure in Gastric Carcinoma - Dong-Dong Yang; Bin-Bin Cui; Ling-yu Sun; Hong-qun Zheng; Qi Huang; Jin-Xue Tong; Qi-Fan Zhang (Cell Biochemistry and Biophysics, 2011)

The Toxicological Effects in Brain of Mice Following Exposure to Cerium Chloride - Haiquan Zha; Zhe Cheng; Jie Chen; Renping Hu; Yi Che; Yaling Cui; Ling Wang; Fashui Hong (Biological Trace Element Research, 2011)

Complete genomic sequence analysis of a highly virulent isolate revealed a novel strain of Sugarcane mosaic virus - Bo Gao; Xiao-Wen Cui; Xiang-Dong Li; Chun-Qing Zhang; Hong-Qin Miao (Virus Genes, 2011)

Two-dimensional numerical model for debris flows in the Jiangjia Gully, Yunnan Province - Hong Peng; Yanxin Zhao; Peng Cui; Wanshun Zhang; Xuejiao Chen; Xiaoqing Chen (Journal of Mountain Science, 2011)

17beta-estradiol attenuates pressure overload-induced myocardial hypertrophy through regulating caveolin-3 protein in ovariectomized female rats - Yu-Hong Cui; Zhi Tan; Xiao-Dong Fu; Qiu-Ling Xiang; Jin-Wen Xu; Ting-Huai Wang (Molecular Biology Reports, 2011)

Synthesis and evaluation of κ-opioid receptor agonistic activity and antinociceptive effect of novel morphine analogues, 7α-phenyl-6α,14α-endo-etheno-tetrahydrothebaine with substituted o-, m- and p-amino group - Hong Qi; Wei Li; Yu Qiu; Yong-yao Cui; Jian Ma; Xiao-ling Gao; Yi-bin Zeng; Jie Yang; Yun Tang; Xing-hai Wang; Wei Sheng; Qiong Xie; et al. (Medicinal Chemistry Research, 2011)

Analysis of phage Mu DNA transposition by whole-genome Escherichia coli tiling arrays reveals a complex relationship to distribution of target selection protein B, transcription and chromosome architectural elements - Jun Ge; Zheng Lou; Hong Cui; Lei Shang; Rasika M Harshey (Journal of Biosciences, 2011)

Effective mitigation of nitrate leaching and nitrous oxide emissions in intensive vegetable production systems using a nitrification inhibitor, dicyandiamide - Min Cui; Xuecheng Sun; Chengxiao Hu; Hong J. Di; Qiling Tan; Changsheng Zhao (Journal of Soils and Sediments, 2011)

Effect of neuronal excitotoxicity on Munc18-1 distribution in nuclei of rat hippocampal neuron and primary cultured neuron - Yan-Ping Zhang; Ping Wan; Hong-Quan Wang; Hong Zhao; Yu-Xia Xu; Ru Yang; Cui-Qing Zhu (Neuroscience Bulletin, 2011)

Abnormal expression of NRF-2α in hepatocellular carcinoma identified with a newly prepared monoclonal antibody against human NRF-2α protein - Ya Qing Zhang; Kai Nan Li; Ji Hong Cui; Yan Fang Liu; Shou Jing Yang (Molecular Biology Reports, 2011)

Up-regulation of mitochondrial antioxidation signals in ovarian cancer cells with aggressive biologic behavior - Yue Wang; Li Dong; Heng Cui; Dan-hua Shen; Ying Wang; Xiao-hong Chang; Tian-yun Fu; Xue Ye; Yuan-yang Yao (Journal of Zhejiang University-SCIENCE B, 2011)

P38-Nrf-2 Signaling Pathway of Oxidative Stress in Mice Caused by Nanoparticulate TiO2 - Jue Wang; Na Li; Lei Zheng; Sisi Wang; Ying Wang; Xiaoyang Zhao; Yanmei Duan; Yaling Cui; Min Zhou; Jingwei Cai; Songjie Gong; Han Wang; et al. (Biological Trace Element Research, 2011)

Isolation of a cinnamoyl CoA reductase gene involved in formation of stone cells in pear (Pyrus pyrifolia) - Xiao-Peng Lu; Yong-Zhong Liu; Ji-Cui An; Hong-Ju Hu; Shu-Ang Peng (Acta Physiologiae Plantarum, 2011)

RNA inference-mediated caveolin-1 down-regulation decrease estrogen receptor alpha (ERα) signaling in human mammary epithelial cells - Xi Wang; Shuang Feng; Hong Zhang; Yang Wang; Yuying Cui; Zhaoyi Wang; Jing Liu; Wei Zou (Molecular Biology Reports, 2011)

Evaluation of the hepatoprotective and antioxidant activities of Rubus parvifolius L. - Jie Gao; Cui-rong Sun; Jie-hong Yang; Jian-mei Shi; Yue-guang Du; Yu-yan Zhang; Jin-hui Li; Hai-tong Wan (Journal of Zhejiang University-SCIENCE B, 2011)

Effects of nitrogen form on growth, CO2 assimilation, chlorophyll fluorescence, and photosynthetic electron allocation in cucumber and rice plants - Yan-hong Zhou; Yi-li Zhang; Xue-min Wang; Jin-xia Cui; Xiao-jian Xia; Kai Shi; Jing-quan Yu (Journal of Zhejiang University-SCIENCE B, 2011)

The Wenchuan Earthquake (May 12, 2008), Sichuan Province, China, and resulting geohazards - Peng Cui; Xiao-Qing Chen; Ying-Yan Zhu; Feng-Huan Su; Fang-Qiang Wei; Yong-Shun Han; Hong-Jiang Liu; Jian-Qi Zhuang (Natural Hazards, 2011)

The α-isoform of class II phosphoinositide 3-kinase is necessary for the activation of ERK but not Akt/PKB - Z. G. Cui; N. Y. Hong; H. K. Kang; D. H. Lee; Y. K. Lee; D. B. Park (Molecular and Cellular Biochemistry, 2011)

Effects of Soil Polycyclic Musk and Cadmium on Pollutant Uptake and Biochemical Responses of Wheat (Triticum aestivum) - Cui-hong Chen; Qi-xing Zhou; Zhang Cai; Ying-ying Wang (Archives of Environmental Contamination and Toxicology, 2010)

Increase of isoflavones in soybean callus by Agrobacterium-mediated transformation - Nan Jiang; Eun-Hee Jeon; Jung-Hun Pak; Tae-Joung Ha; In-Youl Baek; Woo-Suk Jung; Jai-Heon Lee; Doh-Hoon Kim; Hong-Kyu Choi; Zheng Cui; Young-Soo Chung (Plant Biotechnology Reports, 2010)

Interaction Between Nanoparticulate Anatase TiO2 and Lactate Dehydrogenase - Yanmei Duan; Na Li; Chao Liu; Huiting Liu; Yaling Cui; Han Wang; Fashui Hong (Biological Trace Element Research, 2010)

Molecular characterization of T-DNA integration sites in transgenic birch - Fan-Suo Zeng; Ya-Guang Zhan; Hong-Cui Zhao; Ying Xin; Feng-Hui Qi; Chuan-Ping Yang (Trees, 2010)

Overexpression of G10H and ORCA3 in the hairy roots of Catharanthus roseus improves catharanthine production - Cui-Ting Wang; Hua Liu; Xiao-Shu Gao; Hong-Xia Zhang (Plant Cell Reports, 2010)

Glutamate enhances the surface distribution and release of Munc18 in cerebral cortical neurons - Ping Wan; Yan-Ping Zhang; Jie Yan; Yu-Xia Xu; Hong-Quan Wang; Ru Yang; Cui-Qing Zhu (Neuroscience Bulletin, 2010)

Salicylic Acid Reduces Napropamide Toxicity by Preventing Its Accumulation in Rapeseed (Brassica napus L.) - Jing Cui; Rui Zhang; Guo Lin Wu; Hong Mei Zhu; Hong Yang (Archives of Environmental Contamination and Toxicology, 2010)

Molecular characterization and association analysis of porcine PANE1 gene - Honggang Huang; Hong Deng; Yiling Yang; Zhonglin Tang; Shulin Yang; Yulian Mu; Wentao Cui; Jing Yuan; Zhenfang Wu; Kui Li (Molecular Biology Reports, 2010)

Improving Cellular Properties for Genetic Manipulation by Dispersed Growing Mutagenesis in Myxococcus fulvus HW-1 - Cui-ying Zhang; Ke Cai; Zhi-hong Wu; Yue-zhong Li (Current Microbiology, 2010)

Sanchi ginseng (Panax notoginseng (Burkill) F. H. Chen) in China: distribution, cultivation and variations - Hong Bo Guo; Xiu Ming Cui; Na An; Ge Ping Cai (Genetic Resources and Crop Evolution, 2010)

Mechanism of the Formation for Thoracic Impedance Change - Ming-Xing Kuang; Qiu-Jin Xiao; Chao-Ying Cui; Nan-Zhen Kuang; Wen-Qin Hong; Ai-Rong Hu (Annals of Biomedical Engineering, 2010)

GmRFP1 encodes a previously unknown RING-type E3 ubiquitin ligase in Soybean (Glycine max) - Qiu-Li Du; Wen-Zhuo Cui; Chun-Hong Zhang; De-Yue Yu (Molecular Biology Reports, 2010)

Increased serum interleukin 17 in patients with systemic lupus erythematosus - Xue-Fei Zhao; Hai-Feng Pan; Hui Yuan; Wen-Hui Zhang; Xiang-Pei Li; Gui-Hong Wang; Guo-Cui Wu; Hong Su; Fa-Ming Pan; Wen-Xian Li; Lian-Hong Li; Guo-Ping Chen; et al. (Molecular Biology Reports, 2010)

Functional polymorphisms of matrix metallopeptidase-9 and risk of coronary artery disease in a Chinese population - Hong Zhi; Hua Wang; Liqun Ren; Zhiyang Shi; Haiyan Peng; Lunbiao Cui; Genshan Ma; Xingzhou Ye; Yi Feng; Chengxing Shen; Xiangjun Zhai; Chenyu Zhang; et al. (Molecular Biology Reports, 2010)

Fluroxypyr triggers oxidative damage by producing superoxide and hydrogen peroxide in rice (Oryza sativa) - Guo Lin Wu; Jing Cui; Ling Tao; Hong Yang (Ecotoxicology, 2010)

A new treatment of depression for drainage network extraction based on DEM - Yan Wang; Hong Peng; Peng Cui; Wanshun Zhang; Fei Qiao; Cai’er Chen (Journal of Mountain Science, 2009)

Effect of phylogeny, life history and habitat correlates on seed germination of 69 arid and semi-arid zone species from northwest China - Ju Hong Wang; Carol C. Baskin; Xian Liang Cui; Guo Zhen Du (Evolutionary Ecology, 2009)

Activation of extracellular signal-regulated kinase in the anterior cingulate cortex contributes to the induction of long-term potentiation in rats - Hong Cao; Yi-Hui Cui; Zhi-Qi Zhao; Xiao-Hua Cao; Yu-Qiu Zhang (Neuroscience Bulletin, 2009)

Selective inhibition of the cyanobacterium, Microcystis, by a Streptomyces sp. - Xiu-Hong Hua; Jian-Hong Li; Ju-Jiao Li; Li-Hua Zhang; Yan Cui (Biotechnology Letters, 2009)

Nitric oxide inhibits the replication cycle of porcine parvovirus in vitro - Zhan-Yong Wei; Xue-Bin Wang; Xiao-Dong Ning; Ya-Bin Wang; Hong-Ying Zhang; Dong-Fang Wang; Hong-Ying Chen; Bao-An Cui (Archives of Virology, 2009)

QTLs of cold tolerance-related traits at the booting stage for NIL-RILs in rice revealed by SSR - Yawen Zeng; Shuming Yang; Hong Cui; Xiaojuan Yang; Liming Xu; Juan Du; Xiaoying Pu; Zichao Li; Zaiquan Cheng; Xingqi Huang (Genes & Genomics, 2009)

Halomonas sediminis sp. nov., a new halophilic bacterium isolated from salt-lake sediment in China - Heng-Yu Huang; Yi-Guang Chen; Yong-Xia Wang; Ji-Hui Liu; Shu-Kun Tang; Qian Peng; Meng-Liang Wen; Hong Yu; Xiao-Long Cui (Extremophiles, 2008)

Effects and complications of placement of motility coupling post in porous polyethylene orbital implants - Hong-guang Cui; Rong-rong Hu; Hui-yan Li; Wei Han (Journal of Zhejiang University-SCIENCE B, 2008)

Bacterial diversity in sediments of the eutrophic Guanting Reservoir, China, estimated by analyses of 16S rDNA sequence - Jian Hang Qu; Hong Li Yuan; En Tao Wang; Cui Li; Huai Zeng Huang (Biodiversity and Conservation, 2008)

A novel fibrinolytic enzyme from Cordyceps militaris, a Chinese traditional medicinal mushroom - Li Cui; Ming Sheng Dong; Xiao Hong Chen; Mei Jiang; Xin Lv; Guijun Yan (World Journal of Microbiology and Biotechnology, 2008)

Molecular characterization and phylogenetic analysis of membrane protein genes of porcine epidemic diarrhea virus isolates in China - Jian-Fei Chen; Dong-Bo Sun; Cheng-Bao Wang; Hong-Yan Shi; Xiao-Chen Cui; Sheng-Wang Liu; Hua-Ji Qiu; Li Feng (Virus Genes, 2008)

New antibiotic with typical plant anthraquinone structure obtained studying terrestrial and marine Streptomycetes - Hong Xia Cui; Khaled A. Shaaban; Mirko Schiebel; Song Qin; Hartmut Laatsch (World Journal of Microbiology and Biotechnology, 2008)

Conspecific Sharing of Breeding Sites by Anopheline Female Mosquitoes (Diptera: Culicidae) Inferred from Microsatellite Markers - Hong Chen; Noboru Minakawa; Liwang Cui; Guiyun Yan (Journal of Insect Behavior, 2008)

A myxobacterium strain Sorangium cellulosum AHB125 producing epothilone B and other anticancer substances - Wen-Jie Guo; Guan-Jun Tao; Wen-Yi Tao; Feng-Jie Cui; Xian-Chun Jin; Fang Bi; Zheng-Hong Xu; Zong-Hua Ao (Natural Product Research, 2007)

Alleviating soil sickness caused by aerobic monocropping: responses of aerobic rice to soil oven-heating - Lixiao Nie; Shaobing Peng; Bas A. M. Bouman; Jianliang Huang; Kehui Cui; Romeo M. Visperas; Hong-Kyu Park (Plant and Soil, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Effect of basic fibroblast growth factor (bFGF) on the treatment of exposure of the orbital implants - Hong-guang Cui; Hui-yan Li (Journal of Zhejiang University-SCIENCE B, 2007)

Amniotic membrane transplantation for porous sphere orbital implant exposure - Yan-hong Chen; Hong-guang Cui (Journal of Zhejiang University-SCIENCE B, 2007)

Possible involvement of integrin signaling pathway in the process of recovery from restraint stress in rats - Yu-Zhen Gao; Shi-Yu Guo; Qi-Zhang Yin; Xiang-Qin Cui; Tadashi Hisamitsu; Xing-Hong Jiang (Neuroscience Bulletin, 2007)

Wavefield continuation datuming using a near surface model - Xingfu Cui; Hongbing Li; Ying Hu; Hong Liang; Li Qi (Applied Geophysics, 2007)

Macrozoobenthic community of Poyang Lake, the largest freshwater lake of China, in the Yangtze floodplain - Hong-Zhu Wang; Qiao-Qing Xu; Yong-De Cui; Yan-Ling Liang (Limnology, 2007)

High production of laccase by a new basidiomycete, Trametes sp - Pingui Tong; Yuzhi Hong; Yazhong Xiao; Min Zhang; Xiaoming Tu; Tengjiao Cui (Biotechnology Letters, 2007)

Solid Substrate-Room Temperature Phosphorescence Method for the Determination of Trace Mn(II) Based on Oxidizing Reaction of Hydrogen Peroxide Using α,α′-Bipyridine as Sensitizer - Jia-Ming Liu; Xiao-Jie Cui; Fei Gao; Lai-Ming Li; Xiu-Chai Huang; Min-Lan Yang; Fei-Ming Li; Hong Wu (Journal of Fluorescence, 2006)

IGFBP7 plays a potential tumor suppressor role against colorectal carcinogenesis with its expression associated with DNA hypomethylation of exon 1 - Wen-jing Ruan; Jie Lin; En-ping Xu; Fang-ying Xu; Yu Ma; Hong Deng; Qiong Huang; Bing-jian Lv; Hu Hu; Jing Cui; Mei-juan Di; Jian-kang Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2006)

Detection and estrogen regulation of leptin receptor expression in rat dorsal root ganglion - Hong Ping Chen; Jingjing Fan; Sheng Cui (Histochemistry and Cell Biology, 2006)

High density porous polyethylene material (Medpor) as an unwrapped orbital implant - Yan-hong Chen; Hong-guang Cui (Journal of Zhejiang University-SCIENCE B, 2006)

MHC-BPS: MHC-binder prediction server for identifying peptides of flexible lengths from sequence-derived physicochemical properties - Juan Cui; Lian Yi Han; Hong Huang Lin; Zhi Qun Tang; Li Jiang; Zhi Wei Cao; Yu Zong Chen (Immunogenetics, 2006)

The cytotoxic constituents from marine-derived streptomyces 3320# - Ren Hong; Gu Qianqun; Cui Chengbin; Zhu Weiming (Journal of Ocean University of China, 2006)

Characterization of a cDNA coding for an extracellular calmodulin-binding protein from suspension-cultured cells of Angelica dahurica - Guo-Hong Mao; Li-Xia Hou; Cun-Bao Ding; Su-Juan Cui; Da-Ye Sun (Planta, 2005)

Evaluation of five ab initio gene prediction programs for the discovery of maize genes - Hong Yao; Ling Guo; Yan Fu; Lisa A. Borsuk; Tsui-Jung Wen; David S. Skibbe; Xiangqin Cui; Brian E. Scheffler; Jun Cao; Scott J. Emrich; Daniel A. Ashlock; Patrick S. Schnable (Plant Molecular Biology, 2005)

Developmental analyses reveal early arrests of the spore-bearing parts of reproductive organs in unisexual flowers of cucumber (Cucumis sativus L.) - Su-Lan Bai; Yi-Ben Peng; Ji-Xin Cui; Hai-Tao Gu; Li-Yun Xu; Yi-Qin Li; Zhi-Hong Xu; Shu-Nong Bai (Planta, 2004)

The Nervous Supply to the Nasal Cavity of the Bactrian Camel (Camelus Bactrianus) - Sheng Cui; Jian Hong Wang; Zheng Ming Xie (Veterinary Research Communications, 2004)

Decolorization of azo dyes by Rhodobacter sphaeroides - Zhi-yong Song; Ji-ti Zhou; Jing Wang; Bin Yan; Cui-hong Du (Biotechnology Letters, 2003)

The property, age and formation environment of the palaeokarst in Qinghai-Xizang Plateau - Gao Quan-zhou; Cui Zhi-jiu; Tao Zhen; Liu Geng-nian; Hong Yun (Journal of Geographical Sciences, 2002)

Polymerase chain reaction analysis of laboratory generated bioaerosols - Zhai Junhui; Yang Ruifu; Che Fengxiang; Chen Meiling; Cui Hong (Aerobiologia, 1997)